Role of PICK1 in prostate cancer: Modulating epithelial-mesenchymal transition and immune escape through activation of UNC5A - Min Wei; Shuangshuang Zheng; Zehao Wang; Kaige Sheng; Lei Li; Junhong Liu; Yong Tang (Tissue and Cell, 2027)

Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

Mapping the dynamics of teleost mucin biosynthesis in mucous cells under physiological and immersion vaccination conditions in flounder (Paralichthys olivaceus) - Jincheng Wang; Linhui Tao; Xiuzhen Sheng; Yingqin Liu; Xiaoqian Tang; Jing Xing; Heng Chi; Wenbin Zhan (Aquaculture, 2027)

Tensile strength characteristics of unsaturated Hunan clay - Gaoliang Tao; Song Chen; Qing-sheng Chen; Wenxing Tang; Zhe Huang; Ziyue Li; Sanjay Nimbalkar (European Journal of Environmental and Civil Engineering, 2026)

Delayed flooding after green manure incorporation enhances microbial necromass formation and stabilization in paddy soils - Zhengbo Ma; Danna Chang; Qingxu Ma; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Sheng Tang; Guopeng Zhou; Davey L. Jones; Wolfgang Wanek; Qing Zhang; et al. (Soil Biology and Biochemistry, 2026)

HOXC9 transcriptionally activates NRP1 to promote cell malignant progression and immune evasion in colorectal cancer - Xiaofeng Qiu; Sheng Hu; Bingling Liao; Huijun Zhang; Yuncheng Tang; Qihua Xu (Molecular Genetics and Genomics, 2026)

Multifactorial drivers of Trichogramma pintoi parasitism in lepidopteran eggs - Zhou-Yan Liu; Jian-Jun Yue; Nicolas Desneux; Lian-Sheng Zang; Zheng-Peng Yang; Zhen Yan; Liang-De Tang (Crop Protection, 2026)

Qianlong Shutong Formula alleviates benign prostatic hyperplasia associated with the regulation of inflammation, fibrosis and the Hippo-YAP/TAZ pathway - Ze-chao Zhang; Xue-jin Ye; Chang-jie Shang; Zhi-feng Wei; Yu Chen; Shu-ping Huang; Min Zhu; Bo-tao Tang; Tai-sheng Liang (Tissue and Cell, 2026)

Effects of single and double deletion of Vibrio anguillarum histone-like protein HU subunits on biofilm formation and pathogenicity in flounder (Paralichthys olivaceus) - Jiahui Zhang; Qiwei Sun; Wenting Wang; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan; Zhihai Sui; Heng Chi (Fish & Shellfish Immunology, 2026)

Long-term cultivation of indica–japonica hybrid rice increases grain yield, belowground carbon inputs, and soil organic carbon pools in paddy fields - Jinjia Gan; Sheng Tang; Lingli Mao; Fan Liu; Kefeng Han; Lianghuan Wu; Qingxu Ma (Field Crops Research, 2026)

Straw-derived carbon powder (SDCP) and PDMS co-functionalized melamine sponge for high-efficiency oil-water separation - Ruiyi Han; Haiyang Huang; Jingjing He; Taipeng Jiang; Yingying Wang; Lingling Zeng; Sheng Chen; Jianyong Tang; Jin Li; Zhuwei Gao (Desalination, 2026)

Salvia miltiorrhiza biochar-supported single-atom iron activates peroxymonosulfate degrading tetracycline hydrochloride via non-radical Fe(IV)=O and 1O2 synergy - Sheng Liu; Yuan Pan; Xiansheng Zhang; Shanqing Tang; Xinyi Huang; Teng Li; Yunze Wang; Ruilin Cao; Yu Zhang; Zhifeng Liu (Colloids and Surfaces C: Environmental Aspects, 2026)

Disguise strategy-adjusted controlled cleavage of DNA hydrogel for precision theranostics in colorectal cancer - Bo Han; Haitao Cui; Wenhui Chen; Zixiao Ma; Dandan Liang; Dongyang Wang; Jinghui Zhang; Juan Song; Sheng Tang (Chemical Engineering Journal, 2026)

Structural color meets photoprotection: Chiral nanocellulose photonic powders functionalized with lignin nanoparticles - Jiyu Yang; Haixin Wang; Kai Feng; Zeqi Tang; Yiran Yang; Yuwei Qiu; Yadong Xu; Sheng Chen; Yuyue Zhong (Chemical Engineering Journal, 2026)

Valorization of microalgal lipids for the production of high-value bio-based epoxidized monomers - Jiarong Tian; Siyuan Zhang; Yue Liu; Wei Rao; Kuichuan Sheng; Jun Wang; Yu Tang; Shaoqing Cui (Biomass and Bioenergy, 2026)

Facile aqueous synthesis of ionic liquid/phosphotungstic acid co-functionalized MOF-808@silica composite for efficient mixed-mode liquid chromatography - Zhipeng Zeng; Yanjuan Liu; Jingyao Xu; Wenxu Xu; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2026)

Real-time surrounding rock characterization and dynamic prediction of tunneling parameters for TBM in traffic tunnels based on deep sequential networks and feature fusion - Jie Xu; Siyi Tang; Quansheng Liu; Shuang Shu; Mengping Sheng (Transportation Geotechnics, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Nitrogen removal characteristics and mechanisms of the assimilation-dominated and acid-tolerant heterotrophic nitrifying-aerobic denitrifying Acinetobacter soli HY24 - Yuanli Wang; Wei Xu; Fuyang Li; Song Tang; Xin Tan; Shufang Tian; Xiaolong Wu; Shenghua Wei; Jie Zhao; Yequan Sheng; Yanbin Li (Journal of Water Process Engineering, 2026)

From black box to transparency: Explainable artificial intelligence driven origin identification of Xinjiang Nilka black bee honey - Xiao-Hui Sun; Lin-Hua Shi; Xiang-Shuai Li; Xiu-Ying Tang; Hong-Song Ren; Sheng-Hong Liu (Food Chemistry, 2026)

Electrospun chitosan/PCL/Tween-80 nanofibers incorporated with Ocimum basilicum essential oil as bio-based active packaging materials - Qi Liu; Shuqing Wang; Junjun Liang; Hong Chen; Sheng Jiang; Lin Tang (Food Bioscience, 2026)

SMX reshapes algal communities in blooms by altering algal metabolism and the potential functions of phycosphere bacteria - Xiaxia Li; Sheng Sheng; Musheng Ji; Jing Hu; Sijing Tang; Yin Liu; Jin Qian (Environmental Pollution, 2026)

Optimized fertilization boosts maize yield and soil multifunctionality in acidic red soils via microbial function modulation - Sheng Zhao; Mei Sun; Geng Sun; Shanpeng Liu; Yuqing Tang; Yu Jiang; Zedong Long; Kai Ouyang (European Journal of Agronomy, 2026)

Rational Ba doping induces multiphase architecture in PrNi0.5Co0.5O3-δ for enhanced triple conductivity in protonic ceramic electrochemical cells - Mengjun Tang; Xiao Zhang; Waqas Muhammad; Yinghua Niu; Sheng Ma; Zuorui Xin; Jiaqi Wang; Tingting Liu; Mian Li; Liping Dai; Jinquan Wang; Zihao Xu; et al. (Chemical Engineering Journal, 2026)

Defect-engineered CuO nanosheets promote asymmetric *CO-*CHO coupling for ampere-level CO2-to-C2+ electroreduction - Lei Pan; Yaxin Jin; Siyu Tang; Zhanpeng Liang; Yihan Xu; Jianlong Lin; Jie Li; Yuyi Qin; Xinyun Hu; Yuanyuan Xu; Jiahao Zhou; Wei Wang; et al. (Chemical Engineering Journal, 2026)

Redefining the control volume of PFAS thermal treatment: Achieving systemic net reduction via closed-loop GASMILD combustion - Wei Tang; Yi-Che Hsiao; Sheng-Lun Lin; Jhong-Lin Wu; Chien-Er Huang (Chemical Engineering Journal, 2026)

Unlocking the chromatographic potential of emerging hydrogen-bonded/metal-organic frameworks as advanced functional materials for silica stationary phase - Linjun Zuo; Yanjuan Liu; Hongjie Wang; Ruiping Xu; Yuefei Zhang; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Sultr1;2 in tomato mediates the recruitment of Streptomyces to activate selenium and passivate cadmium in rhizosphere soil - Zheng Lei; Jiandong Sheng; Xiang Huang; Suping Wang; Zhen Wang; Jiliang Lü; Keliang Pan; Huaxing Wang; Yanni Tang; Huan Zhang; Peng Cai; Xiaohu Zhao (Soil Biology and Biochemistry, 2026)

Tackling antibiotic resistance genes as environmental contaminants: Innovations in advanced oxidation processes and strategic solutions - Chen Gao; Liang Zhang; Linlin Zang; Hian Kee Lee; Sheng Tang (Journal of Environmental Sciences, 2026)

Valorization of coffee Silverskin into a novel dietary Fiber ingredient: A comprehensive study on structure, and in vitro/in vivo antioxidant activity - Chen Dai; Run Tang; Ziyu Guo; Weixing Yang; Xiaoyu Gao; Jun Sheng; Yang Tian; Jia Liu (Food Research International, 2026)

Green extraction of non-starch polysaccharides from millet using a deep eutectic solvent: structural elucidation and structure-activity relationship of their inhibition of α-glucosidase - Yuxin Li; Rui Fang; Xia Tang; Pravin Ojha; Jingke Liu; Qinghai Sheng; Liangfu Zhou (Food Chemistry, 2026)

Unraveling the cholesterol-lowering mechanism of a Lactobacillus rhamnosus S_82 and xylo-oligosaccharides synbiotic in sour cream - Xuemeng Fu; Wenhao Zhao; Dongyao Li; Na Zhang; Miaoshu Wang; Xia Tang; Qinghai Sheng; Hongtao Tian; Chen Li (Food Microbiology, 2026)

Regulations of Gata-3 on CD4+ T cell differentiation via its zinc finger domains in flounder (Paralichthys olivaceus) - Zhixiang Duan; Ziyang He; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Jing Xing; Wenbin Zhan (Fish & Shellfish Immunology, 2026)

Function identification of nitrogen forms in nitrogen-doped biochar for promoting methane production in anaerobic digestion - Xiao-Yue Cao; Cong-Cong Tang; Shuo-Han Chen; Sheng-Jie Sun; Chun-Xue Yang; Ai-Juan Zhou; Zewei Liu; Zhang-Wei He (Environmental Research, 2026)

Chronic paracetamol exposure disrupts behavior and induces intrinsic apoptosis in a freshwater bivalve - Yun-xia Hou; Shi-yin Tang; Wang Liu; Zhi-tong Li; Kai-jian Wei; Xiang-sheng Hong; Jian-hui Qin; Jin-miao Zha (Environmental Pollution, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Tailored Cu active sites in 2D MOF-derived carbon nanosheets for dual electrochemical detection of chloramphenicol and paracetamol - Zhi-Lun Wu; Tsai-Ting Liu; Mei-Hong Tang; Sheng-Fei Lin; Yu-Jen Shih (Chemical Engineering Journal, 2026)

Morphology engineered Fe-MOFs regulating electronic configuration to enable singlet oxygen driven efficient degradation of antibiotics and ARGs - Yifan Jin; Rongxuan Xu; Chen Gao; Yinting Zhang; Shuhan Zhang; Liang Zhang; Sheng Tang (Chemical Engineering Journal, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

From lignin-carbohydrate complex cleavage to mesoporous cellulose: A multi-scale study on diethylene glycol-ferric chloride pretreatment of timothy straw - Song Tang; Fei Zhou; Bokun Zhou; Jun Li; Jiale Zhang; Junting Li; Jing Zhang; Xin Tan; Yequan Sheng (Biomass and Bioenergy, 2026)

Aphid–plant interactions: from molecular games to ecological outcomes - Zi-Meng Gui; Liang-De Tang; Lian-Sheng Zang; Ricardo Ramirez-Romero; Tong-Xian Liu (Journal of Pest Science, 2026)

Host plant-mediated effects on eri silkworm fitness and Trichogramma parasitoid efficacy - Yue Sun; Ji-Zhi Xue; Liang-De Tang; Nicolas Desneux; W. H. Jayasinghe; Lian-Sheng Zang (Journal of Pest Science, 2026)

Bioactivity assessment of selenium nanoparticles biosynthesized by Akkermansia muciniphila - Xiaoya Sheng; Xilong Deng; Weiyi Zheng; Jingpeng Yang; Xuna Tang (Archives of Microbiology, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

RT-BFE network: A lightweight deep learning model for real-time beef freshness evaluation and edge devices deployment - Weidong Xu; Yingchao He; Liming Que; Caitian Tang; Jiaheng Li; Chunxu Zhang; Qirong Dong; Huadong Sheng; Pengpeng Liu; Wenjun Wang; Donghong Liu (Computers and Electronics in Agriculture, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Retraction notice to “Synthesis and application of waste-based layered double hydroxide: A review” [Sci. Total Environ. 903 (2023) 166245] - Yimei Jiang; Zhengtao Shen; Chao-Sheng Tang; Bin Shi (Science of The Total Environment, 2026)

Retraction notice to “Analysis and study of the migration pattern of microplastic particles in saturated porous media pavement” [Sci. Total Environ. 861 (2023) 160613] - Sheng Liu; Jiayan Wu; Leiye Sun; Minye Huang; Xiaoshan Qiu; Hongmei Tang; Jieyu Liu; Pingxiao Wu (Science of The Total Environment, 2026)

Dynamic communication topology based formation control with double-loop controller for multiple AUVs - Wenkai Zhang; Min Yu; Haoyu Liu; Sheng Gao; Runda Lin; Qirong Tang (Ocean Engineering, 2026)

Climatic drying-wetting cycles induced dynamic coupling effect between 3D soil desiccation cracking and moisture redistribution - Yu-Xuan Chen; Jun-Zheng Zhang; Chao-Sheng Tang; Run-Yang Lan; Qing Cheng; Jin-jian Xu; Ben-Gang Tian (Journal of Hydrology, 2026)

Engineering zirconium-based MOFs for selective adsorption of estrogenic contaminants and the application in electrospun solid-phase microextraction - Senwei Jiang; Xiaoqian Liu; Tianxi Yang; Evgen Multia; Sheng Tang; Hua Jin; Daodong Pan; Zhen Wu; Hangzhen Lan (Journal of Hazardous Materials, 2026)

Competitive mechanism of lauric acid drives the formation of V-type starch for delaying starch retrogradation - Zijun Yu; Wenjing Li; Zhijie Zhu; Juan Tang; Bulei Sheng; Xu Chen (Food Chemistry, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Surface-interior browning differentiation in chestnut kernels across maturation: Insights from integrated transcriptomic and metabolomic profiling - Weiwei Jiang; Junwei Yuan; Ziting Zhang; Yifan Gu; Sheng Tao; Xiaoyu Liu; Peng Wang; Kuo He; Haifen Wang; Yao Tang; Yuqian Jiang (Food Bioscience, 2026)

Intraperitoneal extracellular trap-derived proteins mediate the amplification of vaccine-induced immune responses in flounder (Paralichthys olivaceus) - Jiahui Zhang; Qian Li; Xiaoqian Tang; Chengxu Ha; Jing Xing; Xiuzhen Sheng; Wenbin Zhan; Heng Chi (Fish & Shellfish Immunology, 2026)

Construction full-process detection of geometric imperfections in complex reticulated shells with curved steel members - Hao-Ran Tang; Jian-Sheng Fan; Min Jiao; Guo-Hua Zeng; Hong-Jun Guo; Yu-Fei Liu (Engineering Structures, 2026)

An improved method for Gill’s hematoxylin and eosin staining based on the optimal acetic acid ratio - Zhijie Ma; Caixia Sheng; Danju Wu; Huimin An; Wen Tang; Ping Zhao; Guoxiang Fu (Histochemistry and Cell Biology, 2026)

Fracture behavior and constitutive modeling of rock-concrete contact surfaces with different roughness under freeze–thaw cycles - Mengyuan Cui; Taoying Liu; Yeshan Sheng; Min Tang; Wenbin Cai; Longjun Dong (Bulletin of Engineering Geology and the Environment, 2026)

MAPK signaling pathway and rhizosphere modulation: mechanisms of arbuscular mycorrhizal symbiosis in enhancing Phragmites communis tolerance to triclocarban stress - Yin Liu; Sheng Sheng; Bianhe Lu; Jing Hu; Kailin Xu; Junwei Shen; Sijing Tang; Jin Qian (Mycorrhiza, 2026)

Multi‐Model Ensembles in Ecosystem Modeling: Challenges and Best Practices for Decision‐Making - Kaiyu Guan; Rongzhu Qin; Zewei Ma; Lei Zhao; Licheng Liu; Sheng Wang; Trevor F. Keenan; Mengqi Jia; Debjani Sihi; Eric Potash; Senthold Asseng; Jingyun Tang; et al. (Global Change Biology, 2026)
Ecosystem models are increasingly central to the decision‐making for environmental policy, conservation planning, and climate‐related investments. Yet, the growing reliance on Multi‐Model Ensembles (MMEs) of ecosystem models by practitioners and policymakers, sometimes under tight timelines and imperfect information, has frequently outpaced the scientific rigor required to ensure ensemble reliability. Here, MMEs refer to approaches that combine targeted predictions from multiple models with the expectation of improving robustness and quantifying predictive uncertainty. Poorly designed MMEs may create a false sense of confidence and lead to suboptimal policy and market decisions. This perspective argues that robust decision‐making‐relevant MMEs must be grounded on two pillars: (1) rigorous Model Intercomparison Projects (MIPs), which identify inter‐model agreement and disagreement, characterize model uncertainties, and evaluate robustness with observationally based benchmarks—MIPs' diagnostic evaluation is so critical that it must be needed to drive MME's decision in model selection and weighting, especially when only a limited number of models available; and (2) co‐design by both stakeholders and scientists to ensure that scenarios, metrics and uncertainty requirements provide decision‐relevant information. Building upon the past success and lessons from the existing MIPs‐MMEs efforts (e.g., climate/Earth system/crop), we derived the theoretical basis for MMEs, addressed their specific challenges in ecosystem modeling, and highlighted proper consideration of model numbers and diversity, risk of model inter‐dependence, effective calibration of model parameters, possible overdue of some ecosystem model development, critical roles of open benchmark data across a wide range of conditions, and suggested use of Artificial Intelligence to support MIPs‐MMEs. We highlighted the under‐recognized opportunity for MIPs and MMEs to drive scientific progress and innovation through identifying better performing models, systematic benchmarking, feedback loops, and targeted model improvement. By following actionable best practice guidelines, MMEs can evolve from ad hoc aggregation of models into a trusted backbone of environmental policy and decision‐making.

The regulatory role of HIRRV nucleoprotein on STING-mediated interferon response - Pingyuan Sun; Wenshuo Li; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2026)

Optical retrieval of sea surface wave parameters using China’s HY-1E Coastal Zone Imager - Lifeng Wang; Qingjun Song; Mingxiu Wang; Sheng Yang; Ziyao Yin; Jun Tang; Hang Lü; Keli Zhang; Yuze Cao; Lili Wang; Yuntao Wang; Yingcheng Lu (Journal of Oceanology and Limnology, 2026)

A Predictive Model for the Characterization of the Influence of Thermal Damage Defect Scale on the Mechanical Properties of MICP-Healed Rock Fractures: Insights from Microchanical Testing and Nano-CT Imaging - Qi-Chen Dai; Xiao-Hua Pan; Han-Jiang Lai; Chao-Sheng Tang; Zhi-Hao Dong (Rock Mechanics and Rock Engineering, 2026)

Establishment and Application of a Triple TaqMan qPCR Detection Method for IMNV, DIV1, and CMNV - Yuzhi Wang; Chuang Cui; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Fish Diseases, 2026)
The escalating incidence of emerging pathogens and their propensity for co‐infection pose a severe threat to the sustainable intensification of Penaeus vannamei aquaculture. To address this challenge, a novel triplex TaqMan quantitative PCR (qPCR) assay was developed for the simultaneous detection of three high‐risk agents: Infectious Myonecrosis Virus (IMNV), Decapod Iridescent Virus 1 (DIV1), and Covert Mortality Nodavirus (CMNV). This study not only establishes a robust multiplex platform but also systematically optimises its performance, achieving superior analytical sensitivity and reproducibility compared to existing single‐target or duplex methods. The assay demonstrated a limit of detection as low as 10 1 copies/μL for all targets, with excellent inter‐ and intra‐assay coefficients of variation (CVs) consistently below 3%. Notably, the method effectively overcomes the technical hurdles associated with detecting both RNA (IMNV, CMNV) and DNA (DIV1) viruses within a single reaction, eliminating cross‐reactivity and ensuring high specificity. Validated against clinical samples, the established protocol exhibits a concordance rate exceeding 95% with current standard methods, while significantly streamlining the diagnostic workflow. This advancement provides a powerful tool for routine biosecurity monitoring, seed stock certification, and the comprehensive management of emerging shrimp diseases.

A new chlorine-containing flavanol and four new phenylpropanoids from Toddalia asiatica - Bing-Ying Zheng; Zhan-Tao Zhao; Feng Wu; Nan An; Shu-Qi Wu; Lu Gan; Sheng Yin; Run-Zhu Fan; Gui-Hua Tang (Natural Product Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Exploring geographical modal and its implications to support geographical integration - Zhuo Sun; Tianyu Sheng; Kai Wu; Peilong Ma; Zihao Tang; Dichen Liu; Min Chen; Guonian Lü (Science Bulletin, 2026)

Melt vitrification of washed and unwashed municipal solid waste incineration fly ash: Product stability, metal migration, and process burden - Huikang Song; Yaji Huang; Sheng Wang; Hao Shi; Tianhang Tang; Hao Liu; Daiyang Li; Chenlu Yang; Shengli Song (Process Safety and Environmental Protection, 2026)

Harnessing synergistic magnetic and affinity effects in a Fe/La composite enables rapid selective phosphate removal from actual municipal wastewater - Zhijun Zhou; Jun Huang; Jingyu Liu; Yalan Ma; Xing Wu; Sheng Hu; Fubing Yao; Xi Tang; Chong-jian Tang (Journal of Water Process Engineering, 2026)

Establishment of A triplex TaqMan qPCR assay for EHP, VpTPD, VpAHPND with optimized efficacy using methyl cellulose - Yuzhi Wang; Chuang Cui; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Invertebrate Pathology, 2026)

Spatiotemporal changes of salt crusts in the Ebinur Lake Basin (2005–2025) using a non-linear spectral unmixing model - Chen-Wei Wang; Xiao-Xiao Zhang; Xiao-Ming Cao; Yi-Ming Feng; Jia-Qiang Lei; Sheng-Yu Li; Jia-Xiu Zou; Jie Zhou; Lian-You Liu; Zi-Fa Wang; Xiao Tang (Journal of Arid Environments, 2026)

Drying induces Mars intermediate-sized cracks: New evidence and insight from geometrical quantification - Jin-Jian Xu; Hao Zhang; Chao-Sheng Tang; Yaowen Yang; Mohamed Ramy El-Maarry; Lin Li; Bin Shi (Icarus, 2026)

A self-assembling ferritin nanoparticle vaccine based on SpyTag/SpyCatcher elicits protective immunity against largemouth bass ranavirus - Jia-Lun Tang; Xue-Feng Wei; Jun-Yao Xia; Jun-Jie Sheng; Zhao Zhao; Bin Zhu (Fish & Shellfish Immunology, 2026)

Teleost bone morphogenetic protein 2 (BMP2): Dynamic responses to infection and negative feedback regulation of inflammatory cytokines in gills of flounder (Paralichthys olivaceus) - Zefan Xu; Yingqin Liu; Xiuzhen Sheng; Xiaoqian Tang; Jing Xing; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2026)

PPy/PDMS-functionalized delignified wood aerogel: Photothermal-electrical dual-energy empowerment and all-weather oil–water separation performance - Taipeng Jiang; Jian Wu; Jingjing He; Sheng Chen; Jianyong Tang; Yingying Wang; Lingling Zeng; Ruiyi Han; Haiyang Huang; Jin Li; Zhuwei Gao (Bioresource Technology, 2026)

A novel antagonist of Vibrio pathogens for aquaculture: Isolation, characterization and probiotic potential of Bacillus safensis ZY-1 from marine sediments - Ziyue Yang; Xiaolei Wang; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan; Heng Chi (Aquaculture, 2026)

Effects of gradation on particle breakage and mechanical behaviour of coral sand - Yuan-yi Chen; Fu-sheng Zha; Cai-ying Chen; Yi Tang (Transportation Geotechnics, 2026)

Hirsutanines H−O, monoterpene indole alkaloids from Uncaria hirsuta with neuroprotective effects - Nan An; Lei-Ming Wu; Shu-Qi Wu; Jia-Luo Huang; Dong Huang; Fang-Yu Yuan; Yi-Ling Liao; Run-Zhu Fan; Xian-Yuan Yang; Gui-Hua Tang; Lu Gan; Sheng Yin (Phytochemistry, 2026)

Eremophilane-type sesquiterpenes from Ligularia hodgsonii: isolation, structural characterization, and pro-angiogenic potential - Zhenhua Wan; Huilin Peng; Chunping Tang; Jiangjiang Qin; Bintao Hu; Changqiang Ke; Sheng Yao; Ligen Lin; Yang Ye (Phytochemistry, 2026)

Revealing the roles of biochar in anaerobic digestion of waste activated sludge with the overloading accumulation of humic acids - Wen-Tao Li; Fei Wang; Qing-Bin Meng; Sheng-Jie Sun; Cong-Cong Tang; Lei Yang; Jun Lan; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Spatially decoupled active centers in molecularly imprinted Fe3O4/TiO2@P3HT heterojunctions for enhancing non-radical pathways - Chuang Zou; Xinrui Yang; Liguang Tang; Xinyang Li; Yangrui Xu; Yu Cheng; Xinlin Liu; Sheng Feng; Hong Liu; Jie Jin; Ziyang Lu (Journal of Environmental Chemical Engineering, 2026)

Sustainable solidification/stabilization of chromium (VI)-contaminated soil using enzyme-carbonated reactive magnesia cement: a novel eco-friendly approach - Min Shi; Dian-Long Wang; Jin-Yu Shi; Wen-Bo Chen; Hai-Long Li; Yue-Suo Yang; Chao-Sheng Tang (Journal of Environmental Management, 2026)

Polystyrene nanoplastics promote adipogenesis by stimulating nuclear translocation of PPARγ - Yuchen Zheng; Zijia Liu; Zijie Zhao; Chao Sheng; Wenzhuo Li; Duo Tang; Yunlu Ning; Renhang Zhou; Ao Li; Zhixiang Zhou (Food and Chemical Toxicology, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

De novo-engineered circular DNAzymes with topological rigidity for multiplexed fluorescent-temporal barcoding - Jing Sheng; Ruijia Deng; Liu Feng; Ben Niu; Meilin Gong; Shuang Zhao; Zuowei Xie; Shuang Xie; Yu Tang; Jie Luo; Jingsen Cao; Jiaqi Liu; et al. (Chemical Engineering Journal, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Wear Analysis and Evaluation of Inserted-Tooth Disc Cutters During Shield TBM Tunneling in Soil-Rock Mixed Ground - Hao-Jie Wang; Xiao-Ping Zhang; Quan-Sheng Liu; Shao-Hui Tang (Rock Mechanics and Rock Engineering, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Research on the promoting effect of marine innovation policies on the high quality development of coastal cities - Sheng Gao; Xingyi Xing; Xiaoyu Tang (Journal of Coastal Conservation, 2026)

ZNF468 stabilization by RNF4 enhances apoptosis resistance and carboplatin resistance in breast cancer via transcription activation of XIAP - Juan Hu; Guo Tian; Peizhi Tang; Sheng Yuan; Bingjian Jiang (Genes & Genomics, 2026)

Ultrasensitive dual-detection of antibiotics in animal-derived foods by nucleic acid signal amplification-assisted magnetic dispersive solid-phase extraction - Zhuoyue Shen; Yitong Chen; Xiuqing Su; Yangtong Jing; Dezhao Kong; Chang Liu; Wei Shen; Hian Kee Lee; Sheng Tang (Analytica Chimica Acta, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Teleost intestinal microfold cells: identification, characterization, and mucosal antigen sampling in olive flounder (Paralichthys olivaceus) - Jiasong Sun; Manman Song; Xiuzhen Sheng; Yihe Feng; Xiaoqian Tang; Jing Xing; Heng Chi; Wenbin Zhan (Marine Life Science & Technology, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

New cutting tool wear testing method for evaluating the influence of foam additive on plowing effect during shield TBM tunnelling in dense sandy gravel ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Yu-Cong Pan; Wei-Qiang Xie; Xin-Fang Li; Hao-Jie Wang (Tunnelling and Underground Space Technology, 2026)

Autoinhibition and phospho-switch for the dynamic regulation of ion transport - Ren-Jie Tang; Chao Wang; Changhong Yang; Sheng Luan (Trends in Plant Science, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

RIME-optimized rule-free fuzzy PID controller for ship heading control - Huang Tang; Hao Ye; Jinlu Sheng (Ocean Engineering, 2026)

A combined biochar and biomineralization approach for enhanced soil Pb immobilization under accelerated aging - Huicong Hu; Zhengtao Shen; Chao-Sheng Tang; Wen Mu; Mengtao Wang; Sensen Li; Xiaohua Pan; Huan Liu; Bao-Jun Wang (Journal of Environmental Sciences, 2026)

Hierarchical phenomenon and mechanism in soil desiccation cracking - Chao-Sheng Tang; Tao Wang (Engineering Geology, 2026)

Surface cracks can play a positive role in bioconstruction of climatic buffer barrier on soils: Experimental and numerical evidence - Hao Liu; Chao-Sheng Tang; Chao Lv; Bo Liu; Xiao-Hua Pan (Engineering Geology, 2026)

Reconstructing the spatiotemporal distribution of microbial-induced carbonate precipitation using electrical conductivity tomography - Jun-Zheng Zhang; Chao-Sheng Tang; André Revil; Chao Lv; Jin-Jian Xu; Run-Yang Lan; Qi-You Zhou (Engineering Geology, 2026)

Electrostatically assembled rapid hemostatic powder with ultrafast gelation, robust wet adhesion, and enhanced bactericidal activity - Zhuoyi Sheng; Shicheng Huo; Chen Tang; Bo Wang; Yinghao Tian; Shifeng Yan; Jingbo Yin; Xiaogang Bao; Guohua Xu (Chemical Engineering Journal, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Microbial Community Traits and Necromass Dynamics Shape Soil Carbon Accumulation - Wankun Pan; Sheng Tang; Wolfgang Wanek; Zhongkui Luo; Ji Chen; Yuanhe Yang; Tida Ge; Karina A. Marsden; Guopeng Liang; David R. Chadwick; Xinping Chen; Andrew S. Gregory; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) sequestration is vital for food security and climate mitigation. However, its long‐term response to fertilisation remains unclear. Using the 180‐year Broadbalk Experiment (the world's longest‐running fertilisation trial; Rothamsted, UK), combined with 14 C labelling and metagenomics, we identified fundamentally distinct mechanisms of SOC accumulation: a microbially mediated dual pathway under organic fertilisation versus a resource‐limited pathway under inorganic fertilisation. Sustained organic inputs matched inorganic fertilisers in maintaining crop yields while increasing total SOC by 160% (relative to a no‐fertilisation control), far exceeding the 26% gain under inorganic fertilisation. Mechanistically, the continuous supply of labile organic matter provided an energetic surplus, allowing copiotrophic microbial communities with high carbon use efficiency to reduce investment in energy‐intensive enzyme synthesis. This metabolic efficiency facilitated a dual‐pathway expansion, elevating dynamic particulate organic carbon (POC) from 1.4 to 7.5 g kg −1 , while microbial assimilation and necromass accumulation concurrently increased mineral‐associated organic carbon (MAOC) from 6.8 to 21.5 g kg −1 . Conversely, inorganic fertilisation induced an oligotrophic ‘mining’ strategy, in which microorganisms upregulated the degradation of complex organic matter under carbon‐limited conditions, restricting sustained SOC accumulation primarily to the MAOC pool. A global meta‐analysis of field experiments (0–120 years) corroborated these temporal trajectories across diverse soil types, showing that SOC under organic fertilisation increases in a time‐dependent manner, reaching a 77% gain after 80 years (three‐fold greater than under inorganic inputs). Overall, organic fertilisation enhances total SOC via POC and MAOC accumulation, whereas inorganic fertilisation mainly increases MAOC. Long‐term SOC persistence depends not only on carbon inputs, but also on microbial community traits and necromass dynamics, suggesting that aligning nutrient inputs with these biological mechanisms is critical for sustainable carbon sequestration.

A Physics-Constrained Self-Supervised Neural Network Approach for Multi-Channel Magnetotelluric Noise Separation - Chang-sheng Liu; He-ran Wang; Cai-tang Sun (Applied Geophysics, 2026)

The binding of HIRRV phosphoprotein to TBK1 suppressed IRF3 phosphorylation to facilitate viral replication in HINAE cells - Feixiang Rong; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2026)

Chloride-retaining co-melting of municipal solid waste incineration fly ash for network-breaking index-guided metal recovery and vitrification - Huikang Song; Yaji Huang; Sheng Wang; Hao Shi; Tianhang Tang; Hao Liu; Junfeng Pang; Haiyun Zhou; Can Li (Waste Management, 2026)

Synergistic advanced oxidation and Cu⁺ release by microscale Fe/Cu bimetals for efficient Escherichia coli inactivation - Zhixue Zhang; Junchen He; Anli Liu; Shangyu Yang; Chengwan Wang; Yue Yuan; Qinmei Zhong; Wei Tang; Xian Wu; Sheng-Tao Yang (Process Safety and Environmental Protection, 2026)

Configurable physics-informed operator network for real-time multi-scenario hydrodynamics in river networks - Bingxi Huang; Huiming Zhang; Sheng Jiang; Hongwu Tang; Saiyu Yuan; Xiao Luo; Zhaohui Chen (Journal of Hydrology, 2026)

Manure dissolved organic matter affects antibiotic mobility in soil by altering the composition and nature of adsorption sites - Jin-Sheng Hu; Hui-Yun Xiao; Xiang-Yu Tang; Yu-Juan Lv; Jian-Hua Cheng; Xiao-Yu Li (Journal of Environmental Chemical Engineering, 2026)

In-situ sulfur fixation using aluminum-based sorbents during the pyrolysis of sulfur-containing waste polymers - Yue Sheng; Longfei Tang; Peipei Gao; Weitong Pan; Lu Ding; Xueli Chen; Fuchen Wang (Journal of Environmental Management, 2026)

Co-pyrolysis of polyphenylene sulfide with various plastics: Sulfur migration and interaction mechanism - Yue Sheng; Longfei Tang; Weitong Pang; Siman Nie; Lu Ding; Xueli Chen; Xudong Song; Fuchen Wang (Journal of Environmental Chemical Engineering, 2026)

Zinc-iron layered double hydroxide enhances cadmium tolerance in tobacco via cell wall immobilization and regulation of phenylpropanoid and nitrogen metabolism - Xiaoyan Sui; Zhenyu Zhao; Qiang Ma; Zhongqing Liu; Sheng Zhang; Jianbing Ding; Zhengyu Deng; Pengfei Yi; Weijie Yan; Xiaoxuan Yi; Haocun Tang; Zhenhua Wang; et al. (Journal of Environmental Management, 2026)

Microbial-induced birnessite transformation under different redox conditions and its impact on lead adsorption - Yuanyuan Geng; Guanyu Zhang; Lingyi Tang; Xiaoliang Fan; Huan Liu; Baojun Wang; Chao-Sheng Tang; Bin Shi; Daniel S. Alessi; Zhengtao Shen (Geochimica et Cosmochimica Acta, 2026)

Engineering oxygen defects in non-noble metal catalysts for advanced VOCs Destruction: Progress and Opportunities - Xuan Wang; Fangxu Lu; Nan Sheng; Shiya Tang; Feng Sun; Bing Sun; Jing Zhang; Wei Xu; Zhe Yang (Fuel, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Long-term cultivation of indica–japonica hybrid rice reshapes the sustainability of rice systems by simultaneously enhancing yield, nitrogen use efficiency, and soil health - Jinjia Gan; Xinyue Xu; Sheng Tang; Kefeng Han; Tao Sun; Jinzhao Ma; Xiangde Yang; Xiu Liu; Haoran Fu; Zhihao Pang; Lingli Mao; Lianghuan Wu; et al. (European Journal of Agronomy, 2026)

Climate-induced soil hydro-thermal response on sunny and shady slopes incorporating crack effects - Zhao-Jun Zeng; Chao-Sheng Tang; Tao Wang; Eng-Choon Leong; Qing Cheng; Bin Shi (Engineering Geology, 2026)

Dialysis-controlled sulfur substrate delivery enhances Sulfur-Autotrophic denitrification under oxygen stress - Jingyu Liu; Huize Guan; Sheng Hu; Huifeng Lu; Xi Tang; Chong-Jian Tang (Bioresource Technology, 2026)

The mechanisms and functions of mitochondria-encapsulating extracellular vesicles - Danli Sheng; Xiangyu Chen; Jing Shi; Hongyun Tang (Science China Life Sciences, 2026)

Applications of Piezoelectric Stimulation in Tissue Engineering - Beini Sheng; Jingrui Xing; Biao Song; Yuwei Gao; Hongmei Tang; Miao Xiao (Journal of Medical and Biological Engineering, 2026)

Revealing the mucosal immune microenvironment of teleost: An in-situ atlas of the nasal mucosa in flounder (Paralichthys olivaceus) - Jincheng Wang; Xiuzhen Sheng; Xiaoqian Tang; Jing Xing; Heng Chi; Wenbin Zhan (Aquaculture, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Biochar pyrolysis temperature determines the efficacy of 3, 4-dimethylpyrazole phosphate (DMPP) in reducing N2O emissions from low cadmium-contaminated paddy soil - Muhammad Laeeq Ur Rehman HASHMI; Muhammad Zia Ur Rahman HASHMI; Yasir HAMID; Bilal HUSSAIN; Tang SHENG; Wenjie LIU; Adnan ARSHAD; Tingqiang LI (Pedosphere, 2026)

Self-enhancing climatic resilience of surface soil through bio-carbonation constructed barrier - Rui Wang; Chao-Sheng Tang; Guang-Hui Lei; Xiao-Hua Pan; Zhi-Hao Dong; Shao-Dan Wang; Xiancai Lu (Engineering Geology, 2026)

Solidification of high water content marine deposits by a novel in-situ treatment of magnesia-based bio-cement: Insight from clay content effect - Dian-Long Wang; Wen-Bo Chen; Hao-Yu Fang; Zhen-Yu Yin; Xiao-Hua Pan; Chao-Sheng Tang (Engineering Geology, 2026)

Fluorine decorated strategy toward MOFs-based quasi-solid-state electrolyte for significantly promoting the lithium-ion transport performance in a wide temperature range - Xin Zhang; Sheng Jin; Jianing Yang; Xinyu Tang; Xiaomin Kang; Zhiliang Liu (Chemical Engineering Journal, 2026)

Fabrication of bioinspired coral reef-like superhydrophobic coating via interfacial polymerization: Towards all-weather high-viscosity oil remediation and de-icing performance - Yingying Wang; Shangmin Si; Taipeng Jiang; Sheng Chen; Jinging He; Jianyong Tang; Jian Wu; Weijie Wei; Lingling Zeng; Jin Li; Zhuwei Gao (Bioresource Technology, 2026)

Physiological and molecular responses to sodium acetate addition and supplementation in the two stages of Haematococcus pluvialis - Yanbin Li; Weizhao Han; Na Li; Tian Xie; Xin Tan; Song Tang; Yequan Sheng; Bangxiang He (Journal of Oceanology and Limnology, 2026)

A Forecasting Paradigm Shift: From Traditional Methods to Physics–AI Combination in China’s National-Level Severe Convective Weather Operations - Yongguang Zheng; Bo Yang; Jie Sheng; Kanghui Zhou; Fuyou Tian; Xiaowen Zhang; Xiaoling Zhang; Yu Lan; Yancha Cao; Xinhua Liu; Wenyuan Tang; Tao Zhang; et al. (Advances in Atmospheric Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Flux dynamics and scenario simulation of PFAS under extreme hydrological perturbations in urban tributary flowing into the Yangtze River: A focus on floods - Hui Xiao; Ge Tang; Sheng Zhang; Zeqiang Wu; Qi Liu; Shaoyan Feng; Yifan Fan; Tong Liu; Xin Qian; Huiming Li (Journal of Hazardous Materials, 2026)

Identification of novel B-cell epitopes on Hirame novirhabdovirus (HIRRV) G protein and development of a multi-epitope vaccine - Pingyuan Sun; Lining Zhao; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2026)

Improving hydro-mechanical response of heavy metal contaminated soil to rainfall events through combination of biochar and microbial induced carbonate precipitation (BM) treatment - Huicong Hu; Chao-Sheng Tang; Zhengtao Shen; Xiaohua Pan; Kai Gu; Mengtao Wang; Wen Mu; Bao-Jun Wang; Huan Liu; Zhihan Ji; Weiqiang Li (Engineering Geology, 2026)

Molecular dynamics simulation on microscopic water evaporation process from montmorillonite surface - Yue You; Chao-Sheng Tang; Siqi Zhang; Zhu-Yuan Lin; Tao Wang (Computers and Geotechnics, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

Comparative study on the mechanisms of citrus pectin and polygalacturonic acid in alleviating food allergies - Xin Liu; Xiang Tan; Sheng Tang; Feiyang Yang; Ge Wang; Wenjue Gao; Junying Bai; Linhua Huang (Carbohydrate Polymers, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

Bidimensional regression and order relations: evaluating sketch maps with various spatial knowledge and distortions - Chen Zhang; Ming Tang; Rajasirpi Subramaniyan; Yuewei Jiang; Yehua Sheng (Cognitive Processing, 2026)

Livestock-induced changes in soil properties and microbial dominance determine soil microbial diversity in a conifer forest - Fan Fan; Jiangling Zhu; Kai Dong; Suhui Ma; Chengjun Ji; Zhiyao Tang; Shaopeng Wang; Xiaoli Shen; Sheng Li; Jingyun Fang (Soil Ecology Letters, 2026)

Soil quality and key bacteria mediate slash mulching-induced growth and carbon storage improvements in Eucalyptus plantations - Qin Ke; Lingyue Zhu; Junyu Zhao; Kangting Huang; Liangfen Li; Yilin Weng; Jianke Wen; Xiuhai Wang; Lijun Chen; Sheng Lu; Zuoyu Qin; Lichao Wu; et al. (Applied Soil Ecology, 2026)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: A Predictive Model for Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Qi-Chen Dai; Bin Shi (Rock Mechanics and Rock Engineering, 2026)

Biocontrol potential of the egg-larval parasitoid Chelonus bifoveolatus and egg parasitoid Telenomus remus against fall armyworm - Mi Huang; Zhen Shen; Yong-Ming Chen; Talha Tariq; Liang-De Tang; Qing-Rong Bai; Jian Wei; Kelvin Kamfwa; Nicolas Desneux; Lian-Sheng Zang (Crop Protection, 2026)

Interleukin-12 as an adjuvant enhances Th1-biased immune response in DNA vaccine against Edwardsiella tarda in flounder (Paralichthys olivaceus) - Xiaoyan Wu; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2026)

Exosomal miR-4171-x contributes to T helper II cell immune response by regulating the Gata-3 expression in flounder (Paralichthys olivaceus) - Xueyan Shi; Lixia Jiang; Heng Chi; Roy Ambli Dalmo; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan (Aquaculture, 2026)

Euphebranes A−G: higher diterpenoids from the radix of Euphorbia ebracteolata - Shu-Qi Wu; Lei-Ming Wu; Jia-Qian Chen; Fang-Yu Yuan; Dong Huang; Jia-Luo Huang; Yun-Yun Chen; Tao Yuan; Xin Chen; Zhang-Hua Sun; Gui-Hua Tang; Sheng Yin (Phytochemistry, 2026)

Degassing from Chang’e-6 ilmenite surfaces revealed by a foamy texture: insights for volatile cycles on the Moon - Tian Zhang; Hong Tang; Xiongyao Li; Bing Mo; Yuanyun Wen; Sheng Zhang; Wen Yu; Chuanjiao Zhou; Haiyan Long; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

miR-197-y and novel-m0012–5p modulate Th cell differentiation via STAT4/STAT6 in flounder (Paralichthys olivaceus) - Miao Ye; Xueyan Shi; Heng Chi; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan (Fish & Shellfish Immunology, 2026)

Inhibitory effects of isobavachalcone against Tetrahymena thermophila: Mechanistic insights - Hongming Tang; Juan Liu; Dong Sheng; Xu Ren; Qinghua Yu; Zhixin Guo; Yunpeng Wu; Yuxiao Liu; Yuehan Xiao; Wei Wang; Shigen Ye; Weijia Zhou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

The enrichment and metabolic adaptation of autotrophic denitrifiers in pyrite-induced biofilms enhances TN removal and reduces carbon demand in A2/O systems - Huize Guan; Caiyan Qu; Jingyu Liu; Sheng Hu; Xi Tang; Di Wu; Chong-Jian Tang (Chemical Engineering Journal, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Association of PM2.5, O3 and greenness exposure with risk of cardiometabolic multimorbidity: a prospective cohort study - Ning Gao; Dan Sheng; Shaoyan Tang; Minzhen Wang; Shan Zheng (International Journal of Biometeorology, 2026)

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

Regulation of straw-derived nitrogen dynamics by its quality: Implications for N2O mitigation - Xiu Liu; Congyue Tou; Sheng Tang; Ji Chen; Wolfgang Wanek; David R. Chadwick; Davey L. Jones; Yongchao Liang; Lianghuan Wu; Qingxu Ma (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Co-pyrolysis of polyvinyl chloride and waste rubber: Interaction mechanism during staged pyrolysis - Yue Sheng; Longfei Tang; Chang Zhang; Weitong Pan; Lu Ding; Xueli Chen; Fuchen Wang (Journal of Environmental Chemical Engineering, 2025)

Multifunctional superhydrophobic PDMS@COF@MS sponges for ion removal from waste oils during oil/water separation - Yingying Wang; Taipeng Jiang; Weijie Wei; Lingling Zeng; Jingjing He; Sheng Chen; Jianyong Tang; Zhuwei Gao (Journal of Environmental Chemical Engineering, 2025)

Natural adsorbents for sample pretreatment: Mechanism insights, greenness assessment and practical applications - Qing Wang; Chun-Yu Zhang; Shao-Feng Tang; Chang-Jiang-Sheng Lai (Journal of Environmental Chemical Engineering, 2025)

Chemo-biostratigraphy of the Dzabkhan Craton: Refining the Ediacaran-Cambrian Transition in Southwestern Mongolia - Xiao Tang; Da Li; Simon V. Hohl; Michael Steiner; Ben Yang; Yi-Sheng Yin; Zhong-Lai Zhou; Qiao Li; Min Wu (Global and Planetary Change, 2025)

A peptidomics-based investigation of the synergistic effects of neutral and Alcalase proteases on release of antioxidant peptides from soybean protein isolates - Shulong Cai; Liqi Fan; Dan Liu; Changxing Wei; Na Yang; Xichao Fu; Rong Tang; Jucai Xu; Sheng Yin; Xin Chen (Food Chemistry, 2025)

Construction of hierarchically porous α-Fe2O3 nanosheets from Fe-PVP hybrid gel for sustainable Fenton-like degradation of tetracycline antibiotics with low H2O2 consumption - Mengru Shi; Weijiang Tang; Sheng Guo; Fengxi Chen (Environmental Research, 2025)

CircNOX4 promotes proliferation and resistance by regulating the hsa-miR-6884-5p/YWHAG Axis and ERK signaling pathway in cholangiocarcinoma - Zhangdi Yan; Lixin Du; Yingdi Han; Kangshuai Li; Guoli Sheng; Xudong Wang; Yunjia Liu; Yuankun Zhang; Jian Deng; Zengli Liu; Yunfei Xu; Zongli Zhang; et al. (Functional & Integrative Genomics, 2025)

Crop rotation mitigates soil fungal diversity loss under warming or increased moisture - Zhibo Zhou; Keming Yang; David Tissue; Zhong Wei; Le Li; Zhe Tang; Lukuan Fu; Hanqin Li; Tingting Sheng; Hongwei Liu; Yingjun Zhang; Fengge Zhang (Agriculture, Ecosystems & Environment, 2025)

New aromatic butenolides from the plant endophytic fungus Malbranchea umbrina D16 - Xian-An Chen; Han-Zhuang Weng; Lei-Ming Wu; Shu-Qi Wu; Rong Pu; Tao Yuan; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Field synergy enhancement of fluid flow and heat transfer in intensive tobacco roasting room - Sheng Tang; Jun Zhong; Ming Li; Yonglei Jiang; Ying Zhang; Jianhuan Deng; Chen Deng; Zhihan Deng; Muchi Yao (Computers and Electronics in Agriculture, 2025)

Evaluation of efficacy of intensity measures for fast and reliable seismic fragility analysis of bridge columns - Jian-Cheng Dai; Dong-Sheng Wang; Xiao-Yu Chen; Wei-Jian Tang; Rui Zhang; Ying-Xin Hui (Soil Dynamics and Earthquake Engineering, 2025)

Opposite roles of plant quality and soil exoenzymes in regulation of litter carbon transfer to fungal and bacterial necromass - Xiu Liu; Sheng Tang; Congyue Tou; Ji Chen; Wolfgang Wanek; Yakov Kuzyakov; David R. Chadwick; Davey L. Jones; Lianghuan Wu; Qingxu Ma (Soil Biology and Biochemistry, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Hierarchically porous UiO-67-bpy metal–organic gels for efficient tetracycline removal - Song He; Junqing Zhu; Hongliang Sheng; Jiayi Tang; Tao He; Jinfeng Ji; Yajun Huang (Environmental Research, 2025)

Spatial heterogeneity of soil Cd and Pb driven by combined effects of pedogenesis and anthropogenic activities: A case study in the mountainous and hilly region of Fujian Province, China - Weikang Sheng; Qingye Hou; Zhongfang Yang; Tao Yu; Long Zhan; Ming Zhang; Mo Zhou; Guoguang Chen; Zhimin Tang; Ying Wang (Environmental Research, 2025)

Field monitoring of soil-atmospheric interactions in cracked soils: Coupled thermal and hydrological responses to crack development - Chang Sun; Chao-Sheng Tang; Farshid Vahedifard; Qing Cheng; Annan Zhou; Bin Shi (Engineering Geology, 2025)

Field monitoring of soil-atmospheric interactions in cracked soils: Design and deployment of a multi-sensor in-situ system for energy and matter exchange - Chang Sun; Chao-Sheng Tang; Farshid Vahedifard; Ao Dong; Ben-Gang Tian; Zhan-Ming Yang; Bin Shi (Engineering Geology, 2025)

Geophysical evidence of progressive Noachian crustal thickening on Mars revealed by meteorite impacts - Weijia Sun; Hrvoje Tkalčić; Marco G. Malusà; Ludmila Adam; Qingya Tang; Sheng Wang; Zhi Wei; Yongxin Pan (Earth and Planetary Science Letters, 2025)

Universal ionic wind tweezer for non-contact, phase-inclusive micromanipulation - Qiang Tang; Chengcheng Song; Manfei Liu; Xiaxia Cui; Junjie Zhang; Zetao Wang; Sheng Zhang (Chemical Engineering Journal, 2025)

A dual-signal hydrogel sensor advances prosthesis manipulation towards precision motion control - Xinlei Shi; Zhao Zhang; Xin Liu; Runrun Zhang; Yangyang Pei; Sheng Ding; Xingchen Zhou; Xiancheng Song; Ziqing Tang; Gengzhi Sun; Qiang Chen (Chemical Engineering Journal, 2025)

Multifunctional textiles with bimetallic MOFs for enhanced ammonia uptake and protective applications - Yajie Shu; Zimeng Sheng; Danni Wang; Hao Gu; Yumeng Tang; Guangsheng Zhu; Man Zhang; Jinfeng Wang; Jinming Zhang; Haibao Huang (Chemical Engineering Journal, 2025)

From Cynomorium songaricum residues to supercapacitors: A novel utilization strategy for biomass solid waste - Juan Li; Xiaohui Wang; Jing Tang; Shun Wang; Shouri Sheng (Biomass and Bioenergy, 2025)

4-Hydroxychalcone alleviated Angiotensin II-induced atrial fibrillation via immunoproteasome-IKK-NF-κB signaling pathway modulation - Yun-Long Zhang; Ze-Yan Xu; Yan Sun; Qian-Qiu Zhu; Sheng-Xing Tang; Qing-Hua Zhong; Xiao Han (Journal of Molecular Medicine, 2025)

Integrative histological and transcriptomic profiling of the hepatopancreas and ovary reveals key regulators of ovarian redevelopment in the giant freshwater prawn Macrobrachium rosenbergii - Tianci Kong; Peizi Zheng; Shanhua Xu; Xinyi Yao; Qiang Sheng; Shaokui Yi; Zhenglong Xia; Guoliang Yang; Qiongying Tang (Aquaculture International, 2025)

Corrigendum to: “Substitution of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China” [J Hazard Mater 465 (2024) 1–14 133118] - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Synergistic neurotoxicity of polystyrene nanoparticles and MEHP in zebrafish (Danio rerio) - Yiyun Liu; Qi-Ping Tang; Si-Jia Zuo; Yuan Ding; Feng-Yi Guo; Bao-Fu Zhang; Qin-Hong Zhou; Dongmei Xie; De-Sheng Pei (Environmental Pollution, 2025)

Impact of dynamic desiccation cracks on hydrological processes and stability in expansive clay slopes: A coupled dual-permeability modeling approach - Yi Luo; Jiaming Zhang; Chao-Sheng Tang; Guosheng Jiang; Thom Bogaard (Engineering Geology, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

3D reconstruction and characterization of soil desiccation cracks using smartphone photogrammetry method - Ao Dong; Chao-Sheng Tang; Cheng Zhu; Jin-Jian Xu; Chang Sun; Kun Fang; Qing Cheng; Bin Shi (Computers and Geotechnics, 2025)

Effect of ibuprofen on the behavior, histopathology, antioxidant system, DNA damage, and apoptosis of Asian freshwater clams (Corbicula fluminea) - Yun-xia Hou; Xiang-sheng Hong; Shi-yin Tang; Wang Liu; Zhi-tong Li; Juan Wang; Sai-hong Yan; Jian-hui Qin; Jin-miao Zha (Aquatic Toxicology, 2025)

High-Resolution Prediction of Thin-Layer Reservoirs Based on Seismic Sedimentology: A Case Study of the Penglaizhen Formation, Western Sichuan Basin, China - Gang Lu; Changcheng Wang; Xiaobing Zhang; Xihe Lu; Ruochen Tang; Sheng Zhang; Zheng Wang (Natural Resources Research, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Drought exacerbates levofloxacin phytotoxicity: Insights from Phragmites australis - Yuhang Zong; Sheng Sheng; Yin Liu; Bianhe Lu; Jing Hu; Junwei Shen; Musheng Ji; Sijing Tang; Jin Qian (Journal of Hazardous Materials, 2025)

Dithiothreitol oxidative potential (OP) of PM2.5 in Beijing: Quantitative contribution of metals to OP and its prediction based on machine learning models - Yusheng Ma; Mengshuang Sheng; Jing Shang; Rui Tang; Jiong Cao; Yuhan Liu; Chenyu Liang; Yu Kuang; Yan Zheng; Zhen Cheng; Rico K.Y. Cheung; Robin L. Modini; et al. (Journal of Hazardous Materials, 2025)

Neurocognitive impairments induced by cyclopiazonic acid exposure in mice: Effects on learning and memory - Caihong Huang; Yongli Ye; Jian Ji; Peipei Li; Jia-Sheng Wang; Lili Tang; Yahui Gao; Xiulan Sun (Journal of Hazardous Materials, 2025)

Growth inhibition and activity stimulation of non-target organism nitrogen-fixing bacterium Azotobacter vinelandii by herbicide florasulam - Hua Chen; Hongtao Wang; Jinwei Yang; Yue Yuan; Wei Tang; Xian Wu; Qinmei Zhong; Sheng-Tao Yang (Journal of Hazardous Materials, 2025)

Membrane-enhanced methanogenesis efficiency and biomass retention in EGSB-AnMBR for food waste press filtrate treatment - Haojie Qin; Jianmin Liu; Wendong Chao; Jianyong Liu; Sheng Chang; Chang-Tang Chang; Tiago Martins; Yu-You Li; Hui Cheng (Environmental Research, 2025)

Using black soldier fly larval frass to restore soil health - Shuo-Yun Jiang; Ke-Wei Shen; María Gómez Brandón; Sheng-Biao Lu; Jeffery K. Tomberlin; Xiao-Tian Tang; Hang Wang; Fang-Ming Xiang; Xue-Xin Chen; Zhi-Jian Zhang (Bioresource Technology, 2025)

Anti-neuroinflammatory effects of epivernodalol, a sesquiterpene from Vernonia anthelmintica (L.) Willd., in lipopolysaccharide-stimulated murine microglial cells - Shengnan Ma; Yue Wang; Sheng-An Tang (Journal of Natural Medicines, 2025)

Ionospheric TEC disturbances and Ne anomalies during the Mw 7.8 Alaska earthquake on July 22, 2020 - Yuhan Gao; Jun Tang; Sheng Wang; Wei Zhang; Chaoqian Xu; Liang Zhang (Advances in Space Research, 2025)

Long-term manure and mineral fertilisation drive distinct pathways of soil organic nitrogen decomposition: Insights from a 180-year-old study - Wankun Pan; Sheng Tang; Jingjie Zhou; Wolfgang Wanek; Andrew S. Gregory; Tida Ge; Karina A. Marsden; David R. Chadwick; Yongchao Liang; Lianghuan Wu; Qingxu Ma; Davey L. Jones (Soil Biology and Biochemistry, 2025)

Bioactive terpenoids and sterols from the fruiting bodies of Fomitopsis pinicola - Huan Yu; Qian Chen; Tian-Chi Xu; Yue Wang; Wen-Feng Xu; Min Li; Xu Zhang; Chuan Zhao; Dong-Li Zhang; Peng-Fei Jin; Shao-Yong Li; Sheng-An Tang (Phytochemistry, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Metal-organic frameworks (MOF-74) show distinct bio-effects to nitrogen-fixing bacterium Azotobacter vinelandii - Fangshi Liu; Hongtao Wang; Ziqi Tang; Hua Chen; Yue Yuan; Qinmei Zhong; Xian Wu; Sheng-Tao Yang (Journal of Hazardous Materials, 2025)

Occurrence, temporal, and spatial variation of PPCPs and EDCs in typical drinking water sources and tap water in southern China - Nan Gai; Ge Feng; Huilun Chen; Guohui Lu; Haitao Piao; Qifeng Tang; Sheng Chang; Jiuchen Liu (Journal of Environmental Chemical Engineering, 2025)

Multi-model immunochromatographic assay based on “three in one” Fe3O4@PDA@Pt nanocomposite for ultrasensitive detection of zearalenone in cereals - Wei Sheng; Xinshuang Tang; Tingting Ya; Qiuyue Ji; Zixin Jin; Lishuai Ren; Ziwuzhen Wang; Shuo Wang; Caixu Fan; Yamin Liu (Food Chemistry, 2025)

Machine learning-based investigation on the relation between the design parameters and impact behaviour of SSC structures - Ruo-Yang Tang; Ran Ding; Jian-Sheng Fan (Engineering Structures, 2025)

Moxibustion pre-treatment attenuates seizure severity during status epilepticus and counteracts the proconvulsant function of the purinergic P2X7 receptor - Hong-Wei Zhang; Jia-Jia Li; Yulihan Tang; Mao-Lin Tian; Sheng Huang; Meng-Juan Sun (Purinergic Signalling, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Chemical constituents of Penicillium ferraniaense GE-7 and their cytotoxicities - Yan Wang; Shao-Hua Song; Lei-Ming Wu; Xue Zhou; Qing-Ren Lu; Ai-Ping Yin; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Comparative study on the alleviating effect of neohesperidin dihydrochalcones and its synthetic precursor neohesperidin on ovalbumin-induced food allergy - Xin Liu; Chen Wang; Sheng Tang; Ge Wang; Yaoxin Huang; Feiyang Yang; Xiang Tan; Junying Bai; Linhua Huang (Food Research International, 2025)

The potentials of uncertainty analysis and Bayesian optimization in HONO source modeling diagnosis and improvement - Jinlong Zhang; Wending Wang; Keyu Zhu; Zhijiong Huang; Li Sheng; Songdi Liao; Xin Yuan; Yanan Hu; Jiangping Liu; Mengxue Tang; Xiaofeng Huang; Jie Li; et al. (Environmental Research, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Experimental and numerical study on the evolution of cellulose char granules with different degree of densification - Chang Zhang; Zichao Hu; Yi Ma; Yue Sheng; Weitong Pan; Longfei Tang; Xueli Chen; Lu Ding; Fuchen Wang (Journal of Environmental Chemical Engineering, 2025)

Temperature-controllable antibacterial film mediated by a photoresponsive metal-polyphenol framework for long-term food preservation - Guangyang Jiang; Wenyang Sheng; Li Yang; Yichen Yang; Tingting Tang; Chenzhi Wang; Yongqiang Tian (Food Control, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Generating and predicting soil desiccation cracking patterns utilizing a stochastic model based on geometric parameters - Zhan-Ming Yang; Chao-Sheng Tang; Tao Wang; Qing Cheng; Jun-Dong Liu; Zhi-Xiong Zeng; Zhengtao Shen (Engineering Geology, 2025)

CRISPR/Cas9-mediated mutations of GS3 and GW5 positively regulate grain size and grain width in rice (Oryza sativa indica) - Aqib Zeb; Amir Sohail; Shengjia Tang; Zhonghua Sheng; Peisong Hu (Ecological Genetics and Genomics, 2025)

Iron-modified biochar enhanced nitrogen retention during composting:bridging chemisorption and microbiome modulation - Ruolan Tang; Sheng Yao; Yan Liu; Tianyu Ren; Jingyuan Ma; Xiaoyan Gong; Guoxue Li; Ruonan Ma; Jing Yuan (Chemical Engineering Journal, 2025)

East Asian dust storm in March 2021: Perspective views from ground observation, satellite measurement and numerical simulation - Yi-Bo Xue; Xiao-Xiao Zhang; Jia-Qiang Lei; Sheng-Yu Li; Lian-You Liu; Zi-Fa Wang; Wen-Jun Tian; Xiao Tang; Xue-Shun Chen (Atmospheric Environment, 2025)

Development of regional soil desiccation cracking susceptibility assessment model using GIS-based fuzzy comprehensive evaluation - Ting Wang; Chao-Sheng Tang; Zhi-Xiong Zeng; Ben-Gang Tian; Jin-Jian Xu; Qing Cheng; Zheng-Tao Shen; Xiao-Hua Pan (Bulletin of Engineering Geology and the Environment, 2025)

Objective Nowcasting of Severe Convective Weather: Technological Progress and Outlook - Kanghui Zhou; Yongguang Zheng; Bo Yang; Jie Sheng; Xiaowen Zhang; Fuyou Tian; Wenyuan Tang (Journal of Meteorological Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Mapping risks: A value chain approach to brucellosis introduction in Zhijiang's Cattle Population, China - Zihan Tian; Sheng Jiang; Peng Yuan; Xiaozhong Wang; Jie Pei; Hao Tang; Shubo Li; Ian D. Robertson; Aizhen Guo; Yingyu Chen (Preventive Veterinary Medicine, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Designed amino acid-based deep eutectic solvents as a platform to functionalize biomedical elastomers by polyaddition reactions - Ao Zhen; Ao Wang; Xirui Long; Xiao Wang; Nan Sheng; Qing Tang; Jiehua Li; Hong Tan; Feng Luo; Zhen Li (Chemical Engineering Journal, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Characterization of CD4–2+ cell subsets and their responses in pearl gentian grouper (Epinephelus fuscoguttatus × E. lanceolatus) - Xiaoyu Jiang; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2025)

Direct synthesis of millimeter-sized hexagonal diamond from graphite - Xiaohong Yuan; Guwen Chen; Yong Cheng; Shengcai Zhu; Fuyang Liu; Yujiao Ke; Kuo Hu; Yue Pan; Ming-Sheng Wang; Zhaodong Liu; Hu Tang; Bingbing Liu (Science Bulletin, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Polarity and fluorescent fractions of manure dissolved organic matter could affect differently the adsorption and desorption of antibiotics in soils - Jin-Sheng Hu; Hui-Yun Xiao; Xiang-Yu Tang; Hao Yan; Zhuo Chen; Jian-Hua Cheng; Xiao-Yu Li (Journal of Environmental Management, 2025)

Environmentally friendly bacterial cellulose hydrogel-derived aerogel and membrane for efficient water purification - Yan Guo; Min Li; Tang Zhou; Qidi Wu; Chao Liu; Sheng Li; Quan Feng; Haihua Wang; Zhenyu Li (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Further investigation of CO2 energization fracturing in shale reservoir- from microscopic mechanism to field application - Weiyu Tang; Fujian Zhou; Jamse J. Sheng; Xiukun Wang; Tingxue Jiang (Fuel, 2025)

Temperature-sensitive driving assembled fluorescence hydrogel based dual-mode sensor for adsorbing and detecting of heavy metal cadmium ions in food and water - Ziwuzhen Wang; Wei Sheng; Xinshuang Tang; Tingting Ya; Zixin Jin; Shuo Wang; Qiuyue Ji; Caixu Fan; Yamin Liu (Food Chemistry, 2025)

Ballistic impact tests and penetration simulations on the single steel-plate UHPC composite structures considering various local structural forms - Ruo-Yang Tang; Ran Ding; Yun-Lun Sun; Jian-Sheng Fan; Jian-Guo Nie (Engineering Structures, 2025)

Seasonal dynamics of root growth and desiccation cracks and their effects on soil hydraulic conductivity - Yuliana Yuliana; Arwan Apriyono; Viroon Kamchoom; David Boldrin; Qing Cheng; Chao-Sheng Tang (Engineering Geology, 2025)

Understanding the biological identity of metal-organic framework through profiling proteomic fingerprinting of protein corona - Huan Tang; Jie Zhou; Tong Yang; Hai-Ning Lyu; Zheng Chu; Ying Zhang; Ang Ma; Junzhe Zhang; Yuqing Meng; Chong Qiu; Sheng-Tao Yang; Jigang Wang; et al. (Chemical Engineering Journal, 2025)

Effect of elements availability on the decomposition and utilization of S-containing amino acids by microorganisms in soil and soil solutions - Qingxu Ma; Ruiqi Yao; Xiu Liu; Sheng Tang; Wankun Pan; Jingjie Zhou; Lianghuan Wu; Davey L. Jones (Plant and Soil, 2025)

The Effect of Cuproptosis-Related Proteins on Macrophage Polarization in Mesothelioma is Revealed by scRNA-seq - Jia-Xin Xu; Li-Jing Ma; Li-Ying Tu; Qi-Sheng Tang; Bian Wu; Li-Hong Jiang (Biological Trace Element Research, 2025)

Compressive stress induced by desiccation shrinkage in clayey soils - Hao Zeng; Chao-Sheng Tang; Yu-Jun Cui; Abdallah Najdi (Applied Clay Science, 2025)

Efficient conversion and highly sensitive detection of PAEs in milk based on hydrazinolysis reaction and hydrogen bonding using SERS technique - Lili Hua; Hongmei Li; Jing-Wen Zhou; Xiao-Feng Liu; Xian-Ming Guo; Zhao-Bing Zhang; Yichuan Kou; Tang-Tang Xie; Cuihong Sheng; Lin Zhang; Sheng-Hong Liu; Fan-Li Zhang; et al. (Analytica Chimica Acta, 2025)

17α-methyltestosterone exposure disrupted growth, liver physiology and intestinal microbial on fish: A case study on migratory bony fishes (Takifugu fasciatus) - Yuxi Liu; Sijin Wang; Mengbo Han; Sheng Luo; Peng Chu; Xiaodong Tang; Cheng Zhao; Shiqun Han; Shaowu Yin; Tao Wang (Marine Pollution Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Two new analytical models for heat transport in ground-coupled heat pump system with heat loss at ground surface: A new meshless treatment of ground heat exchanger for reflecting heat capacity effect - Chenyang Tang; Hund-Der Yeh; Ching-Sheng Huang (Geothermics, 2025)

G-CSF modulates innate and adaptive immunity via the ligand-receptor pathway of binding GCSFR in flounder (Paralichthys olivaceus) - Panqiu Geng; Xianghu Meng; Xiaokai Hao; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan; Roy Ambli Dalmo; Heng Chi (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Diapause in parasitoids: a systematic review - Zhen Shen; Liang-De Tang; Nicolas Desneux; Lian-Sheng Zang (Journal of Pest Science, 2025)

Spatiotemporal evolution of PM2.5 and its components and drivers in China, 2000–2023: effects of air pollution prevention and control actions in China - Yindi Peng; Yamin Zhao; Ning Gao; Dan Sheng; Shaoyan Tang; Shan Zheng; Minzhen Wang (Environmental Geochemistry and Health, 2025)

Deep eutectic solvent-based ionogel: Innovative potential as a promising chromatographic separation material - Zexin Huang; Qiaoling Liu; Ziyi Ke; Tiantian Si; Yuefei Zhang; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2025)

Von Willebrand Factor in Weibel–Palade Bodies of Endothelial Cells Involved in the Immune Response to Hirame Novirhabdovirus Infection in a Teleost Paralichthys olivaceus - Qiujie Gan; Heng Chi; Xianghu Meng; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan (Journal of Fish Diseases, 2025)
von Willebrand factor (vWF) is a large multimeric sialoglycoprotein that plays key roles in normal haemostasis, inflammation regulation, angiogenesis and cancer metastasis in mammals. The gene, protein sequences and functions of vWF in flounder Paralichthys olivaceus ( Po vWF) were analysed in this study. Po vWF possesses an 8550‐bp open reading frame (ORF) that encodes a 2849 amino acid protein. Po vWF mRNA is highly expressed in the heart and gill, followed by the intestine, skin, spleen, kidney, muscle and liver. Po vWF positive cells are mainly endothelial cells (ECs), predominantly located along the inner lining of blood vessels, enclosing the bloodstream. After being infected with hirame novirhabdovirus (HIRRV), flounder exhibits a dark body colour, congested fins and visceral membranes. Histopathologic analysis revealed that the ECs of diseased fish had compromised integrity, accompanied by a significant increase in number of cells within blood vessels. Immunofluorescence and ultrastructural studies showed that virions infect ECs can induce morphological and functional alterations, which lead to the release of vWF and facilitate the migration of neutrophils into tissues to exert antiviral functions. This research pinpoints the role of vWF in the immune response to HIRRV infection in teleost. It offers an in‐depth and all‐encompassing understanding of the pathophysiological interaction between HIRRV and endothelial cells during invasive infections in fish.

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Gasification-MILD combustion technology with ash-sludge recirculation for reducing multi-phase net dioxin discharges from a waste incineration - Sheng-Lun Lin; Wei Tang; Chun-Yun Hsiao; Jhong-Lin Wu; Yee-Lin Wu; Chien-Er Huang; Atsushi Matsuki; Ayano Matsumoto; Mengjie Song (Waste Management, 2025)

Chloroplast-localized transporter OsNTP1 mediates cadmium transport from root to shoot and sugar metabolism in rice - Jingxin Wang; Lingwei Yang; Bo Xu; Ruijie Cao; Sidra Charagh; Suozhen Hui; Liang Zhou; Yuanyuan Zhang; Yujuan Chen; Zhonghua Sheng; Guiai Jiao; Gaoneng Shao; et al. (Journal of Hazardous Materials, 2025)

In situ images of Cd2+ in rice reveal Cd2+ protective mechanism using DNAzyme fluorescent probe - Jin Chen; Jiafeng Pan; Meijuan Duan; Fan Fan; Jianbing Liu; Wenjie Hu; Dong Yu; Zhizhong Sun; Xiabing Sheng; Yanning Tan; Yongjun Tan; Xuewu Sun; et al. (Journal of Hazardous Materials, 2025)

Effect of cadmium and fumonisin B1 co-exposure on mitochondrial dysfunction and ferroptosis pathway in Caenorhabditis elegans - Yating Wang; Yongli Ye; Jian Ji; Jia-Sheng Wang; Lili Tang; Lanlan Zhang; Yufeng Li; Jiadi Sun; Lina Sheng; Xiulan Sun (Journal of Hazardous Materials, 2025)

Optimizing nitrogen fertilization rate to achieve high yield and high soil quality in paddy ecosystems with straw incorporation - Jingjie Zhou; Wankun Pan; Sheng Tang; Qingxu Ma; Wenhai Mi; Lianghuan Wu; Xiu Liu (Journal of Environmental Management, 2025)

Homogeneous fluorescence immunoassay based on AuNPs (AgNPs) quenching multicolor QDs@hydrogel beads for the simultaneous ultra-sensitive determination of aflatoxin B1 and capsaicinoids in food - Zixin Jin; Wei Sheng; Ziwuzhen Wang; Xinshuang Tang; Tingting Ya; Shuo Wang; Qiuyue Ji; Caixu Fan; Yamin Liu (Food Chemistry, 2025)

DNA template triggered copper nanoparticles generation coupled with hybridization chain reaction amplification for simultaneous detection of three mycotoxins in food samples - Jiahe Ju; Jingyu Kuang; Jiale Qian; Yitong Chen; Dezhao Kong; Chang Liu; Wei Shen; Haiwei Shi; Sheng Tang (Food Control, 2025)

Optimized near infrared reflectance model based on preprocessing selection strategy for rapid analysis of 2-acetyl-1-pyrroline content in rice flour - Li-Hong Xie; Shao-Qing Tang; Gao-Neng Shao; Zhong-Hua Sheng; Shi-Kai Hu; Xiang-Jin Wei; Gui-Ai Jiao; Ling Wang; Pei-Song Hu (Food Control, 2025)

A first arrival picking method of microseismic signals based on semi-supervised learning using FreeMatch and MS-Picking - Guanqun Sheng; Zhuka Zhang; Xingong Tang; Kai Xie (Computers & Geosciences, 2025)

Efficiently radiation-induced degradation and extraction of Polygonatum sibiricum polysaccharides and its excellent ROS scavenging properties - Dong-Xu Tang; Shi-Zhong Zhou; Zhi-Jun Wang; Yang-Lin Zhang; Kun Liu; Jin-Yu Yang; Xiao-Jie Yang; Yue-Sheng Li; Xia Zhang (Chemical Engineering Journal, 2025)

Characteristics and Prediction of Reservoir Water Quality under the Rainfall-Runoff Impact by Long Short-Term Memory Based Encoder-Decoder Model - Xiaodan Sheng; Yulan Tang; Shupeng Yue; Xu Yang; Yating He (Water Resources Management, 2025)

Sealing Integrity Evaluation and Optimization of Cement Sheath-Formation Interface under Different Formation Conditions during Fracturing - Donghua Su; Sheng Huang; Zaoyuan Li; Jin Li; Ziyu Wang; Shizhong Tang; Hua Wu; Bo Zhao (Journal of Earth Science, 2025)

Iron oxides promote physicochemical stabilization of carbon despite enhancing microbial activity in the rice rhizosphere - Han Sun; Xiaomin Ma; Lukas Van Zwieten; Yu Luo; Robert W. Brown; Georg Guggenberger; Sheng Tang; Yakov Kuzyakov; Peduruhewa H. Jeewani (Science of The Total Environment, 2025)

Insights to the roles of nitrogen-doped biochar in anaerobic digestion - Zhang-Wei He; Sheng-Jie Sun; Ai-Hua Li; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhi-Hua Li; Ai-Jie Wang; Wen-Zong Liu (Process Safety and Environmental Protection, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Release of microplastics from pipe materials and their impact on stagnant water - Keshu Sheng; Ziyi Yang; Yulin Tang; Yongji Zhang (Journal of Water Process Engineering, 2025)

Hawthorn proanthocyanidins extract inhibit intestinal fatty acid uptake through PPARα-FABP1/LXRα pathway: In vitro and in vivo studies - Yuemeng Zhang; Lijun Song; Tianxu Chu; Liangfu Zhou; Xia Tang; Qinghai Sheng; Wen Zhao; Yasai Sun (Food Bioscience, 2025)

Corrigendum to “Soybean glycinin impaired immune function and caused inflammation associated with PKC-ζ/NF-κb and mTORC1 signaling in the intestine of juvenile grass carp (Ctenopharyngodon idella)” [Fish and Shellfish Immunol. 106 (2020) 393–403] - Ya-Lin Zhang; Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2025)

Mitigating rainfall induced soil erosion through bio-approach: From laboratory test to field trail - Bo Liu; Chao-Sheng Tang; Xiao-Hua Pan; Qing Cheng; Jin-Jian Xu; Chao Lv (Engineering Geology, 2025)

Elucidating synergistic effects during co-pyrolysis of plastics and paper in municipal solid waste: Thermal behavior and product characteristics - Zichao Hu; Longfei Tang; Peipei Gao; Bin Wang; Chang Zhang; Yue Sheng; Weitong Pan; Lu Ding; Xueli Chen; Fuchen Wang (Bioresource Technology, 2025)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: Improving Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Dian-Long Wang; Rui Wang; Bin Shi (Rock Mechanics and Rock Engineering, 2025)

Intrathecal Fumagillin Alleviates Chronic Neuropathy-Induced Nociceptive Sensitization and Modulates Spinal Astrocyte-Neuronal Glycolytic and Angiogenic Proteins - Zhi-Hong Wen; Zong-Sheng Wu; Hao-Jung Cheng; Shi-Ying Huang; Shih-Hsuan Tang; Wei-Nung Teng; Fu-Wei Su; Nan-Fu Chen; Chun-Sung Sung (Molecular Neurobiology, 2025)

Parameter-normalized probabilistic seismic demand model considering the structural design strength for structural response assessment - Jian-Cheng Dai; Dong-Sheng Wang; Wei-Jian Tang; Yu-He Zou; Ying-Xin Hui; Ya-Jun Zhang (Soil Dynamics and Earthquake Engineering, 2024)

A comprehensive evaluation of the optimum amount of phosphate fertilizer for drip irrigation of cotton under mulch based on root morphology, physiology, and mycorrhizal symbiosis - Bolang Chen; Zupeng Ye; Xuexia Tang; Zhongping Chai; Yue Ma; Jiandong Sheng; Gu Feng (Soil and Tillage Research, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Inheritance and ecological effects of exogenous genes from transgenic Brassica napus to Brassica juncea hybrids - Xinyu Wang; Zhilu Sheng; Hai Huang; Zhixi Tang; Wei Wei; Charles Neal Stewart; Yongbo Liu (Plant Science, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Selective recovery of Au from waste printed circuit board by water-soluble organic leaching: The key role of in situ bromine mediation and identificationof pathway - Zhenfeng Xiong; Ying Huang; Yonghua Li; Changdong Sheng; Liwei Sun; Jing Ma; Baoyan Chi; Jiali Tan; Xiong Tang; Rong Zha; Xinhua Zhan (Journal of Hazardous Materials, 2024)

Polystyrene nanoplastics enhance thrombosis through adsorption of plasma proteins - Chao Sheng; Guozhen Wang; Zijia Liu; Yuchen Zheng; Zijie Zhao; Duo Tang; Wenzhuo Li; Ao Li; Qi Zong; Renhang Zhou; Xiaonan Hou; Mengfei Yao; et al. (Journal of Hazardous Materials, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Effects of chronic ethanol exposure on citrinin metabolism and gut-liver-kidney-brain related injuries in mice - Yida Xu; Yongli Ye; Jia-Sheng Wang; Lili Tang; Xiao Ning; Xiulan Sun (Food Bioscience, 2024)

Parathyroid hormone mediates the adverse impact of air pollution exposure on serum 25-hydroxyvitamin D: A nationwide cross-sectional study in China - Haitao Zhang; Jing Wang; Xia Meng; Bing Shu; Chunchun Yuan; Xingwen Xie; Zhangyu Liao; Xiaobing Jiang; Bolai Chen; Xinchao Lin; Xu Wei; Xiangyang Leng; et al. (Environmental Research, 2024)

The impact of early life exposure to individual and combined PFAS on learning, memory, and bioaccumulation in C. elegans - Seth D. Currie; Yuqing Ji; Qingguo Huang; Jia-Sheng Wang; Lili Tang (Environmental Pollution, 2024)

Finite element analysis of single steel-plate concrete composite containment of nuclear power plant under commercial aircraft impact - Ruo-Yang Tang; Yun-Lun Sun; You-Gang Wang; Ran Ding; Jian-Sheng Fan; Jian-Guo Nie (Engineering Structures, 2024)

A comprehensive framework for characterizing and quantifying soil desiccation crack patterns: Quantitative parameters and development of CIAS - Chao-Sheng Tang; Ben-Gang Tian; Qing Cheng; Ting Leng; Bin Shi (Engineering Geology, 2024)

An efficient bio-stabilization technology with bio‑carbonation of reactive magnesia for soil improvement in cold regions - Rui Wang; Chao-Sheng Tang; Xiao-Hua Pan; Dian-Long Wang; Zhi-Hao Dong; Xiancai Lu (Engineering Geology, 2024)

Yolk-shell structured FeS0.5Se0.5@N-doped mesoporous carbon composite as high-performance lithium-ion battery anodes - Na Huang; Hehe Zhang; Guanjia Zhu; Cheng Tang; Zhongling Cheng; Aijun Du; Ming-Sheng Wang; Haijiao Zhang (Chemical Engineering Journal, 2024)

The senescent marker p16INK4a enhances macrophage foam cells formation - Wei Sheng Siew; Yin Quan Tang; Bey Hing Goh; Wei Hsum Yap (Molecular Biology Reports, 2024)

Current Status and Future Trends in Installation, Operation and Maintenance of Offshore Floating Wind Turbines - Mingfeng Hu; Jinkun Shi; Sheng Yang; Mingsheng Chen; Yichang Tang; Suqian Liu (Journal of Marine Science and Engineering, 2024)
The installation and operation phases are critical stages in the lifecycle of offshore wind turbines, with costs associated with the installation and maintenance of floating wind turbines accounting for approximately 50% of the total investment. This paper presents the latest advancements in the technologies for the installation and maintenance of floating wind turbines. First, it discusses the installation techniques and relevant research related to the foundations and components of floating wind turbines. Next, it explores various operational strategies for offshore wind turbines and studies on major component replacements. The interrelationship of research in the installation and maintenance fields for floating wind turbines is examined. Furthermore, this paper investigates various tools and equipment used for the installation and maintenance of offshore wind turbines. It also addresses the relevant regulations and standards governing offshore operations for floating wind turbines. Finally, this paper provides a forward-looking perspective on the installation and maintenance of floating wind turbines.

Improvements in source apportionment of multiple time-resolved PM2.5 inorganic and organic speciation measurements using constrained Positive Matrix Factorization - Chun-Sheng Huang; Yi-Hsien Liu; Ho-Tang Liao; Chia-Yang Chen; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

Unexpected antagonism of deoxynivalenol and enniatins in intestinal toxicity through the Ras/PI3K/AKT signaling pathway - Yongli Ye; Luyao Tang; Jia-Sheng Wang; Lili Tang; Xiao Ning; Jiadi Sun; Lina Sheng; Xiulan Sun (Toxicology, 2024)

Study of chlorine disinfection on the formation and resuscitation of Viable but nonculturable (VBNC) bacteria in drinking water distribution systems - Ruotong Xu; Xiuneng Zhu; Keshu Sheng; Yulin Tang; Yongji Zhang (Journal of Water Process Engineering, 2024)

Study of Cerchar abrasive parameters of monomineralic rocks and its application for evaluating cutting efficiency - Xin-Fang Li; Xiao-Ping Zhang; Shao-Hui Tang; Wei-Qiang Xie; Xin-Mei Yang; Quan-Sheng Liu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Immunoglobulin M-based local production in skin-associated lymphoid tissue of flounder (Paralichthys olivaceus) initiated by immersion with inactivated Edwardsiella tarda - Yuan Guo; Xiuzhen Sheng; Xiaoqian Tang; Jing Xing; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2024)

Insight into the initiation and propagation mechanism of desiccation cracking in clayey soil from DEM simulations - Tao Wang; Chao-Sheng Tang; Wei-Jie Liu; Qing Cheng; Zheng-Tao Shen; Xiao-Hua Pan (Computers and Geotechnics, 2024)

A semi-empirical parameter predicting the sensitivity of energetic materials from external pressure - Zhi-Xin Bai; Wei Zeng; Cheng-Lu Jiang; Fu-Sheng Liu; Zheng-Tang Liu; Qi-Jun Liu (Chemical Engineering Journal, 2024)

Periodic intense illumination in gas-solid phase photocatalysis: Efficient VOCs degradation at extremely low duty cycles - Zeyu Duan; Jianping Sheng; Qijun Tang; Xinru Chen; Ying Jia; Fan Dong; Haiqiang Wang; Zhongbiao Wu (Chemical Engineering Journal, 2024)

Phase-changing NIPAM-AM/ATO hydrogels for thermochromic smart windows with highly adaptive solar modulation - Yunxin Li; Meifeng Xu; Dongyang Wang; Zhiqiang Liu; Wei Mao; Jun Sun; Wei Shen; Hian Kee Lee; Sheng Tang (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Regulated charge transfer by cascade dual Z-scheme heterojunction of HCdS@ZnIn2S4-Cobalt porphyrin for efficient photocatalytic solar fuel production - Tengfei Bao; Chenxi Tang; Shuming Li; Ping She; Heng Rao; Jun-sheng Qin (Chemical Engineering Journal, 2024)

Deep eutectic solvent for high-performance aluminum-based hydrated eutectic electrolyte - Cheng Lu; Zhilong Wang; Bowen Tao; Ying Wang; Jiaping Sheng; Gen Tang; Yue Wang; Xiang Guo; Jinjin Li; Liangming Wei (Chemical Engineering Journal, 2024)

Study on the lower head failure in severe accidents Part II: Thermal-mechanical coupling behavior analysis on CAP1400 reactor lower head - Hao Yang; Pengcheng Gao; Bin Zhang; Sheng Cao; Jishen Li; Fan Miao; Shaowei Tang; Jianqiang Shan (Annals of Nuclear Energy, 2024)

Deep eutectic supramolecular polymers based HPLC stationary phase: Green synthesis strategy and promising application prospects - Qiaoling Liu; Wanjiao Wei; Yanjuan Liu; Yuefei Zhang; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

3D magnetic flower-spherical Fe2O3-NiO derived from NiFe-layered double hydroxides for the efficient removal of Bensulfuron methyl: Morphological control and bimetallic synergy - Lu Tang; Wei Chen; Jialing Sheng; Shuke Guo; Xiaoyu Wang; Hongmei Jiang (Science of The Total Environment, 2024)

Deciphering microbial metabolic interactions and their implications for community dynamics in acid mine drainage sediments - Shao-Ming Gao; Pandeng Wang; Qi Li; Wen-Sheng Shu; Ling-Yun Tang; Zhi-Liang Lin; Jin-Tian Li; Li-Nan Huang (Journal of Hazardous Materials, 2024)

Effect of interaction between different plastics and polyvinyl chloride on the chlorine transformation behavior in volatiles during low-temperature pyrolysis - Peipei Gao; Longfei Tang; Zichao Hu; Yue Sheng; Weitong Pan; Lu Ding; Xueli Chen; Fuchen Wang (Journal of Environmental Chemical Engineering, 2024)

High permeability Performance TFC Nanofiltration Membrane with Two dimensional Nanochannels Support Layer Fabricated by Dissolving of Nanosheets - Run-Hua Tang; Shu-Jun Deng; Sheng-Nan Zhao; Yong Shi; Jing Ye; Gui-E Chen; Zhen-Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Effect of combined dialysis method on dewatering of coagulant pretreated sludge - Yin-Lei Sun; Xin-Sheng Zhang; Ke-Meng Tian; Zi-Tang Wang; Chang-Biao He; Yue-Qin Wu (Journal of Environmental Chemical Engineering, 2024)

Effect of lactic acid bacteria fermentation on spray-dried egg yolk powder: Powder characteristics, structural properties and gastrointestinal digestibility - Zhe Li; Yanbin Song; Qinyue Tang; Xiang Duan; Long Sheng (Innovative Food Science & Emerging Technologies, 2024)

Biochar alleviates inhibition effects of humic acid on anaerobic digestion: Insights to performances and mechanisms - Sheng-Jie Sun; Fei Wang; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhihua Li; Wenzong Liu (Environmental Research, 2024)

An improved cracked soil evaporation model accounting for solar radiation and wind effect - Zhao-Jun Zeng; Chao-Sheng Tang; Cheng Zhu; Qing Cheng; Zi-Qi Luo; Zhan-Ming Yang; Bin Shi (Computers and Geotechnics, 2024)

Overlooked role of protocatechuic acid in enhancing the selective elimination of sulfonamide antibiotics in Fe(III)/peroxymonosulfate process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Zhijie Wu; Chenyu Tang; Linfeng He; Xiaobin Liao; Jun Ma (Chemical Engineering Journal, 2024)

A novel strategy with in vivo characterization, extraction, isolation and activity evaluation for discovery of absorbed anti-inflammatory oligosaccharides from Zhu-Ling decoction - Xi-yang Tang; Zhi-heng Shu; Peng-cheng Zhao; Wen Wei; Cai-lian Fan; Zhi-hong Yao; Xin-sheng Yao; Yi Dai (Carbohydrate Polymers, 2024)

Enhancing biocementation performance in low permeability clayey soil through sand column strategy - Xin-Lun Ji; Chao-Sheng Tang; Xiao-Hua Pan; Yao-Jia Cheng; Bin Shi (CATENA, 2024)

Sesquiterpenes from Tinospora sinensis and their chemotaxonomic significance - Rui Ao; Ming-Hui Li; Zi-Nan Xiao; Xue-Lian Tang; Jun-Sheng Zhang; Hua Zhang (Biochemical Systematics and Ecology, 2024)

Detection and localization of citrus picking points based on binocular vision - Chaojun Hou; Jialiang Xu; Yu Tang; Jiajun Zhuang; Zhiping Tan; Weilin Chen; Sheng Wei; Huasheng Huang; Mingwei Fang (Precision Agriculture, 2024)

Microbial metabolism strengths carbon sequestration and crop yield in upland red soil after long-term ex situ incorporation of straw - Li Tang; Xiaobin Guo; Daoyou Huang; Xiaomeng Wei; Hao Sheng; Pei Luo; Ping Zhou; Wei Gao; Yan Li; Miaomiao Zhang; Wei Zheng; Jinshui Wu (Journal of Soils and Sediments, 2024)

Bacterial functions are main driving factors on paddy soil organic carbon in both surface soil and subsoil - Xiang-Wen Huang; Jia-Jun Lin; De-Jin Li; Xiang-Qi Huang; Qi-Huan Xie; Sheng-Gang Pan; Xiang-Ru Tang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2024)

Simultaneous removal of Cd(II) and phosphate by nanoscale zero-valent iron from solution: Co-sorption and implication of corrosion - Haoyang Fu; Jie Sheng; Chenliu Tang; Wei-xian Zhang; Lan Ling (Chemosphere, 2024)

Mitigation of PBDE net discharge in hazardous waste thermal treatment system through reintroducion of sludge and fly ash into GASMILD operations - Wei Tang; Chun-Yun Hsiao; Sheng-Lun Lin; Jhong-Lin Wu; Dong Rip Kim; Yee-Lin Wu; Chien-Er Huang; Mengjie Song (Chemosphere, 2024)

Soil nitrogen and phosphorus regulate decomposition of organic nitrogen compounds in the rothamsted experiment - Sheng Tang; Wankun Pan; Jingjie Zhou; Qingxu Ma; Xiangde Yang; Wolfgang Wanek; Karina A. Marsden; Yakov Kuzyakov; David R. Chadwick; Lianghuan Wu; Andrew S. Gregory; Davey L. Jones (Soil Biology and Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Long-term non-flooded cultivation with straw return maintains rice yield by increasing soil pH and soil quality in acidic soil - Jingjie Zhou; Sheng Tang; Wankun Pan; Xiu Liu; Kefeng Han; Linlin Si; Qingxu Ma; Xiali Mao; Haoran Fu; Lianghuan Wu (European Journal of Agronomy, 2024)

3D DEM simulations of cyclic loading-induced densification and critical state convergence in granular soils - Tao Wang; Antoine Wautier; Chao-Sheng Tang; François Nicot (Computers and Geotechnics, 2024)

Boosted energy storage densities in lead-free Na0.5Bi0.5TiO3-based thick film ceramics via the compositional and microstructural tailoring - Xiang Niu; Yuleng Jiang; Wei Liang; Huanwei Liu; Xiaodong Jian; Xianyi Chen; Wenhan Zeng; Mingtao Xu; Dan Qie; Zichun Zhu; Yufeng Liu; Yi Tang; et al. (Chemical Engineering Journal, 2024)

Integrating spatially distributed data into Positive Matrix Factorization to identify the hotspots of local emission sources - Chun-Sheng Huang; Ho-Tang Liao; Chang-Fu Wu (Atmospheric Research, 2024)

Ultrafast DNA detection based on turn-back loop primer-accelerated LAMP (TLAMP) - Jinyi Shi; Sheng Ding; Chen Li; Gangyi Chen; Feng Du; Sifan Wang; Aiqin Yue; Kaiyuan Ren; Zhirong Yang; Pei Xu; Juan Dong; Jinzhong Zhao; et al. (Analytica Chimica Acta, 2024)

Mycorrhizal Symbiosis Increases Plant Phylogenetic Diversity and Regulates Community Assembly in Grasslands - Entao Zhang; Yang Wang; Shiping Chen; Daowei Zhou; Zhouping Shangguan; Jianhui Huang; Jin‐Sheng He; Yanfen Wang; Jiandong Sheng; Lisong Tang; Xinrong Li; Ming Dong; et al. (Ecology Letters, 2024)
The intricate mechanisms controlling plant diversity and community composition are cornerstone of ecological understanding. Yet, the role of mycorrhizal symbiosis in influencing community composition has often been underestimated. Here, we use extensive species survey data from 1315 grassland sites in China to elucidate the influence of mycorrhizal symbiosis on plant phylogenetic diversity and community assembly. We show that increasing mycorrhizal symbiotic potential leads to greater phylogenetic dispersion within plant communities. Mycorrhizal species predominantly influence deterministic processes, suggesting a role in niche‐based community assembly. Conversely, non‐mycorrhizal species exert a stronger influence on stochastic processes, highlighting the importance of random events in shaping community structure. These results underscore the crucial but often hidden role of mycorrhizal symbiosis in driving plant community diversity and assembly. This study provides valuable insights into the mechanisms shaping ecological communities and the way for more informed conservation that acknowledges the complex interplay between symbiosis and community dynamics.

Prenylated dihydroflavones from the root barks of Morus alba - Jun-Yu Zhu; Han-Zhuang Weng; Di-Kai Tang; Jin-Chen Long; Zhuo-Ya Tang; Ye Chen; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

The role of soil structure on the cracking and cadmium leaching behavior of biochar-amended fine-grained soils - Yu Lu; Kai Gu; Xiang Wang; Zhengtao Shen; Chao-Sheng Tang; Bin Shi; Qiyou Zhou (Chemosphere, 2024)

Protocatechuic acid enhanced the selective degradation of sulfonamide antibiotics in Fe(III)/peracetic acid process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Chenyu Tang; Shiyi Yang; Lingxin Chen; Qingsong Li; Panpan Wang; Jun Ma (Water Research, 2024)

High-resolution monitoring of soil infiltration using distributed fiber optic - Chang Sun; Chao-Sheng Tang; Farshid Vahedifard; Qing Cheng; Ao Dong; Teng-Fei Gao; Bin Shi (Journal of Hydrology, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Novel Eu-dipeptide assemblies for a fluorescence sensing strategy to ultrasensitive determine trace sulfamethazine - Rongfang Yan; Ning Zhang; Weihua Liu; Xuelian Hu; Wenxiu Wang; Yiwei Tang; Shuo Wang; Xianghong Wang; Qinghai Sheng (Food Chemistry, 2024)

Development of a novel anchorage and tensioning system for strengthening steel beams with unbonded prestressed CFRP plates - Hai-Tao Wang; Zhi-Ning Bian; Qiong Wu; Lili Hu; Min-Sheng Chen; Chao Tang (Engineering Structures, 2024)

Macrocyclic thiol ligand additive engineering for stable and efficient perovskite solar cells - Ju Zhang; Weihai Sun; Jihuai Wu; Jia Liu; Sheng Tang; Yiming Xie; Canzhong Lu; Fuda Yu (Chemical Engineering Journal, 2024)

Hydrogen peroxide enhanced Cu(II)/peroxymonosulfate system for naproxen degradation in natural water matrix and simultaneously reduced the formation potential of halogenated by-products - Jianying Wu; Jing Zou; Sheng Li; Chenyu Tang; Zhijie Wu; Linfeng He; Jinbin Lin; Qingsong Li; Jun Ma (Chemical Engineering Journal, 2024)

Serum LDL Promotes Microglial Activation and Exacerbates Demyelinating Injury in Neuromyelitis Optica Spectrum Disorder - Man Chen; Yun-Hui Chu; Wen-Xiang Yu; Yun-Fan You; Yue Tang; Xiao-Wei Pang; Hang Zhang; Ke Shang; Gang Deng; Luo-Qi Zhou; Sheng Yang; Wei Wang; et al. (Neuroscience Bulletin, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory demyelinating disease of the central nervous system (CNS) accompanied by blood-brain barrier (BBB) disruption. Dysfunction in microglial lipid metabolism is believed to be closely associated with the neuropathology of NMOSD. However, there is limited evidence on the functional relevance of circulating lipids in CNS demyelination, cellular metabolism, and microglial function. Here, we found that serum low-density lipoprotein (LDL) was positively correlated with markers of neurological damage in NMOSD patients. In addition, we demonstrated in a mouse model of NMOSD that LDL penetrates the CNS through the leaky BBB, directly activating microglia. This activation leads to excessive phagocytosis of myelin debris, inhibition of lipid metabolism, and increased glycolysis, ultimately exacerbating myelin damage. We also found that therapeutic interventions aimed at reducing circulating LDL effectively reversed the lipid metabolic dysfunction in microglia and mitigated the demyelinating injury in NMOSD. These findings shed light on the molecular and cellular mechanisms underlying the positive correlation between serum LDL and neurological damage, highlighting the potential therapeutic target for lowering circulating lipids to alleviate the acute demyelinating injury in NMOSD.

Wnt3a/GSK3β/β-catenin Signalling Modulates Doxorubicin-associated Memory Deficits in Breast Cancer - Wen Li; Chen Gan; Sheng Yu; Jian Xu; LingXue Tang; Huaidong Cheng (Molecular Neurobiology, 2024)

Effects of dietary Silphium perfoliatum L. on the growth performance, immunity, intestinal health, and resistance against Nocardia seriolae of largemouth bass (Micropterus salmoides) - Hao Tang; Sheng Luo; Jifeng Chen; Qianjin Zhou; Guanjun Yang; Jianfei Lu; Jiong Chen (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the effect of dietary Silphium perfoliatum L. on growth performance, immunity, intestinal health, and resistance against Nocardia seriolae of largemouth bass. Four dietary concentrations of S. perfoliatum L. were prepared: 0% (SPL0), 1% (SPL1), 2.5% (SPL2.5), and 5% (SPL5). After 60 d feeding, a challenge test was conducted by injecting N. seriolae intraperitoneally. The results showed that supplementing the diets with S. perfoliatum L. could promote the weight gain rate, specific growth rate, and feed intake. Meantime, S. perfoliatum L. could also enhance the activity of immune-related enzymes and improve the expression of immune-related genes in the liver. Compared to the control group, S. perfoliatum L. improved intestinal morphology and reduced the abundance of harmful bacteria in intestinal microbiota. Importantly, supplementing the diets with S. perfoliatum L. protected largemouth bass from N. seriolae infection, resulting in a relative percent survival (RPS) of 24% (SPL1), 31.99% (SPL2.5), and 43.99% (SPL5). In conclusion, the present study showed that S. perfoliatum L. could boost growth performance, enhance immunity, promote intestinal health, and improve the ability of largemouth bass against N. seriolae infection.

Numerical Study of Hydrodynamic Characteristics of a Three-Dimensional Oscillating Water Column Wave-Power Device - Jun-Lin Zhu; Peng Tang; Hong-Sheng Zhang; Peng-Bo Zheng (Journal of Marine Science and Engineering, 2024)
The impact of wave-induced forces on the integrity of stationary oscillating water column (OWC) devices is essential for ensuring their structural safety. In our study, we built a three-dimensional numerical model of an OWC device using the computational fluid dynamics (CFDs) software OpenFOAM-v1912. Subsequently, the hydrodynamic performance of the numerical model is comprehensively validated. Finally, the hydrodynamic performance data are analyzed in detail to obtain meaningful conclusions. Results indicate that the horizontal wave force applied to the OWC device is approximately 6.6 to 7.9 times greater than the vertical wave force, whereas the lateral wave force is relatively small. Both the horizontal and vertical wave forces decrease as the relative water depth increases under a constant wave period and height. In addition, the highest dynamic water pressure is observed at the interface between the water surface and device, both within and outside the front wall of the gas chamber. The dynamic water pressure at different locations on the front chamber increases and subsequently decreases as the wave frequency increases.

Two mutations on S2 subunit were critical for Vero cell tropism expansion of infectious bronchitis virus HV80 - Yi Jiang; Xu Cheng; Mingyan Gao; Yan Yu; Xinhong Dou; Haiyu Shen; Mengjun Tang; Sheng Zhou; Daxin Peng (Veterinary Microbiology, 2024)

Extracellular traps in skin lesions infected with lymphocystis disease virus in black rockfish (Sebastes schlegelii) - Qian Li; Qiujie Gan; Heng Chi; Xianghu Meng; Roy Ambli Dalmo; Xiuzhen Sheng; Xiaoqian Tang; Jing Xing; Wenbin Zhan (Fish & Shellfish Immunology, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Multi-scale investigation on dynamic characteristics of clayey soil evaporation and cracking - Hao Zeng; Chao-Sheng Tang; Alessandro Fraccica; Cheng Zhu; Ben-gang Tian; Bin Shi (Computers and Geotechnics, 2024)

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Simultaneous characterization and quantification of 25 flavonoid compounds in Actinidia arguta Miq. leaves by HPLC-DAD and screening for their inhibitory activity on α‑glucosidase - Yu-Fei Hou; Lu Bai; Shao-Jing Liu; Sen Guo; Ya-Long Wang; Chi-Tang Ho; Nai-Sheng Bai (Phytochemistry Letters, 2024)

Soil water potential measurement using fiber-optic sensing technique - Jin-Jian Xu; Chao-Sheng Tang; Qing Cheng; Farshid Vahedifard; Da-Zhan Zhang; Chang Sun; Bin Shi (Journal of Hydrology, 2024)

Occurrence and prevalence of per- and polyfluoroalkyl substances in the sediment pore water of mariculture sites: Novel findings of PFASs from the Bohai and Yellow Seas using a newly established analytical method - Nan Shen; Jiale Tang; Junhui Chen; Cancan Sheng; Tongzhu Han; Xiuping He; Chenguang Liu; Chao Han; Xianguo Li (Journal of Hazardous Materials, 2024)

A biotechnological approach for suspended solids removal in biogas slurry via microbially induced calcite precipitation (MICP) - Rui Wang; Chao-Sheng Tang; Xiaohua Pan; Zhengtao Shen; Yujia Liu; Xiancai Lu (Journal of Cleaner Production, 2024)

Facile synthesis of CoFeAl-layered double hydroxides activated by peroxymonosulfate for enhanced ciprofloxacin degradation - Xiao Li; Sheng Xiong; Xiangwei Tang; Rongdi Tang; Yaocheng Deng; Daoxin Gong (Journal of Environmental Chemical Engineering, 2024)

Sensitive fluorescence detection based on dimeric G-quadruplex combined with enzyme-assisted solid-phase microextraction of streptomycin in honey - Dezhao Kong; Yitong Chen; Yidan Gu; Chao Ding; Chang Liu; Wei Shen; Hian Kee Lee; Sheng Tang (Food Chemistry, 2024)

Experimental study on the flexural performance of prestressed RC beams with post-tensioned CFRP strands - Hai-Tao Wang; Chao Tang; Min-Sheng Chen; Jianzhe Shi; Xu-Yang Cao (Engineering Structures, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Recombinase-aided amplification coupled with lateral flow dipstick for efficient and accurate detection of Bombyx mori nucleopolyhedrovirus - Runpeng Wang; Sheng Xu; Erjun Wei; Ping He; Yiling Zhang; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2024)

Effects of RNA Interference with Acetyl-CoA Carboxylase Gene on Expression of Fatty Acid Metabolism-Related Genes in Macrobrachium rosenbergii under Cold Stress - Hua Zhong; Xinyi Yao; Haihui Tu; Zhenglong Xia; Miaoying Cai; Qiang Sheng; Shaokui Yi; Guoliang Yang; Qiongying Tang (Fishes, 2024)
Macrobrachium rosenbergii is a warm water species, and low temperature is a limiting factor for its growth and survival. In order to explore the role of the acetyl-CoA-carboxylase (ACC) gene in response to the cold stress of M. rosenbergii, we investigated the effects of RNA interference (RNAi) with the ACC gene on the expression of fatty acid metabolism-related genes and the mortality of M. rosenbergii under cold stress. The results showed that different siRNA sequences and different injection concentrations had different inhibiting effects on ACC gene expression, and siRNA-III with an injection concentration of 2.0 μg/g (siRNA/prawn body weight) had the best interference effect. With the optimal siRNA and the optimal concentration under cold stress, the expressions of three fatty acid metabolism-related genes, FabD, echA, and ACOT, were generally significantly down-regulated. Compared to negative (scrambled-siRNA) and blank (PBS) control groups, the expression of FabD in the interference group was extremely significantly down-regulated at 12 h in the hepatopancreas and at 18 h in the muscles and gills; EchA was highly significantly down-regulated at 6 and 12 h in the muscles and gills; and ACOT was extremely significantly down-regulated and kept declining in the gills. Within 6–18 h after injection under cold stress, the mortality rate of the siRNA interference group (75%) was much lower than that of the negative (95%) or blank control group (97.5%), and all prawns died after 24 h. In conclusion, RNA interference with the ACC gene inhibited the expression of some fatty acid metabolism-related genes, and could partly improve the tolerance of M. rosenbergii to cold stress, indicating that the ACC gene might play an important role in the response of M. rosenbergii to cold stress.

Blue source-based food alternative proteins: Exploring aquatic plant-based and cell-based sources for sustainable nutrition - Yue Li; Ning Xiang; Yuyan Zhu; Ming Yang; Chenchen Shi; Yunan Tang; Weijun Sun; Kuichuan Sheng; Donghong Liu; Ximing Zhang (Trends in Food Science & Technology, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

GABLE: A first fine-grained 3D building model of China on a national scale from very high resolution satellite imagery - Xian Sun; Xingliang Huang; Yongqiang Mao; Taowei Sheng; Jihao Li; Zhirui Wang; Xue Lu; Xiaoliang Ma; Deke Tang; Kaiqiang Chen (Remote Sensing of Environment, 2024)

Adjuvant effects of β-defensin on DNA vaccine OmpC against edwardsiellosis in flounder (Paralichthys olivaceus) - Heng Chi; Qingqing Qin; Xiaokai Hao; Roy Ambli Dalmo; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan (Fish & Shellfish Immunology, 2024)

The interaction between the costimulatory molecules CD80/86 and CD28 contributed to CD4+ T lymphocyte activation in flounder (Paralichthys olivaceus) - Jing Xing; Yujie Hu; Wenjing Liu; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Influence of desiccation during freeze-thaw cycles on volumetric shrinkage and tensile strength of compacted clayey soils - Yao Wei; Chao-Sheng Tang; Cheng Zhu; Qing Cheng; Yang Lu; Lin Li; Ben-Gang Tian; Bin Shi (Engineering Geology, 2024)

Simultaneous water softening and selective ammonia nitrogen recovery from coal gasification gray water using an innovative four-chamber flow-electrode electrochemistry system - Taoqin Chen; Sheng Wei; Longqian Xu; Xianchun Tang; Hongbin Chen (Desalination, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Electroacupuncture Exerts Analgesic Effects by Restoring Hyperactivity via Cannabinoid Type 1 Receptors in the Anterior Cingulate Cortex in Chronic Inflammatory Pain - Junshang Wu; Libo Hua; Wenhao Liu; Xiaoyun Yang; Xiaorong Tang; Si Yuan; Sheng Zhou; Qiuping Ye; Shuai Cui; Zhennan Wu; Lanfeng Lai; Chunzhi Tang; et al. (Molecular Neurobiology, 2024)
As one of the commonly used therapies for pain-related diseases in clinical practice, electroacupuncture (EA) has been proven to be effective. In chronic pain, neurons in the anterior cingulate cortex (ACC) have been reported to be hyperactive, while the mechanism by which cannabinoid type 1 receptors (CB1Rs) in the ACC are involved in EA-mediated analgesic mechanisms remains to be elucidated. In this study, we investigated the potential central mechanism of EA analgesia. A combination of techniques was used to detect the expression and function of CB1R, including quantitative real-time PCR (q-PCR), western blot (WB), immunofluorescence (IF), enzyme-linked immunosorbent assay (ELISA), and in vivo multichannel optical fibre recording, and neuronal activity was examined by in vivo two-photon imaging and in vivo electrophysiological recording. We found that the hyperactivity of pyramidal neurons in the ACC during chronic inflammatory pain is associated with impairment of the endocannabinoid system. EA at the Zusanli acupoint (ST36) can reduce the hyperactivity of pyramidal neurons and exert analgesic effects by increasing the endocannabinoid ligands anandamide (AEA), 2-arachidonoylglycerol (2-AG) and CB1R. More importantly, CB1R in the ACC is one of the necessary conditions for the EA-mediated analgesia effect, which may be related to the negative regulation of the N-methyl-D-aspartate receptor (NMDAR) by the activation of CB1R downregulating NR1 subunits of NMDAR (NR1) via histidine triad nucleotide-binding protein 1 (HINT1). Our study suggested that the endocannabinoid system in the ACC plays an important role in acupuncture analgesia and provides evidence for a central mechanism of EA-mediated analgesia.

Experimental study on the influence mechanism of soil additives on scraper wear during EPB-TBM tunnelling in abrasive sandy ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Wei-Qiang Xie; Jian Wu; Hao-Jie Wang; Xin-Fang Li (Bulletin of Engineering Geology and the Environment, 2024)

Experimental investigation of critical parameters for the binary mixture of CO2 + R1336mzz(Z) (cis-1,1,1,4,4,4-hexafluoro-2-butene) and analysis of critical locus for CO2 + hydrofluoroolefin systems - Bo Tang; Xiaoyu Yao; Xueqiang Dong; Bowen Sheng; Yanxing Zhao; Jun Shen; Maoqiong Gong (International Journal of Refrigeration, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Numerical analysis of environmental influences on evaporation in a cracked soil slope - Zhao-Jun Zeng; Chao-Sheng Tang; Qing Cheng; Ni An; Xiao-Ying Chen; Zi-Qi Luo; Bin Shi (Computers and Geotechnics, 2024)

Seasonal variations in air-sea CO2 flux in the Bohai Sea and the temporal relationship between surface and bottom-water carbonate dynamics in a year - Hong-sheng Zhang; Wei-dong Zhai; Kai Tang (Continental Shelf Research, 2024)

Construction of hydrophobic core-shell flame retardant: A novel strategy towards reducing fire hazards and reinforcing mechanical properties of polypropylene - Jie Hu; Jia-Yan Hu; Yu-Jie Chen; Liu Tan; Qian Luo; Wen-Juan Yan; Zhe-Hong Tang; Juan-Juan Zhang; Lei Wang; Nai-Liang Wang; Sheng Xu (Applied Clay Science, 2024)

Exploring the potential applications of amphiphilic carbon dots based nanocomposite hydrogel in liquid chromatographic separations - Qiaoling Liu; Kunming Zhou; Yanjuan Liu; Yuefei Zhang; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2024)

Chemical constituents of Wikstroemia alternifolia and their neuroprotective activities - Qing-Ren Lu; Yan Wang; Zhuo-Ya Tang; Ye Chen; Han-Zhuang Weng; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

Development of natural attapulgite derived ferromanganese spinel oxides as heterogeneous catalysts for persulfate activation of tetracycline degradation - Zhenzhong Hu; Xuejing Tang; Xiaojia Ma; Sheng-qi Guo; Mengmeng Zhen; Jingxia Ning; Sheng Xu; Boxiong Shen (Chemosphere, 2024)

Automatic detection and counting of planthoppers on white flat plate images captured by AR glasses for planthopper field survey - Haiyuan Sheng; Qing Yao; Ju Luo; Yongjian Liu; Xiangfu Chen; Zhongru Ye; Tiezhuang Zhao; Heping Ling; Jian Tang; Shuhua Liu (Computers and Electronics in Agriculture, 2024)

Revealing the synergistic effect between radical and non-radical species of sulfur-doped carbon nitride for ciprofloxacin removal: Based on density functional theory study - Hao Zeng; Zhanpeng Zhou; Wenbo Li; Ling Li; Rongdi Tang; Sheng Xiong; Daoxin Gong; Ying Huang; Lianyang Bai; Yaocheng Deng (Science of The Total Environment, 2024)

Preparation of a capsaicinoids broad spectrum antibody and its application in non-enzyme immunoassay based on DMSNs@PDA@Pt - Zixin Jin; Wei Sheng; Meiyi Sun; Dongmei Bai; Lishuai Ren; Shuo Wang; Ziwuzhen Wang; Xinshuang Tang; Tingting Ya (Journal of Hazardous Materials, 2024)

Substation of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2024)

Exploring xylitol as a low-salt alternative for effective inhibition of gelation in frozen egg yolks - Xiaoli Xu; Zhe Li; Qinyue Tang; Bao Chen; Haobo Jin; Yaqin Yang; Dewei Shu; Zhaoxia Cai; Long Sheng (Food Chemistry, 2024)

Lithium recovery from the spent lithium-ion batteries by commercial acid-resistant nanofiltration membranes: A comparative study - Sheng-Li Gao; Zi-Xuan Qin; Bo-Fei Wang; Jie Huang; Zhen-Liang Xu; Yong-Jian Tang (Desalination, 2024)

Analysis of the stability of cracked soil slopes using a numerical model incorporating stochastic theory - Xiao-Ying Chen; Chao-Sheng Tang; Qing Cheng; Zhao-Jun Zeng; Bin Shi (Computers and Geotechnics, 2024)

Bio-adhesive barrier with active ROS-scavenging ability for simultaneous management of dura tear and epidural inflammatory fibrosis - Meng Han; Jincheng Tang; Haiyue Zhao; Yachao Sheng; Ziang Li; Wenxiao Shi; Jiahao Wang; Chao Ma; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2024)

Unprecedented sulfenic acid-dependent hydroxyl radical production and DNA damage by N-heterocyclic thiols and H2O2 - Li Mao; Zhi-Sheng Liu; Chun-Hua Huang; Tian-Shu Tang; Hao-Zhe Zhang; Shi-Yu Chen; Ben-Zhan Zhu (Chemical Engineering Journal, 2024)

l-Cysteine and barium titanate co-modified enteromorpha biochar as effective peroxymonosulfate activator for atrazine treatment - Sheng Xiong; Hao Zeng; Rongdi Tang; Naif Abdullah Al-Dhabi; Wenbo Li; Zhanpeng Zhou; Ling Li; Wangwang Tang; Daoxin Gong; Yaocheng Deng (Bioresource Technology, 2024)

Biodegradation and bioavailability of low-molecular-weight dissolved organic sulphur in soil and its role in plant-microbial S cycling - Qingxu Ma; Congyue Tou; Sheng Tang; Deying Wang; Wankun Pan; Lianghuan Wu; Davey L. Jones (Plant and Soil, 2024)

CCL2 Knockdown Attenuates Inflammatory Response After Spinal Cord Injury Through the PI3K/Akt Signaling Pathway: Bioinformatics Analysis and Experimental Validation - Sheng Fang; Hao Tang; Hai-long Li; Ti-Chao Han; Zi-Jie Li; Zong-Sheng Yin; Jian-Jun Chu (Molecular Neurobiology, 2024)

Hessian Regularized $$L_{2,1}$$-Nonnegative Matrix Factorization and Deep Learning for miRNA–Disease Associations Prediction - Guo-Sheng Han; Qi Gao; Ling-Zhi Peng; Jing Tang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

The preparation of layered double hydroxide wrapped with triazine-based organic framework to enhance the flame retardancy for polypropylene - Zhe-Hong Tang; Chi-Jie Ding; Cheng-Zhi Zhong; Juan-Juan Zhang; Lei Wang; Zhi-Hao Liu; Sheng Xu (Applied Clay Science, 2024)

Remobilization of Cd caused by iron oxide phase transformation and Mn2+ competition after stabilization by nano zero valent iron - Mengjiao Liu; Xiya Wang; Sheng Tang; Jingjie Zhou; Longfei Liu; Qingxu Ma; Lianghuan Wu; Meng Xu (Chemosphere, 2024)

Pyrolysis of municipal plastic waste: Chlorine distribution and formation of organic chlorinated compounds - Peipei Gao; Zichao Hu; Yue Sheng; Weitong Pan; Lu Ding; Longfei Tang; Xueli Chen; Fuchen Wang (Science of The Total Environment, 2024)

Assessing the effectiveness of 3, 4-dimethylpyrazole phosphate (DMPP) inhibitor in mitigating N2O emissions from contrasting Cd-contaminated soils - Muhammad Laeeq Ur Rehman Hashmi; Yasir Hamid; Muhammad Usman; Jipeng Luo; Sangar Khan; Tang Sheng; Nabila Bano; TalhaTufail Bhatti; Tingqiang Li (Science of The Total Environment, 2024)

Enhanced internal circulation for struvite crystallization in a novel air-lift circulation reactor with Venturi structure for ammonium recovery from wastewater - Zhigong Liu; Tianyu Gao; Qaisar Mahmood; Lili Guo; Weizhi Zeng; Xi Tang; Sheng Hu; Shengguo Xue; Xiaobo Min; Chong-Jian Tang (Journal of Water Process Engineering, 2024)

Contributions of climate change and urbanization to urban flood hazard changes in China's 293 major cities since 1980 - Ziyi Tang; Pin Wang; Yao Li; Yue Sheng; Ben Wang; Nataliia Popovych; Tangao Hu (Journal of Environmental Management, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Enhanced mitigation of inhalable particles and fine particle-bound PAHs from a novel hazardous waste-power plant candidate - Wei Tang; Che-Wei Wu; Sheng-Lun Lin; Jhong-Lin Wu; Shih-Wei Huang; Mengjie Song (Environmental Pollution, 2024)

Field and numerical investigation of soil hydro-thermal response to the climatic conditions in southern China considering soil heterogeneity - Zhao-Jun Zeng; Chao-Sheng Tang; Qing Cheng; Ni An; Zhan-Ming Yang; Xu-Long Gong; Xiao-Ying Chen (Engineering Geology, 2024)

Evaporation and desiccation cracking of soils: Experiment evidence and insight on the freeze-thaw cycle dependence - Yao Wei; Chao-Sheng Tang; Yang Lu; Mingli Zhang; Qing Cheng; Lin Li; Bin Shi (Engineering Geology, 2024)

A Highly Efficient and Energy Saving Electrochromic Platform for Adaptive Visible and Near-Infrared Light Modulation - Dajiang Tang; Junxin Wang; Xiaoyu Huang; Dashui Zhang; Sheng Cao; Linfei Yin; Zhangfa Tong; Hongbing Ji; Rachel C. Evans; Hui-Ying Qu (Chemical Engineering Journal, 2024)

Boosting ion diffusion kinetics of Fe2O3/MoC@NG via heterointerface engineering and pseudocapacitance behavior: An alternative high-rate anode for high‐capacity lithium dual-ion batteries - Juan Ding; Yudai Huang; Wenhua Cheng; Rui Sheng; Zhenjie Liu; Xingchao Wang; Yong Guo; Jiulin Wang; Dianzeng Jia; Xincun Tang; Lei Wang (Chemical Engineering Journal, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Se-(Methyl)-selenocysteine ameliorates blood-brain barrier disruption of focal cerebral ischemia mice via ferroptosis inhibition and tight junction upregulation in an Akt/GSK3β-dependent manner - Yuxiang Fei; Tao Li; Ruoyu Wu; Xuejiao Xu; Sheng Hu; Ya Yang; Chenchen Jin; Wenlian Tang; Xu Zhang; Qianming Du; Chao Liu (Psychopharmacology, 2024)

Effects of tillage practices on soil organic carbon, microbial community and necromass in a double rice cropping system - Jian-Ying Qi; Xiang-Bin Yao; Xue-Chan Zhang; Mei-Yi Fan; Jian-Fu Xue; Jun-Li Cao; Ahmad Latif Virk; Sheng-Gang Pan; Xiang-Ru Tang (Applied Soil Ecology, 2024)

Leveraging CRISPR/Cas12 signal amplifier to sensitive detection of apurinic/apyrimidinic endonuclease 1 and high-throughput inhibitor screening - Sheng Ding; Yi Yuan; Juan Dong; Feng Du; Xin Cui; Zheng Shi; Zhuo Tang (Analytica Chimica Acta, 2024)

Analysis of fluid flow characteristics in spherical nonlinear seepage flow model for dual-porous reservoir with the elastic outer boundary - Sheng Guo; Peng she Zheng; Ya Tang; Li hui Leng; Shun chu Li (Acta Geophysica, 2024)

The anti-cancer drug candidate CBL0137 induced necroptosis via forming left-handed Z-DNA and its binding protein ZBP1 in liver cells - Jun Li; Miao Tang; Ruo-Xian Ke; Pei-Lin Li; Zhi-Guo Sheng; Ben-Zhan Zhu (Toxicology and Applied Pharmacology, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Dichapetalin-type triterpenoids from Dichapetalum longipetalum and their anti-inflammatory activity - Dong-Li Zhang; Yue Wang; Jing-Bo Liu; Qian Chen; Shao-Yong Li; De-Jun Jin; Sheng-An Tang (Phytochemistry, 2024)

Homogeneous fluorescence immunoassay based on AuNPs quenching dendritic silica assembled with multicolor QDs for the simultaneous determination of four mycotoxins in cereals - Zixin Jin; Wei Sheng; Lishuai Ren; Dongmei Bai; Meiyi Sun; Shuo Wang; Tingting Ya; Xinshuang Tang; Ziwuzhen Wang (Chemical Engineering Journal, 2024)

Effects of land-use patterns on seasonal water quality at multiple spatial scales in the Jialing River, Chongqing, China - Yuan-Bo Wang; Muhammad Junaid; Jiao-Yun Deng; Qi-Ping Tang; Lin Luo; Zhuo-Yuan Xie; De-Sheng Pei (CATENA, 2024)

Experimental study on shrinkage characteristics of compacted bentonite–sand mixtures - Dong-Wei Wang; Cheng Zhu; Chao-Sheng Tang; Qing Cheng; Sheng-Jie Li; Bin Shi (Bulletin of Engineering Geology and the Environment, 2024)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Migration characteristics of chlorine during pyrolysis of municipal solid waste pellets - Peipei Gao; Zichao Hu; Yue Sheng; Weitong Pan; Longfei Tang; Yihan Chen; Xueli Chen; Fuchen Wang (Waste Management, 2023)

RETRACTED: Synthesis and application of waste-based layered double hydroxide: A review - Yimei Jiang; Zhengtao Shen; Chao-Sheng Tang; Bin Shi (Science of The Total Environment, 2023)

Sustainable development of World Cultural Heritage sites in China estimated from optical and SAR remotely sensed data - Fulong Chen; Huadong Guo; Peifeng Ma; Yunwei Tang; Fan Wu; Meng Zhu; Wei Zhou; Sheng Gao; Hui Lin (Remote Sensing of Environment, 2023)

Enhancing stability of 1,3-dioleic acid-2-palmitate (OPO) through microencapsulation: A comparative study of single- and double-layer microcapsules - Qinyue Tang; Zhe Li; Xiaoli Xu; Panpan Wang; Bao Chen; Yaqin Yang; Guofeng Jin; Long Sheng (Food Hydrocolloids, 2023)

Coupled effects of temperature and relative humidity on desiccation curling of a clayey soil - Zhan-Ming Yang; Qing Cheng; Chao-Sheng Tang; Ben-Gang Tian; Xi-Ying Zhang (Engineering Geology, 2023)

Improving soil resilience to drought climate by an eco-friendly approach - Lin Li; Chao-Sheng Tang; Jin-Jian Xu; Yao Wei; Qing Cheng; Bin Shi (Engineering Geology, 2023)

Investigating cracking behavior of saline clayey soil under cyclic freezing-thawing effects - Shaini Aluthgun Hewage; Chao-Sheng Tang; Yusuf Mehta; Cheng Zhu (Engineering Geology, 2023)

Dose assessment on the impact of accidents with Fukushima nuclear meltdown emission levels at the four nuclear power plants in Taiwan - Mei-Ling Tang; Ben-Jei Tsuang; Pei-Hsuan Kuo; Yi-Sheng Wang; Xin-Yu Liu; Kai-Chen Ku (Energy and Climate Change, 2023)

Compositionally complex doping for low-V Ti-Cr-V hydrogen storage alloys - Yongyang Zhu; Xubo Li; Xu-Sheng Yang; Pengyun Chen; Gary Chi-Pong Tsui; Zheng-Long Xu; Renheng Tang; Fangming Xiao; Kangcheung Chan (Chemical Engineering Journal, 2023)

The analyses of the complete mitochondrial genomes of three crabs revealed novel gene rearrangements and phylogenetic relationships of Brachyura - Zhao-Zhe Xin; Sheng Tang; Xiang Lu; Hua-Bin Zhang; Dai-Zhen Zhang; Gang Wang; Bo-Ping Tang; Qiu-Ning Liu (Molecular Biology Reports, 2023)

Effects of abnormal expression of CD73 on malignant phenotype of nasopharyngeal carcinoma - Bin Jiang; Mingming Tang; Si Shi; Haijing Xie; Si Pan; Lin Zhang; Juping Sheng (Journal of Molecular Histology, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Ionic liquid/covalent organic framework/silica composite material: Green synthesis and chromatographic evaluation - Yuanfei Liu; Sunqi Shang; Wanjiao Wei; Yuefei Zhang; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2023)

Long-term application of controlled-release fertilizer enhances rice production and soil quality under non-flooded plastic film mulching cultivation conditions - Jingjie Zhou; Sheng Tang; Wankun Pan; Meng Xu; Xiu Liu; Liang Ni; Xiali Mao; Tao Sun; Haoran Fu; Kefeng Han; Qingxu Ma; Lianghuan Wu (Agriculture, Ecosystems & Environment, 2023)

Fluviispira vulneris sp. nov., isolated from human wound secretions - Peijuan Tang; Na Peng; Pengwen Ouyang; Sheng Long; Zhenhua Wei; Xingchun Chen; Pinghua Qu; Liangyi Xie (Antonie van Leeuwenhoek, 2023)
Human infections by environmental bacteria is becoming an increasing problem and has become a matter of great concern due to the adverse effects worldwide. In this study, we reported a new environmental pathogen. Isolate GX5518 T was a novel Gram-negative, aerobic, non-motile, pleomorphic and red-pigmented bacterium, was isolated from human wound secretions (GuangXi, People’s Republic of China). Growth occurred at pH 6.0–8.0 (optimum, pH 7.0) and 10–37 °C (optimum, 28–32 °C) with 0–1.5% (w/v) NaCl in R2A agar. Comparative analysis of the 16S rRNA gene sequences revealed that isolate GX5518 T was closely related to Fluviispira sanaruensis JCM 31447 T (99.73%) and Fluviispira multicolorata 33A1-SZDP T (98.49%). However, the estimated ANI values of the isolate GX5518 T compared to the F. sanaruensis JCM 31447 T and F. multicolorata 33A1-SZDP T were 88.67% and 77.35%, respectively. The estimated dDDH, ANI and AAI values between isolate GX5518 T and its closely related strains were below the threshold values generally considered for recognizing a new species. The genome size was 3.6 Mbp and the DNA G + C content was 33.1%. The predominant fatty acids (> 5%) in GX5518 T cells were iso-C 15:0 , C 16:0 , C 17:0 , C 17:1 ω 8 c and C 16:1 ω 7 c /C 16:1 ω 6 c . The major menaquinone was MK-8 (86.9%). The polar lipids were phosphatidylethanolamine (PE), phosphatidylglycerol (PG) and three unknown lipids (L1-3). The chemical composition was different from that of the F. sanaruensis JCM 31447 T . Comparative genomics analysis between isolate GX5518 T and its related strains revealed that there were a number of genes involved in resistance to antibiotics and toxic compounds in isolate GX5518 T , which were responsible for the copper homeostasis, cobalt-zinc-cadmium resistance, resistance to fluoroquinolones, and zinc resistance. Based on the phenotypic, chemotaxonomic, and genomic analyses, isolate GX5518 T (= CGMCC 1.18685 T = KCTC 82149 T ) represents a novel species of the genus Fluviispira , for which the name Fluviispira vulneris sp. nov. is proposed.

New benzofuran neolignans with neuroprotective activity from Phyllanthodendron breynioides - Tong Su; Mei-Cen Pu; Di-Kai Tang; Jin-Chen Long; Fang-Yu Yuan; Ai-Ping Yin; Shu-Qi Wu; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2023)

Effects of anode materials on nitrate reduction and microbial community in a three-dimensional electrode biofilm reactor with sulfate - Chunhong Jin; Qi Tang; Hengduo Xu; Yanqing Sheng (Chemosphere, 2023)

Soil selenium enrichment in the Loess Plateau of China: Geogenic evidence, spatial distribution, and it's influence factors - Xuezhen Li; Qingye Hou; Yiren Duan; Yongchun Li; Kun Lin; Bo Li; Weikang Sheng; Yongliang Wang; Rilige Su; Zhoulei Gu; Tao Yu; Qifeng Tang; et al. (Chemosphere, 2023)

Fast perception of rock mass strength and integrity in TBM tunnelling using in-situ penetration test - Wei-Qiang Xie; Xiao-Ping Zhang; Shao-Hui Tang; Xiao-Li Liu; Xin-Fang Li; Qi Zhang; Fa-Yuan Yan; Chen Xu; Quan-Sheng Liu (Tunnelling and Underground Space Technology, 2023)

Bacteria pyruvate metabolism modulates AFB1 toxicity in Caenorhabditis elegans - Bowen Tang; Kathy S. Xue; Jia-Sheng Wang; Phillip L. Williams; Lili Tang (Science of The Total Environment, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

The stage-specific toxicity of per- and polyfluoroalkyl substances (PFAS) in nematode Caenorhabditis elegans - Seth D. Currie; Joseph Patrick Doherty; Kathy S. Xue; Jia-Sheng Wang; Lili Tang (Environmental Pollution, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Understanding enhancement of strong Copper-Yttrium interactions on catalytic properties of Cu/Y-SSZ-13 for NH3-SCR - Na Kang; Yan Wang; Zhi Wen Chen; Xuan Tang; Yuanjiang Wang; Zhiyong Ding; Cheng Zhang; Sheng Dai; Chandra Veer Singh; Pengfei Xie; Mi Yan (Chemical Engineering Journal, 2023)

Effect and mechanism of a concentration-dependent inorganic ion biomimetic periosteum in a repairing bone defect - Lichen Zhang; Jincheng Tang; Meng Han; Yang Sun; Wei Wang; Zhuojun Wu; Yachao Sheng; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2023)

Effect of atmospheric pollen concentration on daily visits of allergic rhinitis in Beijing: a distributed lag nonlinear model analysis - Aizhu Liu; Weixuan Sheng; Xianshi Tang; Jinshu Yin (International Journal of Biometeorology, 2023)

Monitoring and mapping the evolution of clayey soil desiccation cracking using electrical resistivity tomography - Jun-Zheng Zhang; Chao-Sheng Tang; Cheng Zhu; Qi-You Zhou; Jin-Jian Xu; Bin Shi (Bulletin of Engineering Geology and the Environment, 2023)

Corrigendum to “Lipidomic biomarkers: Potential mediators of associations between urinary bisphenol A exposure and colorectal cancer” [J Hazard Mater 427 (2022) 127863 - Xu Hong; Gengfu Wang; Xingcun Liu; Ming Wu; Xindong Zhang; Xiaohui Hua; Pengpeng Jiang; Sheng Wang; Song Tang; Xiaoming Shi; Yichao Huang; Tong Shen (Journal of Hazardous Materials, 2023)

Piezoelectricity ameliorates high-valent iron oxo species production in peroxymonosulfate activation for refractory atrazine remediation - Sheng Xiong; Hao Zeng; Rongdi Tang; Ling Li; Zhanpeng Zhou; Wenbo Li; Daoxin Gong; Yaocheng Deng (Journal of Hazardous Materials, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

The severity of foreign direct investment components on China's carbon productivity - Xin Sheng; Rui Yi; Decai Tang; David D. Lansana; Bright Obuobi (Journal of Cleaner Production, 2023)

Dual-supported nanoscale zero-valent iron for As(III) contaminated groundwater remediation - Ying Liang; Lu Tang; Jun Jiang; Meng-li Li; Hua-gang Lv; Yong He; Hong-yu Liu; Sheng-guo Xue (Journal of Environmental Chemical Engineering, 2023)

Mechanism underlying joint loading and controlled release of β-carotene and curcumin by octenylsuccinated Gastrodia elata starch aggregates - Zhen Wu; Xin Tang; Simei Liu; Sheng Li; Xiaowan Zhao; Yongde Wang; Xiaogang Wang; Hong Li (Food Research International, 2023)

Genome-wide identification, phylogenetic relationships and expression patterns of the NOD-like receptor (NLR) gene family in flounder (Paralichthys olivaceus) - Yingqin Liu; Xiuzhen Sheng; Xiaoqian Tang; Jing Xing; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2023)

A numerical model of water evaporation from cracked soil - Zhao-Jun Zeng; Chao-Sheng Tang; Qing Cheng; Ni An; Xiao-Ying Chen; Bin Shi (Computers and Geotechnics, 2023)

Establishment of protoplasts transient expression system in Pinellia ternata (Thunb.) Breit - Yu-hang Tian; Miao Liu; Liu Tang; Yu-jin Zhang; Ye Hang; Li-yang Shangguan; Yin-qun Zhang; Ming-sheng Zhang (Biotechnology Letters, 2023)

Preparation and application of a novel imine-linked covalent organic framework@silica composite for reversed-phase and hydrophilic interaction chromatographic separations - Wanjiao Wei; Haoyu Long; Yanjuan Liu; Yuefei Zhang; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2023)

Multiscale study on differences in regional economic resilience in China - Guandong Song; Chengli Tang; Sheng Zhong; Liuguang Song (Environment, Development and Sustainability, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Afidopyropen suppresses silkworm growth and vitality by affecting carbohydrate metabolism and immune function - Erjun Wei; Ping He; Runpeng Wang; Sheng Xu; Yiling Zhang; Qiang Wang; Xudong Tang; Zhongyuan Shen (Pesticide Biochemistry and Physiology, 2023)

Fe-loaded alginate hydrogel beads activating peroxymonosulfate for enhancing anaerobic fermentation of waste activated sludge: Performance and potential mechanism - Yaqian Chai; Cheng Huang; Mengya Sui; Yuqi Yin; Nan Sun; Yong Chen; Zhiming Liao; Xiuyun Sun; Wei Shen; Sheng Tang (Journal of Environmental Management, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Comparison and Selection of Index for Macro-indentation Test of Brittle Rock - Xiao-Ping Zhang; Xin-Mei Yang; Wei-Qiang Xie; Quan-Sheng Liu; Shao-hui Tang (Rock Mechanics and Rock Engineering, 2023)

Segmentation of rectal tumor from multi-parametric MRI images using an attention-based fusion network - Meng Dou; Zhebin Chen; Yuanling Tang; Leiming Sheng; Jitao Zhou; Xin Wang; Yu Yao (Medical & Biological Engineering & Computing, 2023)

Study on the lower head failure in severe accident Part I: Model development and validation - Pengcheng Gao; Bin Zhang; Hao Yang; Jishen Li; Fan Miao; Shaowei Tang; Sheng Cao; Jianqiang Shan (Annals of Nuclear Energy, 2023)

Carbon–biodiversity relationships in a highly diverse subtropical forest - Andreas Schuldt; Xiaojuan Liu; François Buscot; Helge Bruelheide; Alexandra Erfmeier; Jin‐Sheng He; Alexandra‐Maria Klein; Keping Ma; Michael Scherer‐Lorenzen; Bernhard Schmid; Thomas Scholten; Zhiyao Tang; et al. (Global Change Biology, 2023)
Carbon‐focused climate mitigation strategies are becoming increasingly important in forests. However, with ongoing biodiversity declines we require better knowledge of how much such strategies account for biodiversity. We particularly lack information across multiple trophic levels and on established forests, where the interplay between carbon stocks, stand age, and tree diversity might influence carbon–biodiversity relationships. Using a large dataset (>4600 heterotrophic species of 23 taxonomic groups) from secondary, subtropical forests, we tested how multitrophic diversity and diversity within trophic groups relate to aboveground, belowground, and total carbon stocks at different levels of tree species richness and stand age. Our study revealed that aboveground carbon, the key component of climate‐based management, was largely unrelated to multitrophic diversity. By contrast, total carbon stocks—that is, including belowground carbon—emerged as a significant predictor of multitrophic diversity. Relationships were nonlinear and strongest for lower trophic levels, but nonsignificant for higher trophic level diversity. Tree species richness and stand age moderated these relationships, suggesting long‐term regeneration of forests may be particularly effective in reconciling carbon and biodiversity targets. Our findings highlight that biodiversity benefits of climate‐oriented management need to be evaluated carefully, and only maximizing aboveground carbon may fail to account for biodiversity conservation requirements.

Biochar implications for the engineering properties of soils: A review - Yu Lu; Kai Gu; Zhengtao Shen; Chao-Sheng Tang; Bin Shi; Qiyou Zhou (Science of The Total Environment, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

Magnetic three-phase single-drop microextraction for highly sensitive detection of aflatoxin B1 in agricultural product samples based on peroxidase-like spatial network structure - Jingyu Kuang; Jiahe Ju; Yongli Lu; Yitong Chen; Chang Liu; Dezhao Kong; Wei Shen; Hai-Wei Shi; Li Li; Jin Ye; Sheng Tang (Food Chemistry, 2023)

A scalable framework for quantifying field-level agricultural carbon outcomes - Kaiyu Guan; Zhenong Jin; Bin Peng; Jinyun Tang; Evan H. DeLucia; Paul C. West; Chongya Jiang; Sheng Wang; Taegon Kim; Wang Zhou; Tim Griffis; Licheng Liu; et al. (Earth-Science Reviews, 2023)

Silicon carbide coated carbon nanotube porous sponge with super Elasticity, low Density, high thermal Resistivity, and synergistically enhanced electromagnetic interference shielding performances - Chengqing Tang; Sheng Zhang; Jiapeng Zhang; Xiaohua Zhang; Zhihong Hang; Yitan Li; Zhaohui Yang (Chemical Engineering Journal, 2023)

Insights into the interfacial structure of Cu/ZrO2 catalysts for methanol synthesis from CO2 hydrogenation: Effects of Cu-supported nano-ZrO2 inverse interface - Yangzhi Xu; Maolin Wang; Zhiwei Xie; Dong Tian; Guan Sheng; Xin Tang; Haibo Li; Yichao Wu; Chuqiao Song; Xiaofeng Gao; Siyu Yao; Ding Ma; et al. (Chemical Engineering Journal, 2023)

Recent advances in micro (nano) plastics in the environment: Distribution, health risks, challenges and future prospects - Yan-Bo Ma; Zhuo-Yuan Xie; Naima Hamid; Qi-Ping Tang; Jiao-Yun Deng; Lin Luo; De-Sheng Pei (Aquatic Toxicology, 2023)

Mechanistic investigation of the differential synergistic neurotoxicity between pesticide metam sodium and copper or zinc - Chen Shen; Zhi-Guo Sheng; Jie Shao; Miao Tang; Li Mao; Chun-Hua Huang; Zhi-Hui Zhang; Ben-Zhan Zhu (Chemosphere, 2023)

Nitrogen removal from low-C/N-ratio wastewater using a three-dimensional bioelectrical reactor - Chunhong Jin; Qi Tang; Yanbo Gao; Hengdu Xu; Lei Zhang; Yanqing Sheng (Journal of Water Process Engineering, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

Association between short-term exposure to ambient air pollution and outpatient visits for pulpitis in Hefei, China: a time series study - Wuli Li; Xirun Zong; Yi-Sheng He; Tiantian Meng; Ying Tang; Qi Yang; Qing Huang; Yuanyin Wang; Song Li; Hai-Feng Pan (Environmental Science and Pollution Research, 2023)

Enhancing lead immobilization by biochar: Creation of “surface barrier” via bio-treatment - Huicong Hu; Chao-Sheng Tang; Zhengtao Shen; Xiaohua Pan; Kai Gu; Xiaoliang Fan; Chao Lv; Wen Mu; Bin Shi (Chemosphere, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Strategies of stakeholders’ selection of shore-to-ship power in China - Jinlu Sheng; Liu Tang; Zhongzhen Yang; Min Yu; Xingchen Liu (Transportation Research Part D: Transport and Environment, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Role of macrophage AHR/TLR4/STAT3 signaling axis in the colitis induced by non-canonical AHR ligand aflatoxin B1 - Liwen Zhang; Dong Cheng; Jing Zhang; Hui Tang; Fenghua Li; Yi Peng; Xinglan Duan; En Meng; Cuili Zhang; Tao Zeng; Fuyong Song; Jia-Sheng Wang; et al. (Journal of Hazardous Materials, 2023)

Geochemical controls on the distribution and bioavailability of heavy metals in sediments from Yangtze River to the East China Sea: Assessed by sequential extraction versus diffusive gradients in thin-films (DGT) technique - Yuhao Liang; Rui Wang; G. Daniel Sheng; Linhong Pan; Ergang Lian; Ni Su; Xiliang Tang; Shouye Yang; Daqiang Yin (Journal of Hazardous Materials, 2023)

Constructing functional thermal-insulation-layer on Co3O4 nanosphere for reinforced local-microenvironment photothermal PMS activation in pollutant degradation - Mengting Liu; Hongyang Zhu; Rongrong Du; Wuxiang Zhang; Weilong Shi; Zengjing Guo; Sheng Tang; Edison Huixiang Ang; Jun Yang; Jianming Pan; Fu Yang (Journal of Environmental Chemical Engineering, 2023)

Host-microbiota affects the toxicity of Aflatoxin B1 in Caenorhabditis elegans - Bowen Tang; Kathy S. Xue; Jia-Sheng Wang; Phillip L. Williams; Lili Tang (Food and Chemical Toxicology, 2023)

All-ceramic array patch for 5G signal enhancement based on B-site substituted zinc-cobalt molybdate low temperature co-fired ceramics - Fuyu Li; Yuanxun Li; Sheng Li; Yang Luo; Yongcheng Lu; Tingting Tang; Yulong Liao; Jinping Zhang; Qiye Wen (Chemical Engineering Journal, 2023)

Synergistic effect of high-valent cobalt oxo species and piezoelectricity on enhanced peroxymonosulfate activation for atrazine removal - Sheng Xiong; Hao Zeng; Rongdi Tang; Ling Li; Zhanpeng Zhou; Jiajia Wang; Chunxia Ding; Daoxin Gong; Yaocheng Deng (Chemical Engineering Journal, 2023)

Insights into the long-term stability of landslide dams on the eastern margin of the Tibetan Plateau, China–A case study of the Diexi area - Liang Song; Yun-sheng Wang; Dong-yu Hu; Hao-chen Wu; Tao Tang; Shi-cheng Liu (Journal of Mountain Science, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Dissection of pyroptosis-related prognostic signature and CASP6-mediated regulation in pancreatic adenocarcinoma: new sights to clinical decision-making - Jun Zhu; Yanlong Shi; Sheng Lan; Jingyan Wang; Fei Jiang; Caiping Tang; Yuan Cai; Ziyuan Pan; Haokun Jian; Hanlu Fang; Yewei Zhang; Fei Zhong (Apoptosis, 2023)
Recent studies have indicated that pyroptosis may participate in the regulation of tumorigenesis and immune microenvironment. However, the role of pyroptosis-related genes (PRGs) in pancreatic adenocarcinoma (PAAD) remains unclear. Through multiple bioinformatics analysis, we constructed a prognostic gene model and competing endogenous RNA network. The correlation between PRGs and prognosis, immune infiltration, immune checkpoints, and tumor mutational burden was analyzed by Kaplan–Meier curve, univariate Cox, multivariate regression, and Spearman’s analysis in PAAD patients. The qRT-PCR, Western blotting, CCK-8, Wound healing, and Transwell assay were applied to examine the role of CASP6 in PANC-1 cell. Thirty-one PRGs were upregulated in PAAD. Functional enrichment analysis revealed that the PRGs were mainly involved in pyroptosis, NOD-like receptor signaling pathway, and response to bacteria. We established a novel 4-gene signature related to PRGs for evaluating the prognosis of PAAD patients. Patients with PAAD in the low-risk group had a better prognosis than those in the high-risk group. The nomogram suggested that the 1-, 3-, and 5-years survival probability exhibited robust predictive performance. Significant correlation was observed between prognostic PRGs and immune infiltration, immune checkpoints, and tumor mutational burden. We first identified the potential competing endogenous RNA regulatory axis in PAAD: lncRNA PVT1/hsa-miR-16-5p/CASP6/CASP8. Moreover, knockdown of CASP6 dramatically inhibited the proliferation, migration, and invasion ability of PANC-1 cell in vitro. In conclusion, CASP6 could be a potential biomarker, promoting the occurrence and progression in PAAD. The lncRNA PVT1/hsa-miR-16-5p/CASP6/CASP8 regulatory axis plays an vital role in regulating the anti-tumor immune responses for PAAD.

Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. - Pan Yi; Bin Li; Salman Zafar; Sajjad Ali; Wen-Bing Sheng; Yu Mao; Fang Zhou; Wen-Ming Chen; Yan-Ran Tang; Cai-Yun Peng; M. Iqbal Choudhary; Atta-ur- Rahman; et al. (Natural Product Research, 2023)

Adaptation of the infectious bronchitis virus H120 vaccine strain to Vero cell lines - Yi Jiang; Mei Xue; Mengjun Tang; Di Zhang; Yan Yu; Sheng Zhou (Veterinary Microbiology, 2023)

Microbial community succession in soil is mainly driven by carbon and nitrogen contents rather than phosphorus and sulphur contents - Sheng Tang; Qingxu Ma; Karina A. Marsden; David R. Chadwick; Yu Luo; Yakov Kuzyakov; Lianghuan Wu; Davey L. Jones (Soil Biology and Biochemistry, 2023)

Bearing capacity reliability analysis using the coupled FEM-BPNN-RSM for monopile-supported OWTs - Suxi Tang; Jinjin Zhai; Qilin Yin; Wei Wang; Sheng Xu (Ocean Engineering, 2023)

Phycobiliproteins from algae: Current updates in sustainable production and applications in food and health - Liang Ji; Sheng Qiu; Zhiheng Wang; Chenni Zhao; Bo Tang; Zhengquan Gao; Jianhua Fan (Food Research International, 2023)

Determination of dry soil layer and its soil heat flux distribution using actively heated distributed temperature sensing - Meng-Ya Sun; Bin Shi; Yu-Jun Cui; Chao-Sheng Tang; Xing Zheng; Jin Liu; Zi Ying; Yi-Jie Sun; Yun-Qiang Wang; Jing-Xiong Zhou (Engineering Geology, 2023)

Coupling effect of fiber reinforcement and MICP stabilization on the tensile behavior of calcareous sand - Dian-Long Wang; Chao-Sheng Tang; Xiao-Hua Pan; Bo Liu; Bin Shi (Engineering Geology, 2023)

Utilisation and transformation of organic and inorganic nitrogen by soil microorganisms and its regulation by excessive carbon and nitrogen availability - Wankun Pan; Jingjie Zhou; Sheng Tang; Lianghuan Wu; Qingxu Ma; Karina A. Marsden; David R. Chadwick; Davey L. Jones (Biology and Fertility of Soils, 2023)

Peridinin-chlorophyll-protein complex industry from algae: A critical review of the current advancements, hurdles, and biotechnological potential - Sheng Qiu; Yuchen Yuan; Xiaoyi Li; Chenni Zhao; Yulong He; Bo Tang; Wenda Wang; Jianhua Fan (Algal Research, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

Amycolatolides A and B: Two new secondary metabolites from the lichen-derived actinomycete Amycolatopsis sp. YIM 130923 - Qing-Rong Yang; Yi Jiang; Chuan-Sheng Liu; Tang-Chang Xu; Rong Huang; Shao-Hua Wu (Phytochemistry Letters, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Translatomics and physiological analyses of the detoxification mechanism of green alga Chlamydomonas reinhardtii to cadmium toxicity - Baolong Zhang; Yuxin Tang; Fei Yu; Zhao Peng; Sheng Yao; Xuan Deng; Huan Long; Xun Wang; Kaiyao Huang (Journal of Hazardous Materials, 2023)

Aflatoxin B1 damaged structural barrier through Keap1a/Nrf2/ MLCK signaling pathways and immune barrier through NF-κB/ TOR signaling pathways in gill of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Zhen-Zhen Zeng; Lin Feng; Pei Wu; Wei-Dan Jiang; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Three Days Delayed Recanalization Improved Neurological Function in pMCAO Rats by Increasing M2 Microglia—Possible Involvement of the IL-4R/STAT6/PPARγ Pathway - Ruiqing Kang; Marcin Gamdzyk; Yujie Luo; Hong Tang; Lei Huang; Cameron Lenahan; Desislava Doycheva; Dujuan Li; Jiping Tang; Sheng Tan; John H. Zhang (Translational Stroke Research, 2023)

Identification of the CCL2 PI3K/Akt axis involved in autophagy and apoptosis after spinal cord injury - Sheng Fang; Hao Tang; Ming-Zhi Li; Jian-Jun Chu; Zong-Sheng Yin; Qi-Yu Jia (Metabolic Brain Disease, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Use of untargeted metabolomics to analyse changes in extractable soil organic matter in response to long-term fertilisation - Sheng Tang; Qingxu Ma; Jingjie Zhou; Wankun Pan; David R. Chadwick; Andrew S. Gregory; Lianghuan Wu; Davey L. Jones (Biology and Fertility of Soils, 2023)

Single-cell transcriptome uncovers heterogeneity and immune responses of leukocytes after vaccination with inactivated Edwardsiella tarda in flounder (Paralichthys olivaceus) - Hongfei Tian; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2023)

Immune and protective effects of subunit vaccines from S-domain or P-domain in capsid protein against nervous necrosis virus in pearl gentian grouper - Tianwen Lin; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Thermomechanically micronized sugar beet pulp: Emulsification performance and the contribution of soluble elements and insoluble fibrous particles - Jiawei Lin; Zhong-Sheng Tang; Charles S. Brennan; Jayani Chandrapala; Wenhong Gao; Zhong Han; Xin-An Zeng (Food Research International, 2023)

Effects of different extraction methods on the structural, antioxidant and hypoglycemic properties of red pitaya stem polysaccharide - Yayuan Tang; Xuemei He; Guoming Liu; Zhen Wei; Jinfeng Sheng; Jian Sun; Changbao Li; Ming Xin; Li Li; Ping Yi (Food Chemistry, 2023)

Full-length transcriptome sequencing of lymphocytes respond to IFN-γ reveals a Th1-skewed immune response in flounder (Paralichthys olivaceus) - Ziyang He; Hongfei Tian; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2023)

MoS2 supported on acid activated kaolinite used in the kaolinite-epoxy resin composites for suppressing smoke toxicity and degradation - Wufei Tang; Haizhou Fan; Fang Liu; Yunhui Liao; Qi Xiao; Jiao Yan; Sheng Zhang; Xiaoyu Gu (Applied Clay Science, 2023)

Acanthopagrus latus migration patterns and habitat use in Wanshan Islands, Pearl River Estuary, determined using otolith microchemical analysis - Guanglong Tang; Zehua He; Yong Liu; Yayuan Xiao; Sheng Bi; Ye Sun; Jiman Liang; Peng Wu; Teng Wang; Jinyu Ye; Chunhou Li (Frontiers in Marine Science, 2023)
Introduction The waters surrounding the Wanshan Islands are important traditional fishing grounds in China, with rich habitat types. Acanthopagrus latus is an economically important species in this area; however, the distribution of its spawning grounds and habitat use patterns remain unknown. Methods Thus 100 otolith samples of A. latus were collected from three geographic areas (MW: Qi’ao Island Mangrove Water Habitat; OW: Yamen Estuary Oyster Farm Water Habitat; RW: Dong’ao-Guishan Island Reef Water Habitat), and the concentrations of Sr and Ca along the shortest axis of the vertical otolith annual or lunar rings were measured to span the entire life cycle of A. latus , with the core and edge areas corresponding to environmental characteristics at birth and capture, respectively. Results and discussion Analysis of covariance (ANCOVA) revealed that the ratios of Sr/Ca in otolith edges of RW samples are significantly higher than those of OW and MW samples; however, both the values of Sr/Ca ratio in otolith cores collected from OW and MW are comparable with those of RW samples. Cluster analysis and non-metric multidimensional scaling (nMDS) indicated that at the juvenile stage, RW and MW individuals in the two main clusters belonged to the same cluster. There was no significant difference between the cores of the RW samples and the edges of the MW and OW samples. Therefore, the spawning area of A. latus in the Wanshan Islands is thought to have originated from low to medium-salinity waters with mangroves and oyster farm habitats in the Pearl River Estuary. A. latus from RW was found to have three distinct habitat-use patterns: 1) Marine Resident (7.2% of sampled fish) fish that remain in marine habitats for life; 2) Marine Migrant (16.4% of sampled fish) juveniles inhabit low to moderate salinity habitats and migrate to marine habitats as they grow; 3) Estuarine Visitor (76.4% of sampled fish) repeated migration between low to moderate salinity and marine habitats. This suggests widespread migration between estuarine and marine habitats throughout the ontogeny. The plasticity of this habitat use and the protection of spawning grounds should be considered in future fisheries management because A. Latus in this area has been the victim of the overexploitation of resources.

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

RETRACTED: Analysis and study of the migration pattern of microplastic particles in saturated porous media pavement - Sheng Liu; Jiayan Wu; Leiye Sun; Minye Huang; Xiaoshan Qiu; Hongmei Tang; Jieyu Liu; Pingxiao Wu (Science of The Total Environment, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Rapid screening of antioxidant from natural products by AAPH-Incubating HPLC-DAD-HR MS/MS method: A case study of Gardenia jasminoides fruit - Guo-Dong Zhuang; Wen-Ting Gu; Shu-Hong Xu; Dong-Min Cao; Si-Min Deng; Yong-Sheng Chen; Shu-Mei Wang; Dan Tang (Food Chemistry, 2023)

Elucidation of the cellulose nanocrystal-sugar beet pectin interactions for emulsification enhancement - Jiawei Lin; Zhong-Sheng Tang; Jayani Chandrapala; Charles Stephen Brennan; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2023)

Matrix metalloproteinase 9 modulates immune response along with the formation of extracellular traps in flounder (Paralichthys olivaceus) - Heng Chi; Zhixiao Dong; Qiujie Gan; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Wenbin Zhan (Fish & Shellfish Immunology, 2023)

Estimating the CO2 emissions of Chinese cities from 2011 to 2020 based on SPNN-GNNWR - Lizhi Miao; Sheng Tang; Xinting Li; Dingyu Yu; Yamei Deng; Tian Hang; Haozhou Yang; Yunxuan Liang; Mei-Po Kwan; Lei Huang (Environmental Research, 2023)

Healing behaviour of desiccation cracks in a clayey soil subjected to different wetting rates - Ben-Gang Tian; Qing Cheng; Chao-Sheng Tang; Bin Shi (Engineering Geology, 2023)

Graphite intercalation compounds (GICs) based multi-functional interface layer toward highly reversible Zn metal anodes - Shunzhang You; Dao-Sheng Liu; Minghui Ye; Yufei Zhang; Yongchao Tang; Xiaoqing Liu; Cheng Chao Li (Chemical Engineering Journal, 2023)

Green supply chain management for a more sustainable manufacturing industry in China: a critical review - Xuerou Sheng; Leping Chen; Xueliang Yuan; Yuzhou Tang; Qian Yuan; Rong Chen; Qingsong Wang; Qiao Ma; Jian Zuo; Hongwei Liu (Environment, Development and Sustainability, 2023)

Portal vein tumor thrombosis in hepatocellular carcinoma: molecular mechanism and therapy - Xing-Hao Zhou; Jing-Ru Li; Tang-Hui Zheng; Hong Chen; Chen Cai; Sheng-Long Ye; Bo Gao; Tong-Chun Xue (Clinical & Experimental Metastasis, 2023)

Distribution fractions and potential ecological risk assessment of heavy metals in mangrove sediments of the Greater Bay Area - Huan-Zhan Zhou; Jun-Feng Wang; Hui-Min Jiang; Ze-Xiang Cai; Guan-Hui Tang; Song Ding; Sheng-Teng Liu; Zhi-Min Xu (Environmental Science and Pollution Research, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Metagenomics reveals N-induced changes in carbon-degrading genes and microbial communities of tea (Camellia sinensis L.) plantation soil under long-term fertilization - Xiangde Yang; Kang Ni; Yuanzhi Shi; Xiaoyun Yi; Lingfei Ji; Sirou Wei; Yanyan Jiang; Yongli Zhang; Yanjiang Cai; Qingxu Ma; Sheng Tang; Lifeng Ma; et al. (Science of The Total Environment, 2023)

Sources, transport, and visibility impact of ambient submicrometer particle number size distributions in an urban area of central Taiwan - Li-Hao Young; Chih-Sheng Hsu; Ta-Chih Hsiao; Neng-Huei Lin; Si-Chee Tsay; Tang-Huang Lin; Wen-Yinn Lin; Chau-Ren Jung (Science of The Total Environment, 2023)

Nontargeted metabolomic analysis of four different parts of Actinidia arguta by UPLC-Q-TOF-MSE - Yu-fei Hou; Lu Bai; Sen Guo; Jia-bing Hu; Shan-shan Zhang; Shao-jing Liu; Ying Zhang; Shiming Li; Chi-Tang Ho; Nai-sheng Bai (Food Research International, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Genome characterization of Hirame novirhabdovirus (HIRRV) isolate CNPo2015 and transcriptome analysis of Hirame natural embryo (HINAE) cells infected with CNPo2015 - Fenghuang Pan; Xinbiao Ma; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Fish & Shellfish Immunology, 2023)

Long-term nitrogen addition increases denitrification potential and functional gene abundance and changes denitrifying communities in acidic tea plantation soil - Xiangde Yang; Sheng Tang; Kang Ni; Yuanzhi Shi; Xiaoyun Yi; Qingxu Ma; Yanjiang Cai; Lifeng Ma; Jianyun Ruan (Environmental Research, 2023)

Improving tea (Camellia sinensis) quality, economic income, and environmental benefits by optimizing agronomic nitrogen efficiency: A synergistic strategy - Sheng Tang; Haoran Fu; Wankun Pan; Jingjie Zhou; Meng Xu; Kefeng Han; Kaijun Chen; Qingxu Ma; Lianghuan Wu (European Journal of Agronomy, 2023)

Nonoxidative propane dehydrogenation by isolated Co2+ in BEA zeolite: Dealumination-determined key steps of propane C H activation and propylene desorption - Sheng Wei; Hua Dai; Jiangping Long; Hongqiao Lin; Junkun Gu; Xupeng Zong; Dan Yang; Yu Tang; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Thin-walled vesicular Triazole-CN-PDI with electronic n→π* excitation and directional movement for enhanced atrazine photodegradation - Rongdi Tang; Hao Zeng; Daoxin Gong; Yaocheng Deng; Sheng Xiong; Ling Li; Zhanpeng Zhou; Jiajia Wang; Chengyang Feng; Lin Tang (Chemical Engineering Journal, 2023)

Insights into the dual Z-scheme and piezoelectricity co-driven photocatalyst for ultra-speed degradation of nitenpyram - Sheng Xiong; Hao Zeng; Yaocheng Deng; Chengyang Feng; Rongdi Tang; Zhanpeng Zhou; Ling Li; Jiajia Wang; Daoxin Gong (Chemical Engineering Journal, 2023)

Key technology for the construction and inspection of long-distance underwater tunnel for 1000 kV gas-insulated transmission line - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Hao-Jie Wang; Xin-Fang Li; Peng Chen; Hao Liu (Bulletin of Engineering Geology and the Environment, 2023)

Effects of combined application of nitrogen, phosphorus, and potassium fertilizers on tea (Camellia sinensis) growth and fungal community - Sheng Tang; Jingjie Zhou; Wankun Pan; Tao Sun; Mengjiao Liu; Rui Tang; Zijing Li; Qingxu Ma; Lianghuan Wu (Applied Soil Ecology, 2023)

Light-enhanced transparent hydrogel for uric acid and glucose detection by four different analytical platforms - Wei Mao; Xingwei Cai; Ruirong Pan; Sheng Tang; Fu Yang; Yanjuan Cui; Jun Sun; Wei Shen (Analytica Chimica Acta, 2023)

Characterization, expression patterns and functional analysis of PcMPK12 gene in Phytophthora capsici - Tong-tong Zhu; Sheng-han Xiang; Lei Yang; Fang Tang; Wei Li; Ying-bao Liu; Wen-xiu Sun (European Journal of Plant Pathology, 2022)

Local application of triamcinolone acetonide-conjugated chitosan membrane to prevent benign biliary stricture - Tao Wang; Shibo Zhang; Lianmin Wang; Kun Su; Zhiyi Tang; Haiyu He; Yanmei Shi; Yaqiong Liu; Mengyao Zheng; Wen Fu; Sheng Hu; Xiaowen Zhang; et al. (Drug Delivery and Translational Research, 2022)

Exploring complex urban growth and land use efficiency in China’s developed regions: implications for territorial spatial planning - Xiaolu Tang; Li Sheng; Yinkang Zhou (Frontiers of Earth Science, 2022)

Plants can access limited amounts of nitrogen- and sulphur-containing amino acids in soil owing to rapid microbial decomposition - Qingxu Ma; Wankun Pan; Sheng Tang; David R. Chadwick; Lianghuan Wu; Davey L. Jones (Plant and Soil, 2022)

PPCPs and heavy metals from hydrothermal sewage sludge-derived biochar: migration in wheat and physiological response - Kai Zhen; Qing Zhu; Sheng Zhai; Yue Gao; Huimin Cao; Xuejiao Tang; Cuiping Wang; Jiao Li; Lili Tian; Hongwen Sun (Environmental Science and Pollution Research, 2022)

A new tigliane-type diterpenoid from Euphorbia tirucalli - Han-Zhuang Weng; Yang Tian; Jun-Sheng Zhang; Jia-Luo Huang; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2022)

Bifunctional Ni@NiO catalyst supported on loofah sponge-derived carbon for electrocatalytic air oxidation of biorefractory pollutant in a coupling system - Min Sun; Xiong-Fei Tao; Sheng-Nan Tang; Jun Yu; Yan Wang; Lin-Feng Zhai (Environmental Science and Pollution Research, 2022)

Actinomycin D: a novel Pseudomonas aeruginosa quorum sensing inhibitor from the endophyte Streptomyces cyaneochromogenes RC1 - Yue-Xiang Zeng; Jun-Sheng Liu; Ying-Jie Wang; Shi Tang; Da-Yong Wang; Shi-Ming Deng; Ai-Qun Jia (World Journal of Microbiology and Biotechnology, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Comparison of 16S rRNA Gene Primers on Studying Microbial Community Composition in Bottom Water and Sediment of Artificial Reefs in Laoshan Bay, China - Guangjie Fang; Haolin Yu; Huaxiang Sheng; Yanli Tang; Zhenlin Liang (Journal of Ocean University of China, 2022)

An Experimental and Modeling Investigation on Creep Mechanical Behavior of Granite Under Triaxial Cyclic Loading and Unloading - Sheng-Qi Yang; Jin-Zhou Tang; Su-Sheng Wang; Dian-Sen Yang; Wen-Tang Zheng (Rock Mechanics and Rock Engineering, 2022)

Cluster of differentiation antigens: essential roles in the identification of teleost fish T lymphocytes - Hong-fei Tian; Jing Xing; Xiao-qian Tang; Heng Chi; Xiu-zhen Sheng; Wen-bin Zhan (Marine Life Science & Technology, 2022)
Cluster of differentiation (CD) antigens are cell surface molecules expressed on leukocytes and other cells associated with the immune system. Antibodies that react with CD antigens are known to be one of the most essential tools for identifying leukocyte subpopulations. T lymphocytes, as an important population of leukocytes, play essential roles in the adaptive immune system. Many of the CD antigens expressed on T lymphocytes are used as surface markers for T lymphocyte classification, including CD3, CD4 and CD8 molecules. In this review, we summarize the recent advances in the identification of CD molecules on T lymphocytes in teleosts, with emphasis on the functions of CD markers in the classification of T lymphocyte subsets. We notice that genes encoding CD3, co-receptors CD4 and CD8 have been cloned in several fish species and antibodies have been developed to study protein expression in morphological and functional contexts. T lymphocytes can be divided into CD4 + and CD8 + cells discriminated by the expression of CD4 and CD8 molecules in teleost, which are functionally similar to mammalian helper T cells (Th) and cytotoxic T cells (Tc), respectively. Further studies are still needed on the particular characteristics of teleost T cell repertoires and adaptive responses, and results will facilitate the health management and development of vaccines for fish.

Silicon isotope fractionation dynamics during uptake and translocation by various crop species under three soil types - Jingjie Zhou; Sheng Tang; Wankun Pan; Han Xiao; Qingxu Ma; Yan Sun; Meng Xu; Mengjiao Liu; Lianghuan Wu (Plant and Soil, 2022)

Exposure to phthalates in early pregnancy and the risk of fetal growth restriction: a nested case–control study in a Zhuang Chinese population - Xiaojing Guo; Yonghong Sheng; Bihu Liu; Peng Tang; Runfeng Liu; Li Wu; Jiehua Chen; Dongping Huang; Shun Liu; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2022)

Effects of the individual rearing stage on the growth traits of candidate giant freshwater prawns (Macrobrachium rosenbergii) - Juan Sui; Sheng Luan; Guoliang Yang; Zhenglong Xia; Qiongying Tang; Kun Luo; Xianhong Meng; Jie Kong (Aquaculture International, 2022)

Impact of summer moratorium on set-net fishery in Haizhou Bay, China - Guangjie Fang; Haolin Yu; Xinmeng Wang; Huaxiang Sheng; Yanli Tang; Changdong Liu; Chuanxi Chen; Zhenlin Liang (Journal of Oceanology and Limnology, 2022)

Modification-Free Fluorescent Biosensor for CEA Based on Polydopamine-Coated Upconversion Nanoparticles - Dezhong Yu; Zhonghui Zha; Sheng Tang; Yuan Qiu; Dong Liu (Journal of Fluorescence, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Plant–microbial competition for amino acids depends on soil acidity and the microbial community - Wankun Pan; Sheng Tang; Jingjie Zhou; Mengjiao Liu; Meng Xu; Yakov Kuzyakov; Qingxu Ma; Lianghuan Wu (Plant and Soil, 2022)

Impact of N application rate on tea (Camellia sinensis) growth and soil bacterial and fungi communities - Sheng Tang; Jingjie Zhou; Wankun Pan; Rui Tang; Qingxu Ma; Meng Xu; Tong Qi; Zhengbo Ma; Haoran Fu; Lianghuan Wu (Plant and Soil, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Coupling effect of biocementation-fiber reinforcement on mechanical behavior of calcareous sand for ocean engineering - Chao-Sheng Tang; Hao Li; Xiao-Hua Pan; Li-Yang Yin; Liang Cheng; Qing Cheng; Bo Liu; Bin Shi (Bulletin of Engineering Geology and the Environment, 2022)

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Investigation on desiccation cracking behavior of clayey soils with a perspective of fracture mechanics: a review - Jin-Jian Xu; Chao-Sheng Tang; Qing Cheng; Qi-liang Xu; Hilary I. Inyang; Zhu-Yuan Lin; Bin Shi (Journal of Soils and Sediments, 2022)

Two bicistronic DNA vaccines against Vibrio anguillarum and the immune effects on flounder Paralichthys olivaceus - Hanlin Li; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Oceanology and Limnology, 2022)

Assessment of genetic diversity among Chinese high-oleic peanut genotypes using miniature inverted-repeat transposable element markers - Chuan Tang Wang; Guo Sheng Song; Zhi Wei Wang; Hong Ju Li; Hong Wei Han; Xiao Yuan Chi; Xiu Zhen Wang; Xiu Shan Sun (Genetic Resources and Crop Evolution, 2022)

Morphological description of desiccation cracks in soils: insights from the perspective of anisotropy - Bei-Bing Dai; Jun Yang; Feng-Tao Liu; Chao-Sheng Tang; Tian-Qi Li (Bulletin of Engineering Geology and the Environment, 2022)

Effect of confining pressure on mechanics and deformation behavior of sandstone containing a single inclined joint - Jin-Zhou Tang; Sheng-Qi Yang; Wen-Ling Tian; Yan Tao (European Journal of Environmental and Civil Engineering, 2022)

Short-form OPA1 is a molecular chaperone in mitochondrial intermembrane space - Deyang Yao; Yukun Li; Sheng Zeng; Zhifan Li; Zahir Shah; Bigui Song; Jinglei Liu; Yi Wu; Liang Yang; Qi Long; Wenqian Wang; Zhijuan Hu; et al. (Science China Life Sciences, 2022)

Euphopanes A–C, three new diterpenoids from Euphorbia pekinensis - Xue-Long Yan; Jia-Luo Huang; Ya-Qi Tang; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Development and application of rose (Rosa chinensis Jacq.) SNP markers based on SLAF-seq technology - Ao-Nan Xia; Ao-Ao Yang; Xian-Shui Meng; Gui-Zhi Dong; Xiao-Juan Tang; Sheng-Ming Lei; Yun-Guo Liu (Genetic Resources and Crop Evolution, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Anti-inflammatory Dendranacetylene A, a new polyacetylene glucoside from the flower of Chrysanthemum morifolium Ramat - Meng Li; Mengnan Zeng; Jingke Zhang; Jingya Shi; Jinjin Lv; Yingying Tang; Xiao-ke Zheng; Wei-sheng Feng (Natural Product Research, 2021)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Euphanoids A and B, two new lathyrane diterpenoids with nitric oxide (NO) inhibitory activity from Euphorbia kansuensis - Xue-Long Yan; Run-Zhu Fan; Jun Sang; Xing-Lin Xie; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

New types of ATP ‐grasp ligase are associated with the novel pathway for complicated mycosporine‐like amino acid production in desiccation‐tolerant cyanobacteria - Zhong‐Chun Zhang; Kai Wang; Fu‐Hua Hao; Jin‐Long Shang; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Mycosporine‐like amino acids (MAAs) were widespread in diverse organisms to attenuate UV radiation. We recently characterized the large, complicated MAA mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) in desert cyanobacterium Nostoc flagelliforme . Synthesis of this MAA requires the five‐gene cluster mysABDC2C3 . Here, bioinformatic analysis indicated that mysC duplication within five‐gene mys clusters is strictly limited to drought‐tolerant cyanobacteria. Phylogenic analysis distinguished these duplicated MysCs into two clades that separated from canonical MysCs. Heterologous expression of N. flagelliforme mys genes in Escherichia coli showed that MysAB produces 4‐deoxygadusol. The ATP‐grasp ligase of MysC3 catalyses the linkage of the δ‐ or ε‐amino group of ornithine/lysine to 4‐deoxygadusol, yielding mycosporine‐ornithine or mycosporine‐lysine respectively. The ATP‐grasp ligase of MysC2 strictly condenses the α‐amino group of mycosporine‐ornithine to another 4‐deoxygadusol. MysD (D‐Ala–D‐Ala ligase) functions following MysC2 to catalyse the formation of mycosporine‐2‐(4‐deoxygadusolyl‐ornithine). High arginine content likely provides a greater pool of ornithine over other amino acids during rehydration of desiccated N. flagelliforme . Duplication of ATP‐grasp ligases is specific for the use of substrates that have two amino groups (such as ornithine) for the production of complicated MAAs with multiple chromophores. This five‐enzyme biosynthesis pathway for complicated MAAs is a novel adaptation of cyanobacteria for UV tolerance in drought environments.

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

The inhibitory effects of the antifouling compound Irgarol 1051 on the marine diatom Skeletonema sp. across a broad range of photosynthetically active radiation - Yao Tang; Cheng Chen; Yangjie Sheng; Peijian Ding; Xinyu Wu; John Beardall; Yaping Wu (Environmental Science and Pollution Research, 2021)

An experimental study on cutting tool hardness optimization for shield TBMs during dense fine silty sand ground tunneling - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Xin-Bin Tu; Peng Chen; Fang-Yi Li (Bulletin of Engineering Geology and the Environment, 2021)

Application of the modified cytosine base-editing in the cultured cells of bama minipig - Jia-sheng Pan; Zi-sheng Lin; Jian-cong Wen; Jian-feng Guo; Xia-hui Wu; Ying-ying Liu; Wen-jun Lai; Qi-ying Liang; Yong-shi Xie; Yi-rou Chen; Yi-hong Chen; Ai-fen Yan; et al. (Biotechnology Letters, 2021)

Improvement on the Effectiveness of Marine Stock Enhancement in the Artificial Reef Area by a New Cage-Based Release Technique - Junbo Zhang; Yufeng He; Zhixing Guo; Shuheng Ji; Shuo Zhang; Yanli Tang; Huaxiang Sheng; Rong Wan; Daisuke Kitazawa (Journal of Ocean University of China, 2021)

Seismic signal characteristics and interpretation of the 2020 “6.17” Danba landslide dam failure hazard chain process - Yan Yan; Yifei Cui; Dingzhu Liu; Hui Tang; Yongjian Li; Xin Tian; Lei Zhang; Sheng Hu (Landslides, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Fluvastatin attenuated ischemia/reperfusion-induced autophagy and apoptosis in cardiomyocytes through down-regulation HMGB1/TLR4 signaling pathway - Hua-Sheng Ding; Jun Yang; Jian Yang; Xin Guo; Yan-Hong Tang; Yan Huang; Zhen Chen; Zhi-Xing Fan; Cong-Xin Huang (Molecular Biology Reports, 2021)

A Functional Polymorphism in HIF-3α Is Related to an Increased Risk of Ischemic Stroke - Xi-Xi Gu; Zhuan-Zhi Tang; Yong-Ling He; Zhi-Neng Zeng; Wu-Xiang Shi; Yong-Chao Qiao; Ye-Sheng Wei (Journal of Molecular Neuroscience, 2021)
Hypoxia-inducible factor-3α ( HIF-3α ), a member of HIF family, can mediate adaptive responses to low oxygen and ischemia. It is believed that HIF plays crucial roles in stroke-related diseases. However, there are no reports on the association between HIF-3α genetic variants and ischemic stroke (IS) susceptibility. Therefore, we examined the association between HIF- 3α gene polymorphisms (rs3826795, rs2235095, and rs3764609) and IS risk. The study population included 302 controls and 310 patients with ischemic stroke. Three polymorphisms in HIF- 3α (rs3826795, rs2235095, and rs3764609) were genotyped using SNPscan technique. Our study showed a strong association of rs3826795 in HIF-3α with the risk of IS. The genotype and allele frequencies were shown to differ between the two groups. The rs3826795 in an intron of HIF-3α was related to a prominent increased IS risk (AA vs GG adjusted odd ratio [OR], 2.21; 95% confidence intervals [95% CI], 1.10–4.44; P = 0.03; AA vs AG/GG OR = 1.74, 95% CI, 1.02–2.97, P = 0.04; A vs G OR = 1.48, 95% CI, 1.05–2.07, P = 0.02). Logistic regression analysis suggested that rs3826795 posed a risk factor for IS in addition to common factors. Furthermore, when compared to controls, increased levels of homocysteic acid and level of non-esterified fatty acid were found in the cases ( P < 0.01). However, no significant association was found between rs2235095 or rs3264609 and IS risk. These findings indicated that the rs3826795 polymorphism may be a potential target for predicting the risk of IS.

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Effects of Selenium on Arsenic-Induced Liver Lesions in Broilers - Zhihua Ren; Huidan Deng; Youtian Deng; Wenjiao Tang; Qiang Wu; Zhicai Zuo; Hengmin Cui; Yanchun Hu; Shumin Yu; Sheng-yu Xu; Junliang Deng (Biological Trace Element Research, 2021)

Three-Dimensional Numerical Modeling of Grain-Scale Mechanical Behavior of Sandstone Containing an Inclined Rough Joint - Jin-Zhou Tang; Sheng-Qi Yang; Derek Elsworth; Yan Tao (Rock Mechanics and Rock Engineering, 2021)

Identifying Accurate Crack Initiation and Propagation Thresholds in Siliceous Siltstone and Limestone - Xiao-Ping Zhang; Gen-Gen Lv; Quan-Sheng Liu; Shun-Chuan Wu; Qi Zhang; Pei-Qi Ji; Xu-Hai Tang (Rock Mechanics and Rock Engineering, 2021)

Ferroptosis occurs in phase of reperfusion but not ischemia in rat heart following ischemia or ischemia/reperfusion - Li-Jing Tang; Xiu-Ju Luo; Hua Tu; Heng Chen; Xiao-Ming Xiong; Nian-Sheng Li; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Conserving the Chinese caterpillar fungus under climate change - Yi Li; Yujing Yan; Zhiyao Tang; Ke Wang; Jin-Sheng He; Yi-Jian Yao (Biodiversity and Conservation, 2021)

Mapping the permafrost stability on the Tibetan Plateau for 2005–2015 - Youhua Ran; Xin Li; Guodong Cheng; Zhuotong Nan; Jinxing Che; Yu Sheng; Qingbai Wu; Huijun Jin; Dongliang Luo; Zhiguang Tang; Xiaobo Wu (Science China Earth Sciences, 2021)

MST1 modulates Th17 activation in psoriasis via regulating TLR4-NF-κB pathway - Huayang Tang; Ze Guo; Xianfa Tang; Jinping Gao; Wenjun Wang; He Huang; Xiaodong Zheng; Hui Cheng; Yujun Sheng; Liangdan Sun (Human Cell, 2021)

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

Insights into a giant landslide-prone area on the eastern margin of the Tibetan Plateau, China - Bo Zhao; Yun-sheng Wang; Jia Li; Jian-lin Wang; Chen-xiao Tang (Journal of Mountain Science, 2021)

Characteristics of the potential vorticity and its budget in the surface layer over the Tibetan plateau - Chen Sheng; Guoxiong Wu; Yiqiong Tang; Bian He; Yongkun Xie; Tingting Ma; Ting Ma; Jinxiao Li; Qing Bao; Yimin Liu (International Journal of Climatology, 2021)
The variability of interior atmospheric potential vorticity (PV) is linked with PV generation at the Earth's surface. The present paper reveals the features of the surface PV and provides a stepping stone to investigate the surface PV budget. In this study, the formats of the PV and PV budget adopting a generalized vertical coordinate were theoretically examined to facilitate the calculation of the surface PV and its budget. Results show that the formats of the PV and PV budget equations are independent of the vertical coordinate. While the vertical component of the surface PV dominates over the platform of the Tibetan Plateau, the horizontal component plays an important role over the slopes of the Tibetan Plateau, especially the southern slope owing to the strong in‐situ meridional gradient of the potential temperature. These results indicate that the employment of complete surface PV not only provides a finer PV structure but also more appropriately reveals its effect on atmospheric circulation. Diagnosis based on reanalysis and model output demonstrates that the surface PV budget equation is well balanced both in terms of the climate mean and synoptic process, and the surface PV budget in June has a prominent diurnal cycle. The diabatic heating with a minimum in the early morning and a maximum from evening to midnight contributes dominantly to this diurnal cycle. It is further indicated that positive PV generation due to diabatic heating is essential for the formation, development, and movement of the Tibetan Plateau vortex.

Nutrition and growth outcomes are affected by aflatoxin exposures in Kenyan children - Ruth Nabwire Wangia-Dixon; Kathy Siyu Xue; Jessica Alcala; Trang Ho Thu Quach; Xiao Song; Lili Tang; James Ombaka; David Peter Githanga; Omu Aggrey Anzala; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2020)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

Spororrminone A and 2- epi -spororrminone A, two new chromones from an endolichenic fungus Sporormiella irregularis - Mei-Juan Huang; Yan-Jun Li; Jia Tang; Guo-Dong Chen; Dan Hu; Wei Xu; Liang-Dong Guo; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2020)

Aircraft measurements reveal vertical distribution of atmospheric ammonia over the North China Plain in early autumn - Weiwei Pu; Heng Guo; Zhiqiang Ma; Yulu Qiu; Yixi Tang; Quan Liu; Fei Wang; Jiujiang Sheng (Environmental Chemistry Letters, 2020)

Efficient CRISPR/Cas9-mediated gene editing in Guangdong small-ear spotted pig cells using an optimized electrotransfection method - Yan-yan Wei; Qun-mei Zhan; Xiang-xing Zhu; Ai-fen Yan; Juan Feng; Lian Liu; Jian-hao Li; Dong-sheng Tang (Biotechnology Letters, 2020)

Laboratory characterization of sandy soil water content during drying process using electrical resistivity/resistance method (ERM) - Ni An; Chao-Sheng Tang; Qing Cheng; De-Yin Wang; Bin Shi (Bulletin of Engineering Geology and the Environment, 2020)

Drying-induced soil shrinkage and desiccation cracking monitoring with distributed optical fiber sensing technique - Qing Cheng; Chao-Sheng Tang; Cheng Zhu; Ke Li; Bin Shi (Bulletin of Engineering Geology and the Environment, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Microseismic Monitoring to Characterize Structure-Type Rockbursts: A Case Study of a TBM-Excavated Tunnel - Quan-Sheng Liu; Jian Wu; Xiao-Ping Zhang; Lie-Xian Tang; Chen Bi; Wei-Wei Li; Jin-Lin Xu (Rock Mechanics and Rock Engineering, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Translocator protein 18 kDa: a potential therapeutic biomarker for post traumatic stress disorder - Zhi-Kun Qiu; Xu Liu; Yong Chen; Rong-Jia Wu; Shi-Feng Guan; Yun-yun Pan; Qian-Bo Wang; Dan Tang; Tao Zhu; Ji-Sheng Chen (Metabolic Brain Disease, 2020)

The Influence of pH on Cadmium Accumulation in Seedlings of Rice (Oryza sativa L.) - Umed Ali; Min Zhong; Tahmina Shar; Sajid Fiaz; Lihong Xie; Guiai Jiao; Shakeel Ahmad; Zhonghua Sheng; Shaoqing Tang; Xiangjin Wei; Peisong Hu (Journal of Plant Growth Regulation, 2020)

Toonapolyynes A–D, new polyynes from Toona ciliata - Rong Wang; Fu-Qiang Ni; Jun Sang; Yao Zhang; Jia-Luo Huang; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

An alternative splicing variant of mineralocorticoid receptor discovered in preeclampsia tissues and its effect on endothelial dysfunction - Mengxi Guo; Chengliang Zhou; Gufeng Xu; Lin Tang; Yechun Ruan; Ying Yu; Xianhua Lin; Dandan Wu; Hao Chen; Priscilla Yu; Luyang Jin; Yinyu Wang; et al. (Science China Life Sciences, 2020)

Isolation of urease-producing bacteria and their effects on reducing Cd and Pb accumulation in lettuce (Lactuca sativa L.) - Tiejun Wang; Shilin Wang; Xingchun Tang; Xianpeng Fan; Sheng Yang; Lunguang Yao; Yadong Li; Hui Han (Environmental Science and Pollution Research, 2020)

Mechanical behavior of fiber-reinforced, chemically stabilized dredged sludge - Hong-Sheng Wang; Chao-Sheng Tang; Kai Gu; Bin Shi; Hilary I. Inyang (Bulletin of Engineering Geology and the Environment, 2020)

Aflatoxin in household maize for human consumption in Kenya, East Africa - Wangia Ruth Nabwire; James Ombaka; Christopher Peyton Dick; Christian Strickland; Lili Tang; Kathy Siyu Xue; Jia-Sheng Wang (Food Additives & Contaminants Part B-Surveillance, 2020)

Risk profiling using metabolomic characteristics for susceptible individuals of drug-induced liver injury caused by Polygonum multiflorum - Le Zhang; Ming Niu; Ai-wu Wei; Jin-fa Tang; Can Tu; Zhao-fang Bai; Zheng-sheng Zou; Xiao-he Xiao; You-ping Liu; Jia-bo Wang (Archives of Toxicology, 2020)

CAS FGOALS-f3-L Model Datasets for CMIP6 GMMIP Tier-1 and Tier-3 Experiments - Bian He; Yimin Liu; Guoxiong Wu; Qing Bao; Tianjun Zhou; Xiaofei Wu; Lei Wang; Jiandong Li; Xiaocong Wang; Jinxiao Li; Wenting Hu; Xiaoqi Zhang; et al. (Advances in Atmospheric Sciences, 2020)
The Chinese Academy of Sciences (CAS) Flexible Global Ocean–Atmosphere–Land System (FGOALS-f3-L) model datasets prepared for the sixth phase of the Coupled Model Intercomparison Project (CMIP6) Global Monsoons Model Intercomparison Project (GMMIP) Tier-1 and Tier-3 experiments are introduced in this paper, and the model descriptions, experimental design and model outputs are demonstrated. There are three simulations in Tier-1, with different initial states, and five simulations in Tier-3, with different topographies or surface thermal status. Specifically, Tier-3 contains four orographic perturbation experiments that remove the Tibetan–Iranian Plateau, East African and Arabian Peninsula highlands, Sierra Madre, and Andes, and one thermal perturbation experiment that removes the surface sensible heating over the Tibetan–Iranian Plateau and surrounding regions at altitudes above 500 m. These datasets will contribute to CMIP6’s value as a benchmark to evaluate the importance of long-term and short-term trends of the sea surface temperature in monsoon circulations and precipitation, and to a better understanding of the orographic impact on the global monsoon system over highlands.

Inositol as a new enhancer for improving lipid production and accumulation in Schizochytrium sp. SR21 - Zhao-Xin Liu; Shuai You; Bin-Ping Tang; Bo Wang; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Spatial distribution of the oxygen-18 in precipitation in China based on a new empirical model - Pei Zhao; Zheng-sheng Guo; Dong-li She; Xiang-yu Tang (Journal of Mountain Science, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

Modelling Rock Failure with a Novel Continuous to Discontinuous Method - Bin Gong; Shanyong Wang; Scott William Sloan; Daichao Sheng; Chun’an Tang (Rock Mechanics and Rock Engineering, 2019)

Application of four-component dipole shear reflection imaging to interpret the geological structure around a deviated well - Sheng-Qing Lee; Ming Chen; Xi-Hao Gu; Yuan-Da Su; Xiao-Ming Tang (Applied Geophysics, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Asperpyrone F, a new dimeric naphtho- γ -pyrone from the edible fungus Pleurotus ostreatus - Xu Cai; Yang Yu; Qian Li; Ben-Ke Chen; Yun Huang; Xian-Wei Zou; Jin-Tian Tang; Bi-Sheng Huang (Natural Product Research, 2019)

Magnetic characteristics of Juniperus formosana needles along an urban street in Lanzhou, Northwest China: the variation of different season and orientation - Hong Chen; Bo Wang; Dun-sheng Xia; Yi-jiao Fan; Hui Liu; Zhi-rong Tang; Shan Ma (Environmental Science and Pollution Research, 2019)

Age-related variations of needles and twigs in nutrient, nonstructural carbon and isotope composition along altitudinal gradients - Duo-teng Tang; Guo-quan Peng; Sheng Zhang (Journal of Mountain Science, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

Geochronology, geochemistry and Sr-Nd-Pb-Hf isotopes of the Early Paleogene gabbro and granite from Central Lhasa, southern Tibet: petrogenesis and tectonic implications - Yun-hui Zhang; Hua-wen Cao; Steven P. Hollis; Li Tang; Mo Xu; Jun-sheng Jiang; Shun-bao Gao; Yang-shuang Wang (International Geology Review, 2019)

Analysis of Genetic Diversity and Population Structure in Sophora japonica Linn. in China With Newly Developed SSR Markers - Wen-Jiang Shu; Jian-min Tang; Zong-You Chen; Yun-Sheng Jiang; Zheng-Feng Wang; Xiao Wei (Plant Molecular Biology Reporter, 2019)

Toxicological effects benzotriazole to the marine scallop Chlamys nobilis: a 2-month exposure study - Tang-tian He; Tao Zhang; Shi-bo Liu; Jing-chun Shi; Yi-sheng Huang; Huai-ping Zheng; Wen-hua Liu (Environmental Science and Pollution Research, 2019)

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis - Daowen Wang; Sheng Li; Jiangang Jiang; Jiangtao Yan; Chunxia Zhao; Yan Wang; Yexin Ma; Hesong Zeng; Xiaomei Guo; Hong Wang; Jiarong Tang; Houjuan Zuo; et al. (Science China Life Sciences, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Endophytic effects of Aspergillus oryzae on radish (Raphanus sativus) and its herbivore, Plutella xylostella - Bo-Tong Sun; Komivi Senyo Akutse; Xiao-Feng Xia; Jun-Hui Chen; Xin Ai; Yang Tang; Qian Wang; Bo-Wen Feng; Mark S. Goettel; Min-Sheng You (Planta, 2018)

Gibberellin Inhibits Floral Initiation in the Perennial Woody Plant Jatropha curcas - Jialong Li; Bang-Zhen Pan; Longjian Niu; Mao-Sheng Chen; Mingyong Tang; Zeng-Fu Xu (Journal of Plant Growth Regulation, 2018)

Chlorophyll deficient 3, Encoding a Putative Potassium Efflux Antiporter, Affects Chloroplast Development Under High Temperature Conditions in Rice (Oryza sativa L.) - Rongjian Luo; Hanwei Jiang; Yusong Lv; Shikai Hu; Zhonghua Sheng; Gaoneng Shao; Shaoqing Tang; Peisong Hu; Xiangjin Wei (Plant Molecular Biology Reporter, 2018)

New pyridocarbazole alkaloids from Strychnos nitida - Wei Li; Gui-Hua Tang; Lin Chen; Ya-Qi Tang; You-Kai Xu; Bo Liu; Sheng Yin (Natural Product Research, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Improvement of sulfamethoxazole (SMX) elimination and inhibition of formations of hydroxylamine-SMX and N4-acetyl-SMX by membrane bioreactor systems - Min-Hui Tang; Nan Gao; Jiao Zhou; Yan Zhao; Jing-Sheng Cheng; Wen-Kun Su; Ying-Jin Yuan (Biodegradation, 2018)

Modelling Coastal Cliff Recession Based on the GIM–DDD Method - Bin Gong; Shanyong Wang; Scott William Sloan; Daichao Sheng; Chun’an Tang (Rock Mechanics and Rock Engineering, 2018)

A terrain openness index for the extraction of karst Fenglin and Fengcong landform units from DEMs - Xin Meng; Li-yang Xiong; Xian-wu Yang; Bi-sheng Yang; Guo-an Tang (Journal of Mountain Science, 2018)

A new bisabolane sesquiterpenoid and a new abietane diterpenoid from Cephalotaxus sinensis - Abrar Ahmed; Wei Li; Jun-Sheng Zhang; Pek-Ha Sam; Yi-Hong Zou; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2018)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Correction to: Synthesis and inhibitory effect of 10-chlorocanthin-6-one on ovarian cancer HO8910PM cells - Wenhua Li; Yuwen Chen; Yuwen Sheng; Zeyu Xie; Yaxiong Tang (Biotechnology Letters, 2018)

Synthesis and inhibitory effect of 10-chlorocanthin-6-one on ovarian cancer HO8910PM cells - Wenhua Li; Yuwen Chen; Yuwen Sheng; Zeyu Xie; Yaxiong Tang (Biotechnology Letters, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

The Effects of Soil Drying on the Growth of a Dominant Peatland Species, Carex lasiocarpa - Jihong Yuan; Ping Wang; Jacob Weiner; Hongfeng Bian; Zhanhui Tang; Lianxi Sheng (Wetlands, 2017)

Erratum to: Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2017)

Chinese progress in geomorphometry - Guonian Lv; Liyang Xiong; Min Chen; Guoan Tang; Yehua Sheng; Xuejun Liu; Zhiyao Song; Yuqi Lu; Zhaoyuan Yu; Ka Zhang; Meizhen Wang (Journal of Geographical Sciences, 2017)

Localization and dynamic expression of a 27.8 kDa receptor protein for lymphocystis disease virus infection in sea bass (Lateolabrax japonicus) tissues - Ronghua Wu; Xiuzhen Sheng; Xiaoqian Tang; Jing Xing; Wenbin Zhan (Journal of Ocean University of China, 2017)

Identification of a three-base deletion in the Pi2 locus, and development of functional marker for marker-assisted resistance selection - Zhonghua Sheng; Qianlong Li; Wei Li; Wei Chen; Xiangjin Wei; Lihong Xie; Guiai Jiao; Gaoneng Shao; Jianlong Wang; Shaoqing Tang; Peisong Hu (Euphytica, 2017)

Two new flavans from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Shu-Sheng Huang; Ye-Er Liang; Jian-Bo Sun; Yan Ma; Bao Zeng; Simon Ming-Yuen Lee; Jian-Lin Lu (Natural Product Research, 2017)

Association of GWAS-Reported Variant rs11196288 near HABP2 with Ischemic Stroke in Chinese Han Population - Shao-hua Li; Chang-he Shi; Yu-sheng Li; Fang Li; Mi-bo Tang; Xin-jing Liu; Shuo Zhang; Zhi-lei Wang; Bo Song; Yu-ming Xu (Journal of Molecular Neuroscience, 2017)

An object-based approach for two-level gully feature mapping using high-resolution DEM and imagery: a case study on hilly loess plateau region, China - Kai Liu; Hu Ding; Guoan Tang; A-Xing Zhu; Xin Yang; Sheng Jiang; Jianjun Cao (Chinese Geographical Science, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

OsNHX2, an Na+/H+ antiporter gene, can enhance salt tolerance in rice plants through more effective accumulation of toxic Na+ in leaf mesophyll and bundle sheath cells - Xin-Xia Teng; Wen-Lei Cao; Hong-Xia Lan; Hai-Juan Tang; Yong-Mei Bao; Hong-Sheng Zhang (Acta Physiologiae Plantarum, 2017)

Two eisosome proteins play opposite roles in autophagic control and sustain cell integrity, function and pathogenicity in Beauveria bassiana - Long‐Bin Zhang; Li Tang; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2017)
Summary Pil1A and Pil1B are two core eisosome proteins that are homologous to yeast Pil1/Lsp1 or filamentous fungal Pil1A/Pil1B but have been unexplored in entomopathogenic fungi. Here we examined subcellular localization and functions of Pil1A and Pil1B in Beauveria bassiana , a fungal insect pathogen. Either localization or co‐localization experiments of the two proteins demonstrated that Pil1A and Pil1B were simultaneously localized at the periphery of hyphal cells for formation of stable, punctuate spots in B. bassiana . This is different from a reliance of proper Lsp1/Pil1B localization upon Pil1/Pil1A in other fungi. Deletions of pil1A and pil1B caused opposite changes in expression of many autophagy‐related genes and formation of intravacuolar autophagosomes. Such opposite changes were restored to nearly normal status by exogenous rapamycin, implicating a link of Pil1A/B to the target of rapamycin signalling pathway. All single/double deletion mutants of pil1A and pil1B lost almost all pathogenicity due to reduced ability to secrete Pr1 proteases for cuticle degradation. They also showed differential changes in cell wall integrity and multiple stress responses. These findings unveil opposite roles for Pil1A and Pil1B in autophagic regulation and an essentiality of both for cell integrity, function and pathogenicity of the fungal entomopathogen.

Development and application of monoclonal antibodies against IgM of black rockfish Sebastes schlegeli - W. Zhang; X. Q. Tang; X. Z. Sheng; J. Xing; W. B. Zhan (Journal of Fish Biology, 2017)
Monoclonal antibodies ( mAbs ) against black rockfish Sebastes schlegeli serum immunoglobulin M ( IgM ) were developed, which showed a specific reaction with the heavy chain of S. schlegeli IgM in Western blotting and with surface IgM positive ( sIgM + ) lymphocytes in indirect immunofluorescence. mAb 2A6 was employed to investigate the antibody and sIgM + lymphocyte responses of S. schlegeli injected with inactivated Edwardsiella tarda , by ELISA and flow cytometry. Compared with controls, the level of specific antibodies and the percentage of sIgM + lymphocytes both increased in the immunized fish and simultaneously reached their peaks at day 35 after immunization.

Benzimidazole derivative M084 extends the lifespan of Caenorhabditis elegans in a DAF-16/FOXO-dependent way - Ai-Jun Ding; Gui-Sheng Wu; Bin Tang; Xuechuan Hong; Michael X. Zhu; Huai-Rong Luo (Molecular and Cellular Biochemistry, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Molecular mechanisms of water table lowering and nitrogen deposition in affecting greenhouse gas emissions from a Tibetan alpine wetland - Hao Wang; Lingfei Yu; Zhenhua Zhang; Wei Liu; Litong Chen; Guangmin Cao; Haowei Yue; Jizhong Zhou; Yunfeng Yang; Yanhong Tang; Jin‐Sheng He (Global Change Biology, 2017)
Rapid climate change and intensified human activities have resulted in water table lowering ( WTL ) and enhanced nitrogen (N) deposition in Tibetan alpine wetlands. These changes may alter the magnitude and direction of greenhouse gas ( GHG ) emissions, affecting the climate impact of these fragile ecosystems. We conducted a mesocosm experiment combined with a metagenomics approach (GeoChip 5.0) to elucidate the effects of WTL (−20 cm relative to control) and N deposition (30 kg N ha −1 yr −1 ) on carbon dioxide ( CO 2 ), methane ( CH 4 ) and nitrous oxide (N 2 O) fluxes as well as the underlying mechanisms. Our results showed that WTL reduced CH 4 emissions by 57.4% averaged over three growing seasons compared with no‐ WTL plots, but had no significant effect on net CO 2 uptake or N 2 O flux. N deposition increased net CO 2 uptake by 25.2% in comparison with no‐N deposition plots and turned the mesocosms from N 2 O sinks to N 2 O sources, but had little influence on CH 4 emissions. The interactions between WTL and N deposition were not detected in all GHG emissions. As a result, WTL and N deposition both reduced the global warming potential ( GWP ) of growing season GHG budgets on a 100‐year time horizon, but via different mechanisms. WTL reduced GWP from 337.3 to −480.1 g CO 2 ‐eq m −2 mostly because of decreased CH 4 emissions, while N deposition reduced GWP from 21.0 to −163.8 g CO 2 ‐eq m −2 , mainly owing to increased net CO 2 uptake. GeoChip analysis revealed that decreased CH 4 production potential, rather than increased CH 4 oxidation potential, may lead to the reduction in net CH 4 emissions, and decreased nitrification potential and increased denitrification potential affected N 2 O fluxes under WTL conditions. Our study highlights the importance of microbial mechanisms in regulating ecosystem‐scale GHG responses to environmental changes.

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Predicting the Binding Affinity of ERβ Ligands Based on a Novel Variable Selection Method - Hong-Yan Liu; Fei Zhang; Li-Tang Qin; Zhong-Sheng Yi; Xiu-Li Wang; Ling-Yun Mo (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Modified method for the extraction of mRNA from paddy soils - Hongling Qin; Xiangbi Chen; Yafang Tang; Haijun Hou; Rong Sheng; Jinlin Shen (Biotechnology Letters, 2016)

Intervention trial with calcium montmorillonite clay in a south Texas population exposed to aflatoxin - Brad H. Pollock; Sarah Elmore; Amelia Romoser; Lili Tang; Min-su Kang; Kathy Xue; Marisa Rodriguez; Nicole A. Dierschke; Holly G. Hayes; H. Andrew Hansen; Fernando Guerra; Jia-Sheng Wang; et al. (Food Additives & Contaminants: Part A, 2016)

Voriconazole combined with low-dose amphotericin B liposome for treatment of cryptococcal meningitis - Shan-Shan Li; Xin-Yue Tang; Sheng-Guo Zhang; Shun-Lan Ni; Nai-Bin Yang; Ming-Qin Lu (Infectious Diseases, 2016)

Elevated Serum Levels of Neopterin at Admission Predicts Depression After Acute Ischemic Stroke: a 6-Month Follow-Up Study - Chao-Zhi Tang; Yu-Ling Zhang; Wen-Sheng Wang; Wei-Guo Li; Ji-Peng Shi (Molecular Neurobiology, 2016)

Copper isotopic signature of the Tiegelongnan high-sulfidation copper deposit, Tibet: implications for its origin and mineral exploration - Jilin Duan; Juxing Tang; Yubin Li; Sheng-Ao Liu; Qin Wang; Chao Yang; Yiyun Wang (Mineralium Deposita, 2016)

Monitoring of heavy metal levels in the major rivers and in residents’ blood in Zhenjiang City, China, and assessment of heavy metal elimination via urine and sweat in humans - Jianguo Sheng; Wenhui Qiu; Bentuo Xu; Hui Xu; Chong Tang (Environmental Science and Pollution Research, 2016)

Molecular phylogenetic analysis of key Jatropha species inferred from nrDNA ITS and chloroplast (trnL-F and rbcL) sequences - Guo-ye Guo; Sheng-hua Wang; Ying Xu; Lin Tang; Mao-qun Yu; Fang Chen (Genes & Genomics, 2016)

Serum Levels of High-sensitivity C-Reactive Protein at Admission Are More Strongly Associated with Poststroke Depression in Acute Ischemic Stroke than Homocysteine Levels - Chao-Zhi Tang; Yu-Ling Zhang; Wen-Sheng Wang; Wei-Guo Li; Ji-Peng Shi (Molecular Neurobiology, 2016)

Effect of contact state on the shear behavior of artificial rock joint - Zhi Cheng Tang; Run Qiu Huang; Quan Sheng Liu; Louis Ngai Yuen Wong (Bulletin of Engineering Geology and the Environment, 2016)

Lentivirus-mediated transfection of chondroitinase ABC gene without the bacterial leader sequence enables long-term secretion of functional chondroitinase ABC in human bone marrow stromal cells - Yang Guo; Michael Klüppel; Hao Tang; Sheng Tan; Peidong Zhang; Zhenzhou Chen (Biotechnology Letters, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Dynamic changes of histone H3 lysine 9 following trimethylation in bovine oocytes and pre-implantation embryos - Sheng Zhang; Fang Wang; Congli Fan; Bo Tang; Xueming Zhang; Ziyi Li (Biotechnology Letters, 2016)

Evolution of the Late Cretaceous Yongfeng-Chongren Basin in Jiangxi Province, southeast China: insights from sedimentary facies analysis and pebble counting - Liu-qin Chen; Fu-sheng Guo; Chao Tang (Journal of Mountain Science, 2016)

Enhancement of Autophagy by Histone Deacetylase Inhibitor Trichostatin A Ameliorates Neuronal Apoptosis After Subarachnoid Hemorrhage in Rats - Anwen Shao; Zhen Wang; Haijian Wu; Xiao Dong; Yong Li; Sheng Tu; Junjia Tang; Mingfei Zhao; Jianmin Zhang; Yuan Hong (Molecular Neurobiology, 2016)

Comparison of clinical outcomes of patients with non-small-cell lung cancer harbouring epidermal growth factor receptor exon 19 or exon 21 mutations after tyrosine kinase inhibitors treatment: a meta-analysis - Miaomiao Sheng; Fang Wang; Yueguang Zhao; Shanshan Li; Xiaojie Wang; Tao Shou; Ying Luo; Wenru Tang (European Journal of Clinical Pharmacology, 2016)

Investigating the Effects of Small Synthetic Organic Matters on Dissolved Organic Matter Adsorption - Liang Yan; Lan Jiang; Yingdong Tang; Hao Yu; Sheng Sheng; Guanglu Yu (Water, Air, & Soil Pollution, 2015)

Voriconazole: a novel treatment option for cryptococcal meningitis - Yan Yao; Jia-Tang Zhang; Bo Yan; Ting Gao; Xiao-Wei Xing; Cheng-Lin Tian; Xu-Sheng Huang; Sheng-Yuan Yu (Infectious Diseases, 2015)

Effects of trawl selectivity and genetic parameters on fish body length under long-term trawling - Yang Yu; Peng Sun; He Cui; Huaxiang Sheng; Fenfang Zhao; Yanli Tang; Zelin Chen (Journal of Ocean University of China, 2015)

Longitudinal evaluation of aflatoxin exposure in two cohorts in south-western Uganda - Min-Su Kang; Peter Nkurunziza; Richard Muwanika; Guoqing Qian; Lili Tang; Xiao Song; Kathy Xue; Allan Nkwata; John Ssempebwa; Tom Lutalo; Gershim Asiki; David Serwadda; et al. (Food Additives & Contaminants: Part A, 2015)

Growth, photosynthetic and physiological responses of Torreya grandis seedlings to varied light environments - Hui Tang; Yuan-Yuan Hu; Wei-Wu Yu; Li-Li Song; Jia-Sheng Wu (Trees, 2015)

Association analysis revealed one susceptibility locus for vitiligo with immune-related diseases in the Chinese Han population - Shu Li; Weiyi Yao; Qian Pan; Xianfa Tang; Suli Zhao; Wenjun Wang; Zhengwei Zhu; Jinping Gao; Yujun Sheng; Fusheng Zhou; Xiaodong Zheng; Xianbo Zuo; et al. (Immunogenetics, 2015)

Changes in local oceanographic and atmospheric conditions shortly after the 2004 Indian Ocean tsunami - Zhongzhen Yan; Yi Sui; Jinyu Sheng; Danling Tang; I-I Lin (Ocean Dynamics, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

The rice thermo-sensitive genic male sterility gene tms9: pollen abortion and gene isolation - Zhonghua Sheng; Liqun Tang; Gaoneng Shao; Lihong Xie; Guiai Jiao; Shaoqing Tang; Peisong Hu (Euphytica, 2015)
The development of two-line hybrid rice has done great contribution to the food security. It is imperative to study the male sterility mechanism of rice photo-thermo sensitive genic male sterile (PTGMS) line which is the core component of two-line hybrid rice. Zhu1S is a rice thermo-sensitive genic male sterile line used frequently as female parent in two-line hybrid seed production. A cytological examination of the development of the Zhu1S anther wall and the microspores showed that tms9 encoded male sterility is caused by the failure of the tapetum to degenerate normally, thereby starving the microspores and finally leading to pollen abortion. A fine-scale genetic map based on a large F2 population allowed tms9 to be located within a 30.2 Kb segment of chromosome 2 harboring seven open reading frames. A comparison between Zhu1S under sterile temperature condition (high temperature, male sterile) and fertile temperature condition (low temperature, fertile) showed that only one of the seven genes, LOC_Os02g12290 , was differentially transcribed, with its transcript abundance being much lower under the sterile temperature growing condition. LOC_Os02g12290 encodes a nuclear ribonuclease Z. Re-sequencing demonstrated that the Zhu1S LOC_Os02g12290 allele differed from that present in non tms9 carrier alleles by two contiguous nucleotides in the first exon, inducing a truncated mRNA.

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Long-term morphological response to dredging including cut-across-shoal in a tidal channel-shoal system - Yu-Hai Wang; Chong-Hao Wang; Li-Qun Tang; Da-Bin Liu; Chuan-Sheng Guo; Chun-Jing Liu; Hui-Ming Zhao (Ocean Dynamics, 2014)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Mechanical Model for Predicting Closure Behavior of Rock Joints Under Normal Stress - Zhi-Cheng Tang; Quan-Sheng Liu; Cai-Chu Xia; Ying-Long Song; Ji-Hui Huang; Chun-Bo Wang (Rock Mechanics and Rock Engineering, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Assessment of carbon sustainability under different tillage systems in a double rice cropping system in Southern China - Jian-Fu Xue; Sheng-Li Liu; Zhong-Du Chen; Fu Chen; Rattan Lal; Hai-Ming Tang; Hai-Lin Zhang (The International Journal of Life Cycle Assessment, 2014)

Downregulation of miR-101-3p by hepatitis B virus promotes proliferation and migration of hepatocellular carcinoma cells by targeting Rab5a - Yanrui Sheng; Jianbo Li; Chengcheng Zou; Sen Wang; Yiyi Cao; Jingnan Zhang; Ailong Huang; Hua Tang (Archives of Virology, 2014)

Complete genome sequence of a novel infectious bronchitis virus strain circulating in China with a distinct S gene - Sheng Zhou; Mengjun Tang; Yi Jiang; Xu Chen; Xinyue Shen; Jianmei Li; Yabin Dai; Jianmin Zou (Virus Genes, 2014)

C-type natriuretic peptide inhibiting vascular calcification might involve decreasing bone morphogenic protein 2 and osteopontin levels - Jing-Jing Chen; Jing Zhang; Yan Cai; Ye-Bo Zhou; Ge-Bo Wen; Chao-Shu Tang; Yong-Fen Qi; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2014)

Deep re-sequencing of a widely used maintainer line of hybrid rice for discovery of DNA polymorphisms and evaluation of genetic diversity - Yuanyi Hu; Bigang Mao; Yan Peng; Yidan Sun; Yinlin Pan; Yumei Xia; Xiabing Sheng; Yaokui Li; Li Tang; Longping Yuan; Bingran Zhao (Molecular Genetics and Genomics, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Berberine regulates the expression of E-prostanoid receptors in diabetic rats with nephropathy - Li Qin Tang; Sheng Liu; Shan Tang Zhang; Ling Na Zhu; Feng Ling Wang (Molecular Biology Reports, 2014)

Adipose-derived stem cells transfected with pEGFP-OSX enhance bone formation during distraction osteogenesis - Qing-guo Lai; Shao-long Sun; Xiao-hong Zhou; Chen-ping Zhang; Kui-feng Yuan; Zhong-jun Yang; Sheng-lei Luo; Xiao-peng Tang; Jiang-bo Ci (Journal of Zhejiang University-SCIENCE B, 2014)

A comparative study of bioactive secondary metabolite production in diploid and tetraploid Echinacea purpurea (L.) Moench - Chuan-gui Xu; Tie-xin Tang; Rong Chen; Chun-hui Liang; Xiang-yu Liu; Chuan-long Wu; Yue-sheng Yang; De-po Yang; Hong Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Association of interleukin-8 gene polymorphisms with the risk of hepatocellular carcinoma - Jun-li Wang; Le-gen Nong; Ye-sheng Wei; Yu-jin Tang; Jian-chu Wang; Chun-fang Wang (Molecular Biology Reports, 2014)

The rice nuclear gene WLP1 encoding a chloroplast ribosome L13 protein is needed for chloroplast development in rice grown under low temperature conditions - Jian Song; Xiangjin Wei; Gaoneng Shao; Zhonghua Sheng; Daibo Chen; Congli Liu; Guiai Jiao; Lihong Xie; Shaoqing Tang; Peisong Hu (Plant Molecular Biology, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Diagnosis of the secondary circulation of tropical storm Bilis (2006) and the effects of convective systems on its track - Jinhua Yu; Hao Fu; Sheng Tang; Siwei Sheng (Journal of Meteorological Research, 2014)

Peroxisome proliferator-activated receptor-α activation protects against endoplasmic reticulum stress-induced HepG2 cell apoptosis - Wei-xiang Tang; Li-kui Wang; Yi-qiao Wang; Zhi-jun Zong; Zhi-xin Gao; Xue-sheng Liu; Yu-jun Shen; Yu-xian Shen; Yuan-hai Li (Molecular and Cellular Biochemistry, 2014)

Production of ramoplanin analogues by genetic engineering of Actinoplanes sp. - Hai-Xue Pan; Zhou-Zhou Chen; Lei Shao; Ji-An Li; Jun-Sheng Chen; Chun-Bao Zhu; Gong-Li Tang; Dai-Jie Chen (Biotechnology Letters, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Fine mapping of BH1, a gene controlling lemma and palea development in rice - Xiangjin Wei; Xuanwen Zhang; Gaoneng Shao; Jiwai He; Guiai Jiao; Lihong Xie; Zhonghua Sheng; Shaoqing Tang; Peisong Hu (Plant Cell Reports, 2013)

Role of microRNA-21 in regulating 3T3-L1 adipocyte differentiation and adiponectin expression - Min Kang; Li-Mei Yan; Wen-Yu Zhang; Yu-Mei Li; An-Zhou Tang; He-Sheng Ou (Molecular Biology Reports, 2013)

HBx and HBs regulate RhoC expression by upregulating transcription factor Ets-1 - Dongdong Qin; Kai Li; Jialin Qu; Sen Wang; Chengcheng Zou; Yanrui Sheng; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Evaluation of efficiency of aircraft liquid waste treatment and identification of daily inspection indices: a case study in Changchun, China - Jianling Xu; Jiaqi Yang; Nan Zhao; Lianxi Sheng; Yuanhui Zhao; Zhanhui Tang (Environmental Monitoring and Assessment, 2013)

Berberine ameliorates renal injury by regulating G proteins-AC- cAMP signaling in diabetic rats with nephropathy - Li Qin Tang; Feng Ling Wang; Ling Na Zhu; Fei Lv; Sheng Liu; Shan Tang Zhang (Molecular Biology Reports, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Molecular cloning and expression analysis of major histocompatibility complex class IIB gene of the Whitespotted bambooshark (Chiloscyllium plagiosum) - Qian Ma; Yong-Quan Su; Jun Wang; Zhi-Meng Zhuang; Qi-Sheng Tang (Fish Physiology and Biochemistry, 2013)

Hepatitis B virus regulation of Raf1 promoter activity through activation of transcription factor AP-2α - Jialin Qu; Jianbo Li; Ke Chen; Dongdong Qin; Kai Li; Yanrui Sheng; Chengcheng Zou; Sen Wang; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Repellent and attractive effects of herbs on insects in pear orchards intercropped with aromatic plants - Guang Bo Tang; Bei Zhou Song; Ling Ling Zhao; Xu Sheng Sang; Hui Hua Wan; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2013)

Risk assessment of traffic-related air pollution in a world heritage city - N. Sheng; U. W. Tang (International Journal of Environmental Science and Technology, 2013)

Genetic manipulation revealing an unusual N-terminal region in a stand-alone non-ribosomal peptide synthetase involved in the biosynthesis of ramoplanins - Hai-Xue Pan; Ji-An Li; Lei Shao; Chun-Bao Zhu; Jun-Sheng Chen; Gong-Li Tang; Dai-Jie Chen (Biotechnology Letters, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Overexpression of AtbZIP60deltaC Gene Alleviates Salt-induced Oxidative Damage in Transgenic Cell Cultures - Wei Tang; Michael Page; Yongjun Fei; Lecheng Liu; Feng Xu; Xiaodong Cai; Longyi Yuan; Qiang-Sheng Wu; Mingqin Zhou (Plant Molecular Biology Reporter, 2012)

Polymorphisms in TP53 and MDM2 contribute to higher risk of colorectal cancer in Chinese population: a hospital-based, case–control study - Yuxing Zhang; Li Liu; Yingchun Tang; Chao Chen; Qian Wang; Jun Xu; Chao Yang; Xiaoping Miao; Sheng Wei; Jigui Chen; Shaofa Nie (Molecular Biology Reports, 2012)

Vinpocetine inhibits breast cancer cells growth in vitro and in vivo - Er-Wen Huang; Sheng-Jiang Xue; Zheng Zhang; Jia-Guo Zhou; Yong-Yuan Guan; Yong-Bo Tang (Apoptosis, 2012)

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2012)

Zygote-derived seedling production of Sargassum thunbergii: focus on two frequently experienced constraints in tank culture of seaweed - Quan Sheng Zhang; Yong Zheng Tang; Shi Kai Liu; Shu Bao Zhang; Zhi Cheng Lu; Shao Hua Cu; Yong Qiang Yu (Journal of Applied Phycology, 2012)

Recombinant human endostatin inhibits adjuvant arthritis by down-regulating VEGF expression and suppression of TNF-α, IL-1β production - Wei Hu; Li-Juan Xia; Fei-Hu Chen; Fan-Rong Wu; Jie Tang; Cun-Zhi Chen; Sheng Jiang; Hui-Hui Chen (Inflammation Research, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Mycobacterial infections in adult patients with hematological malignancy - C.-Y. Chen; W.-H. Sheng; C.-C. Lai; C.-H. Liao; Y.-T. Huang; W. Tsay; S.-Y. Huang; J.-L. Tang; H.-F. Tien; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Fine mapping of a major QTL for flag leaf width in rice, qFLW4, which might be caused by alternative splicing of NAL1 - Mingliang Chen; Ju Luo; Gaoneng Shao; Xiangjin Wei; Shaoqing Tang; Zhonghua Sheng; Jian Song; Peisong Hu (Plant Cell Reports, 2012)

Pharmacophore modeling and structure-based virtual screening for a novel “switch region” target of bacterial RNA polymerase - Yu-Sheng Li; Lu Zhou; Xiang Ma; Hang Song; Xiang-Yang Tang (Medicinal Chemistry Research, 2012)

H. pylori related proinflammatory cytokines contribute to the induction of miR-146a in human gastric epithelial cells - Na Li; Xiang Xu; Bin Xiao; En-Dong Zhu; Bo-sheng Li; Zhen Liu; Bin Tang; Quan-Ming Zou; Hua-Ping Liang; Xu-Hu Mao (Molecular Biology Reports, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Robust multi-scale image matching for deriving ice surface velocity field from sequential satellite images - Hongxing Liu; Lei Wang; Sheng-Jung Tang; Kenneth C. Jezek (International Journal of Remote Sensing, 2012)

The role of PRKCH gene variants in coronary artery disease in a Chinese population - Jun Zhu; Jian-Jun Yan; Zheng-Ping Kuai; Wei Gao; Jian-Jin Tang; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular Biology Reports, 2012)

Rilmenidine improves hepatic steatosis through p38-dependent pathway to higher the expression of farnesoid X receptor - Po-Sheng Yang; Hung-Tsung Wu; Hsien-Hui Chung; Chun-Ta Chen; Chin-Wen Chi; Ching-Hua Yeh; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

PCSK9 siRNA inhibits HUVEC apoptosis induced by ox-LDL via Bcl/Bax–caspase9–caspase3 pathway - Chun-Yan Wu; Zhi-Han Tang; Lu Jiang; Xue-Fei Li; Zhi-Sheng Jiang; Lu-Shan Liu (Molecular and Cellular Biochemistry, 2012)

Preliminary evaluation of evaluation of the efficiency of aircraft liquid waste treatment using resolvable sanitizing liquid: a case study in Changchun - Jianling Xu; Jiaqi Yang; Nan Zhao; Lianxi Sheng; Yuanhui Zhao; Zhanhui Tang (Environmental Monitoring and Assessment, 2011)

Rapid and Sensitive Detection of Listeria monocytogenes by Loop-Mediated Isothermal Amplification - Meng-Jun Tang; Sheng Zhou; Xiao-Yan Zhang; Jun-Hua Pu; Qing-Lian Ge; Xiu-Jun Tang; Yu-Shi Gao (Current Microbiology, 2011)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

Production and characterization of interspecific somatic hybrids between Brassica oleracea var. botrytis and B. nigra and their progenies for the selection of advanced pre-breeding materials - Gui-xiang Wang; Yu Tang; Hong Yan; Xiao-guang Sheng; Wei-wei Hao; Li Zhang; Kun Lu; Fan Liu (Plant Cell Reports, 2011)

Amycolatopsis endophytica sp. nov., a novel endophytic actinomycete isolated from oil-seed plant Jatropha curcas L. - Qian Miao; Sheng Qin; Guang-Kai Bian; Bo Yuan; Ke Xing; Yue-Ji Zhang; Qin Li; Shu-Kun Tang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

New cytotoxic oxygenated sterols from marine bryozoan Bugula neritina - Fan Yang; Hong-Jun Zhang; Jian-Tao Chen; Hai-Feng Tang; Shu-Juan Piao; Wan-Sheng Chen; Hou-Wen Lin (Natural Product Research, 2011)

A tasseled cap transformation for CBERS-02B CCD data - Li Sheng; Jing-feng Huang; Xiao-lu Tang (Journal of Zhejiang University-SCIENCE B, 2011)

The discovery approaches and detection methods of microRNAs - Yong Huang; Quan Zou; Sheng Peng Wang; Shun Ming Tang; Guo Zheng Zhang; Xing Jia Shen (Molecular Biology Reports, 2011)

c-Myc influences olaquindox-induced apoptosis in human hepatoma G2 cells - Ting Zhang; Shu-Sheng Tang; Xi Jin; Feng-Ying Liu; Chao-Ming Zhang; Wen-Xia Zhao; Shen Zhang; Chun-Di Sun; Xi-Long Xiao (Molecular and Cellular Biochemistry, 2011)

The ultrastructure of the extrusomes in Pseudourostyla cristata, a hypotrichous ciliated protozoan - Jun Zhang; Chun Sheng; Lei Tang; Bing Ni; Fukang Gu (Protoplasma, 2011)

Construction and detection of expression vectors of microRNA-9a in BmN cells - Yong Huang; Quan Zou; Sheng-peng Wang; Shun-ming Tang; Guo-zheng Zhang; Xing-jia Shen (Journal of Zhejiang University-SCIENCE B, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

Influence of arbuscular mycorrhiza on organic solutes in maize leaves under salt stress - Min Sheng; Ming Tang; Fengfeng Zhang; Yanhui Huang (Mycorrhiza, 2011)

Biological functions of microRNAs: a review - Yong Huang; Xing Jia Shen; Quan Zou; Sheng Peng Wang; Shun Ming Tang; Guo Zheng Zhang (Journal of Physiology and Biochemistry, 2011)

A polymorphism in the visfatin gene promoter is related to decreased plasma levels of inflammatory markers in patients with coronary artery disease - Lian-Sheng Wang; Jian-Jun Yan; Na-Ping Tang; Jun Zhu; Yue-Song Wang; Qi-Ming Wang; Jian-Jin Tang; Ming-Wei Wang; En-Zhi Jia; Zhi-Jian Yang; Jun Huang (Molecular Biology Reports, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Preparation, Crystal Structures and Luminescent Properties of Terbium and Europium Complexes with a New Amino-Alkenone Type Ligand - Jun Xu; Yu-Fei Ma; Wei-Sheng Liu; Yu Tang; Min-Yu Tan (Journal of Fluorescence, 2011)

Improved myocardial perfusion and cardiac function by controlled-release basic fibroblast growth factor using fibrin glue in a canine infarct model - Shao-ping Nie; Wang Xiao; Qiao Shi-bin; Zeng Qiu-tang; Jiang Ju-quan; Liu Xiao-qing; Zhu Xiang-ming; Cao Guo-xiang; Ma Chang-sheng (Journal of Zhejiang University-SCIENCE B, 2010)

Elevated high sensitive C-reactive protein and apelin levels after percutaneous coronary intervention and drug-eluting stent implantation - Xin Du; Jun-ping Kang; Jia-hui Wu; Qiang Lv; Chao-shu Tang; Chang-sheng Ma (Journal of Zhejiang University-SCIENCE B, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Climate change alters interannual variation of grassland aboveground productivity: evidence from a 22-year measurement series in the Inner Mongolian grassland - Wenhong Ma; Zhongling Liu; Zhiheng Wang; Wei Wang; Cunzhu Liang; Yanhong Tang; Jin-Sheng He; Jingyun Fang (Journal of Plant Research, 2010)

The Gab2 in signal transduction and its potential role in the pathogenesis of Alzheimer’s disease - Xiao-Ling Pan; Ru-Jing Ren; Gang Wang; Hui-Dong Tang; Sheng-Di Chen (Neuroscience Bulletin, 2010)

Development and characterization of microsatellite markers for Camellia nitidissima - Zong-You Chen; Yun-Sheng Jiang; Zheng-Feng Wang; Ji-Qing Wei; Xiao Wei; Hui Tang; Zhong-Chao Li (Conservation Genetics, 2010)

Growth promotion of cucumber by pure cultures of gibberellin-producing Phoma sp. GAH7 - Muhammad Hamayun; Sumera Afzal Khan; Abdul Latif Khan; Dong-Sheng Tang; Javid Hussain; Bashir Ahmad; Yasir Anwar; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2010)

Diazoxide Reduces Status Epilepticus Neuron Damage in Diabetes - Chin-Wei Huang; Sheng-Nan Wu; Juei-Tang Cheng; Jing-Jane Tsai; Chao-Ching Huang (Neurotoxicity Research, 2010)

Preparation and the antitumor activity in vitro of polysaccharides from Tricholoma matsutake - Shuang Yang; Xiaodong Ren; Jingxue Sheng; Jiahui Lu; Tingting Li; Fangrong Tang; Yanfeng Wang; Lingjun Meng; Qingfan Meng; Lirong Teng (World Journal of Microbiology and Biotechnology, 2010)

Synthesis and Luminescent Properties of Lanthanide Complexes with Structurally Related Novel Multipodal Ligands - Qing Wang; Xu-Huan Yan; Wei-Sheng Liu; Min-Yu Tan; Yu Tang (Journal of Fluorescence, 2010)

Ageing in nematodes: do antioxidants extend lifespan in Caenorhabditis elegans? - Pamela Boon Li Pun; Jan Gruber; Soon Yew Tang; Sebastian Schaffer; Raphael Lee Sheng Ong; Sheng Fong; Li Fang Ng; Irwin Cheah; Barry Halliwell (Biogerontology, 2010)

The common variant in the GSTM1 and GSTT1 genes is related to markers of oxidative stress and inflammation in patients with coronary artery disease: a case-only study - Jian-Jin Tang; Ming-Wei Wang; En-zhi Jia; Jian-Jun Yan; Qi-Ming Wang; Jun Zhu; Zhi-Jian Yang; Xiang Lu; Lian-sheng Wang (Molecular Biology Reports, 2010)

Investigation of three-dimensional circulation and hydrography over the Pearl River Estuary of China using a nested-grid coastal circulation model - Liqun Tang; Jinyu Sheng; Xiaomei Ji; Wenhong Cao; Dabin Liu (Ocean Dynamics, 2009)

Synthesis and characterisation of seleno- Cynomorium songaricum Rupr. polysaccharide - Ji Zhang; Feng-Xia Wang; Zhong-Wang Liu; Sheng-Tang Zhang; Yu-Yuan Zhang; Jun-Yu Liang; Yun-Pu Wang (Natural Product Research, 2009)

Changes in topsoil carbon stock in the Tibetan grasslands between the 1980s and 2004 - YUANHE YANG; JINGYUN FANG; PETE SMITH; YANHONG TANG; ANPING CHEN; CHENGJUN JI; HUIFENG HU; SHENG RAO; KUN TAN; JIN‐SHENG HE (Global Change Biology, 2009)
Climate warming is likely inducing carbon loss from soils of northern ecosystems, but little evidence comes from large‐scale observations. Here we used data from a repeated soil survey and remote sensing vegetation index to explore changes in soil organic carbon (SOC) stock on the Tibetan Plateau during the past two decades. Our results showed that SOC stock in the top 30 cm depth in alpine grasslands on the plateau amounted to 4.4 Pg C (1 Pg=10 15 g), with an overall average of 3.9 kg C m −2 . SOC changes during 1980s–2004 were estimated at −0.6 g C m −2 yr −1 , ranging from −36.5 to 35.8 g C m −2 yr −1 at 95% confidence, indicating that SOC stock in the Tibetan alpine grasslands remained relatively stable over the sampling periods. Our findings are nonconsistent with previous reports of loss of soil C in grassland ecosystems due to the accelerated decomposition with warming. In the case of the alpine grasslands on the Tibetan Plateau studied here, we speculate that increased rates of decomposition as soils warmed during the last two decades may have been compensated by increased soil C inputs due to increased grass productivity. These results suggest that soil C stock in terrestrial ecosystems may respond differently to climate change depending on ecosystem type, regional climate pattern, and intensity of human disturbance.

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Screening and identification of natural antisense transcripts in Helicobacter pylori by a novel approach based on RNase I protection assay - Bin Xiao; Wei Li; Gang Guo; Bo-Sheng Li; Zhen Liu; Bin Tang; Xu-Hu Mao; Quan-Ming Zou (Molecular Biology Reports, 2009)

A fast automatic recognition and location algorithm for fetal genital organs in ultrasound images - Sheng Tang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Development of gene-tagged markers for quantitative trait loci underlying rice yield components - Chang-Jie Yan; Song Yan; Ya-Chun Yang; Xiu-Hong Zeng; Yu-Wei Fang; Sheng-Yuan Zeng; Chun-Yan Tian; Ya-Wei Sun; Shu-Zhu Tang; Ming-Hong Gu (Euphytica, 2009)

Association of the DRD2 and DRD3 polymorphisms with response to pramipexole in Parkinson’s disease patients - Ying-Zi Liu; Bei-Sha Tang; Xin-Xiang Yan; Jie Liu; Dong-Sheng Ouyang; Li-Nuo Nie; Lan Fan; Zhi Li; Wei Ji; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Study on Three-dimensional Visualization for Rock Structure - He-Jun Chai; Jun-Jie Wang; Sheng-Chuan Tang (Geotechnical and Geological Engineering, 2009)

Isolation and Characterization of the Native Entomopathogenic Nematode, Heterorhabditis brevicaudis, and its Symbiotic Bacteria from Taiwan - Feng-Chia Hsieh; Chiaw-Yen Tzeng; Jui-Tang Tseng; Yeong-Sheng Tsai; Menghsiao Meng; Suey-Sheng Kao (Current Microbiology, 2009)

Eight polymorphic microsatellite loci for the Chinese medicinal plant Artemisia annua L. (Asteraceae) - Hui-Run Huang; Guang Zhou; Xue-Jun Ge; Xiao Wei; Yun-Sheng Jiang; Hui Tang (Conservation Genetics, 2009)

Cladosporium sphaerospermum as a new plant growth-promoting endophyte from the roots of Glycine max (L.) Merr. - Muhammad Hamayun; Sumera Afzal Khan; Nadeem Ahmad; Dong-Sheng Tang; Sang-Mo Kang; Chae-In Na; Eun-Young Sohn; Young-Hyun Hwang; Dong-Hyun Shin; Byung-Hyun Lee; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Introduction of a seedling production method using vegetative gametophytes to the commercial farming of Laminaria in China - Bo Xu; Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Xue Xi Tang (Journal of Applied Phycology, 2009)

Diabetic Hyperglycemia Aggravates Seizures and Status Epilepticus-induced Hippocampal Damage - Chin-Wei Huang; Juei-Tang Cheng; Jing-Jane Tsai; Sheng-Nan Wu; Chao-Ching Huang (Neurotoxicity Research, 2009)

Lack of variation of ATTCT pentanucleotide repeats at ATXN10 gene between clinically diagnosed ataxia patients and normal individuals originated from Chinese Han - Jun-Ling Wang; Hong Jiang; Shen Zhang; Qian Xu; Ya-Fang Zhou; Shu-Sheng Liao; Lu Shen; Xin-Xiang Yan; Huai-Xu Zhu; Qian Pan; Kun Xia; Bei-Sha Tang (Journal of Genetics, 2008)

Influence of arbuscular mycorrhizae on photosynthesis and water status of maize plants under salt stress - Min Sheng; Ming Tang; Hui Chen; Baowei Yang; Fengfeng Zhang; Yanhui Huang (Mycorrhiza, 2008)

Preparation, Characterization and Photophysical Properties of Highly Luminescent Terbium Complexes Incorporated Into SiO2/Polymer Hybrid Material - Li Xu; Yu-Fei Ma; Kuan-Zhen Tang; Yu Tang; Wei-Sheng Liu; Min-Yu Tan (Journal of Fluorescence, 2008)

High throughput culture and gametogenesis induction of Laminaria japonica gametophyte clones - Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Shi Ju Luo; Xue Xi Tang (Journal of Applied Phycology, 2008)

Synthesis and Luminescent Properties of Lanthanide Complexes with a Novel Multipodal Ligand - Zhen-Zhong Yan; Yu Tang; Wei-Sheng Liu; Hai-Xia Cui; Min-Yu Tan (Journal of Fluorescence, 2008)

Association of Heart Rate Variability of the Elderly with Personal Exposure to PM1, PM1–2.5, and PM2.5–10 - Li-Te Chang; Chin-Sheng Tang; Ying-Zu Pan; Chang-Chuan Chan (Bulletin of Environmental Contamination and Toxicology, 2007)

Soluble Neuroprotective Antioxidant Uric Acid Analogs Ameliorate Ischemic Brain Injury in Mice - Frank Haberman; Sung-Chun Tang; Thiruma V. Arumugam; Dong-Hoon Hyun; Qian-Sheng Yu; Roy G. Cutler; Zhihong Guo; Harold W. Holloway; Nigel H. Greig; Mark P. Mattson (NeuroMolecular Medicine, 2007)

Recombinant tissue factor pathway inhibitor induces apoptosis in cultured rat mesangial cells via its Kunitz-3 domain and C-terminal through inhibiting PI3-kinase/Akt pathway - Yi-feng Lin; Nong Zhang; Hong-shen Guo; De-sheng Kong; Tao Jiang; Wang Liang; Zhong-hua Zhao; Qi-qun Tang; Duan Ma (Apoptosis, 2007)

A xyloglucan endotransglucosylase/hydrolase involves in growth of primary root and alters the deposition of cellulose in Arabidopsis - Ya-Bao Liu; Si-Min Lu; Jian-Feng Zhang; Sheng Liu; Ying-Tang Lu (Planta, 2007)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Breeding of an elite Laminaria variety 90-1 through inter-specific gametophyte crossing - Quan-Sheng Zhang; Xue-Xi Tang; Yi-Zhou Cong; Shan-Cun Qu; Shi-Ju Luo; Guan-Pin Yang (Journal of Applied Phycology, 2007)

Genetic dissection of plant height by molecular markers using a population of recombinant inbred lines in maize - Tang Ji-hua; Teng Wen-tao; Yan Jian-bing; Ma Xi-qing; Meng Yi-jiang; Dai Jin-rui; Li Jian-Sheng (Euphytica, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Improvement of the Cellulolytic Activity of Trichoderma reesei Endoglucanase IV with an Additional Catalytic Domain - Gang Liu; Xin Tang; Sheng-Li Tian; Xu Deng; Miao Xing (World Journal of Microbiology and Biotechnology, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

Quantitative trait loci mapping and epistatic analysis for grain yield and yield components using molecular markers with an elite maize hybrid - Jian-bing Yan; Hua Tang; Yi-qin Huang; Yong-lian Zheng; Jian-sheng Li (Euphytica, 2006)

A case of overlapping Bickerstaff’s brainstem encephalitis and Guillain-Barré syndrome - De-sheng Wang; Ying Tang; Ye Wang (Journal of Zhejiang University-SCIENCE B, 2006)

A new two-way nesting technique for ocean modeling based on the smoothed semi-prognostic method - Jinyu Sheng; Richard J. Greatbatch; Xiaoming Zhai; Liqun Tang (Ocean Dynamics, 2005)

Phenotypic and functional characteristics of dendritic cells derived from human peripheral blood monocytes - Ling-ling Tang; Zhe Zhang; Jie-sheng Zheng; Ji-fang Sheng; Ke-zhou Liu (Journal of Zhejiang University-SCIENCE B, 2005)

Simulating the upper ocean circulation on the belize shelf: An application of a triply nested-grid ocean circulation model - Jinyu Sheng; Liqun Tang; Liang Wang (Journal of Ocean University of China, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

A two-way nested-grid ocean-circulation model for the Meso-American Barrier Reef System - Jinyu Sheng; Liqun Tang (Ocean Dynamics, 2004)

Cloning and identification of a cDNA that encodes a novel human protein with thrombospondin type I repeat domain, hPWTSR - Jin-Zhong Chen; Shu Wang; Rong Tang; Quan-Sheng Yang; Enpeng Zhao; Yaoqiong Chao; Kang Ying; Yi Xie; Yu-Min Mao (Molecular Biology Reports, 2002)

Characterization of resistance to Helicoverpa armigera in three lines of transgenic Bt Upland cotton - Jing Sun; Canming Tang; Xiefei Zhu; Wangzhen Guo; Tianzhen Zhang; Weijun Zhou; Fengxia Meng; Jingliang Sheng (Euphytica, 2002)

Distribution of Polycyclic Aromatic Hydrocarbons in Aerosols and Dustfall in Macao - Qi Shihua; Yan Jun; Zhang Gan; Fu Jiamo; Sheng Guoying; Wang Zhishi; S. M. Tong; U. W. Tang; Min Yunshun (Environmental Monitoring and Assessment, 2001)

Synthesis and diversity analysis of lead discovery piperazine-2-carboxamide libraries - Timothy F. Herpin; George C. Morton; Allison K. Dunn; Cedric Fillon; Paul R. Menard; Sheng Yu Tang; Joseph M. Salvino; Richard F. Labaudinière (Molecular Diversity, 1998)

Reduced vascular β-adrenergic receptors and catecholamine response in rats with lead induced hypertension - Huoy-Rou Chang; Shun-Sheng Chen; Der-An Tsao; Juei-Tang Cheng; Chi-Kung Ho; Hsin-Su Yu (Archives of Toxicology, 1997)

Inhibitory mechanism of lead on transferrin-bound iron uptake by rabbit reticulocytes: A fractal analysis - Zhong Ming Qian; De Sheng Xiao; Qin Wang; Pak Lai Tang; Yong Mei Pu (Molecular and Cellular Biochemistry, 1997)